3-Deoxygalactosone, a new glucose degradation product in peritoneal dialysis fluids: Identification, quantification by HPLC/DAD/MSMS and its pathway of formation - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2011)
Heat sterilization of peritoneal dialysis (PD) fluids leads to the formation of glucose degradation products (GDPs), which considerably impair long-term application of PD. Knowledge of the exact composition of GDPs present in a PD fluid is important to improve the biocompatibility of dialysis solutions. The present study conducted a targeted screening for novel GDPs with α-dicarbonyl structure in PD fluids. Thus, 3-deoxygalactosone (3-DGal) was identified for the first time in PD fluids. Quantification of 3-DGal was achieved by high-performance liquid chromatography (HPLC)/DAD/MSMS after derivatization with o-phenylendiamine to yield the quinoxaline derivative. Baseline separation of all α-dicarbonyl GDPs, particularly of the diastereomers 3-deoxyglucosone (3-DG) and 3-DGal, required the application of a polar, phenyl-based RP column for HPLC and additional pH-gradient elution. Concentrations of 3-DGal ranged between 55.8 and 136.9 μM in single-chamber PD fluids, and between 2.5 and 12.4 μM in double-chamber PD fluids. In solutions containing glucose, 3-DGal is formed from 3-DG via the intermediate 3,4-dideoxyglucosone-3-ene (3,4-DGE). Further studies are now required to determine the (patho-)physiological properties of 3-DGal. © 2010 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.3deoxy
Keywords: 3-Deoxygalactosone (3-DGal); [alpha]-Dicarbonyl compounds; Glucose degradation products (GDPs); HPLC; Peritoneal dialysis fluid; Quinoxaline derivatives

5-Hydroxy-2-methyl-4-(alkylamino)-2H-pyran-3(6H)-one: a new sugar derived aminoreductone - Knerr, Thomas; Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 1994)
2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (3) is one of the main products obtained from glucose under the conditions of the Maillard reaction. Heating of 3 in the presence of primary amines leads to the formation of 5-hydroxy-2-methyl-4-(alkylamino)-2H-pyran-3(6H)-one (11). These new aminoreductones can also be isolated from glucose/amine reaction mixtures. © 1994 American Chemical Society.
UnivIS-Import:2015-03-05:Pub.1994.nat.dchph.llmch.5hydro
Keywords: Aminoreductone; Glucose; HPLC; Maillard reaction

Absolute quantification of two antimicrobial peptides alpha(S2)-casein(182-207) and alpha(S2)-casein(151-181) in bovine milk by UHPLC-ESI-MS/MS in sMRM mode - Liu, Yufang; Pischetsrieder, Monika (Food Chemistry, 2018)
To evaluate if the recently identified antimicrobial milk peptides alpha(S2)-casein(182-207) and alpha(S2)-casein(151-181) can be of physiological or technological relevance, their presence in commercial milk was investigated. Thus, a UHPLC-ESI-MS/MS scheduled multiple reaction monitoring method was developed for quantification using stable isotope-labeled peptides. The developed protocol gave very good linear response (R-2 > 0.99) for both peptides, recovery > 95% and coefficients of variations of 5.51% and 4.79%. The limits of detection (0.3 nM alpha(S2)-casein(182-207) and 0.5 nM alpha(S2)-casein(151-181)) were low enough to detect both peptides without further enrichment. The highest peptide concentration was recorded in pasteurized milk (1.36 mu M alpha(S2)-casein(182-207) and 0.20 mu M alpha(S2)-casein(151-181)). The concentration of alpha(S2)-casein(182-207) was in a range that was previously reported to act bacteriostatic against Bacillus subtilis. Industrial milk processing led to a significant loss of both peptides resulting in a mean concentration of 0.47 mu M alpha(S2)-casein(182-207) and 0.098 mu M alpha(S2)-casein(151-181) in ultrahigh-temperature milk.
Keywords: alpha(S2)-casein(182-207); Antimicrobial peptides; Milk; UHPLC-ESI-MS/MS-sMRM; Absolute quantification

Absorption, Biokinetics, and Metabolism of the Dopamine D2 Receptor Agonist Hordenine (N, N-Dimethyltyramine) after Beer Consumption in Humans - Sommer, Thomas; Göen, Thomas; Budnik, Nadja; Pischetsrieder, Monika (Journal of agricultural and food chemistry, 2020)
Hordenine, a natural constituent of germinated barley, is a biased agonist of the dopamine D2 receptor. This pilot study investigated the biokinetics of hordenine and its metabolites in four volunteers consuming beer equal to 0.075 mg hordenine/kg body weight. A new ultrahigh-performance liquid chromatography method coupled to electrospray ionization tandem mass spectrometry (UHPLC-ESI-MS/MS) method determined maximum plasma concentrations of 12.0-17.3 nM free hordenine after 0-60 min. Hordenine phase-II metabolism was first dominated by sulfation, but later by glucuronidation. The elimination half-lives in plasma were 52.7-66.4 min for free hordenine and about 60/80 min longer for hordenine sulfate and hordenine glucuronide. Urinary excretion peaked 2-3.5 h after consumption and accumulated to 3.78 μmol within 24 h, corresponding to 9.9% of the ingested dose. The observed hordenine levels in plasma seem too low to provoke direct interaction with the dopamine D2 receptor related to food reward, but synergistic or additive effects with alcohol or N-methyltyramine may occur.
CRIS-Team Scopus Importer:2020-03-10
Keywords: beer; biokinetics; dopamine D2 receptor; hordenine; human metabolism

Accumulation of non-enzymatic glycation products on proteins and DNA - Kislinger, Thomas; Schneider, Marc; Pischetsrieder, Monika (Aging. Morphological, Biochemical, Molecular and Social Aspects, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.accumu

A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

Activation of membrane-located Ca2+ channels by hop beta acids and their tricyclic transformation products - Schulz, Carolin; Fritz, Nikolas; Sommer, Thomas; Krofta, Karel; Friedland, Kristina; Pischetsrieder, Monika (Food Chemistry, 2018)
Beta-bitter acids of hops (lupulones) revealed sedative and antidepressant-like effects in animal studies. Transformation of beta-acids during beer brewing leads to the formation of tricyclic transformation products, which have a close structural analogy to hyperforin. The latter compound is responsible for the antidepressant activity of St. John's wort by activation of TRPC6 cation channels in neuronal-like cells leading to Ca2+ influx. In this study, nortricyclolupones, dehydrotricyclolupones, and tricyclolupones were isolated from a wort-boiling model and their structures were elucidated by UHPLC-DAD, UHPLC-ESI–MS/MS and 1D/2D-NMR spectroscopy. Beta-bitter acids and their transformation products induced Ca2+ influx in PC12 cells to the same extent as hyperforin. Application of a Ca2+-free environment abolished the Ca2+ elevation, indicating that the increase is mediated by influx across the plasma membrane. Thus, activation of neuronal-like Ca2+-channels by lupulones and tricyclolupones represent a novel mechanism contributing to the antidepressant activity of hops.
Keywords: Antidepressant; beta-bitter acids; Ca2+ influx; Hops; Lupulones; Neuronal-like cells; Tricyclolupones

Activation of the transcription factor Nrf2 in macrophages, Caco-2 cells and intact human gut tissue by Maillard reaction products and coffee - Sauer, Tanja; Raithel, Martin; Kressel, Jürgen; Münch, Gerald; Pischetsrieder, Monika (Amino Acids, 2013)
In addition to direct antioxidative effects, Maillard reaction products (MRPs) could increase the antioxidative capacity of cells through the induction of cytoprotective enzymes. Since many of those enzymes are regulated by the transcription factor Nrf2, the effect of MRPs on nuclear translocation of Nrf2 in macrophages and Caco-2 cells was investigated. Stimulation of both cell types by MRPs showed a concentration-dependent significant increase in nuclear translocation of Nrf2 up to fivefold after short-term (2 h) and up to 50-fold after long-term treatment (24 h). In intact human gut tissue, nuclear translocation of Nrf2 was significantly twofold increased after short-term incubation. To study the activation mechanisms, macrophages and Caco-2 cells were stimulated with MRPs in the presence of catalase, which significantly suppressed Nrf2 activation. Thus, activation was related to extracellular H 2O2 continuously formed from MRPs. Short-term incubation with coffee, a MRP-rich beverage, led to a trend towards Nrf2 activation in macrophages, but not in Caco-2 cells or intact human gut tissue. Long-term incubation with coffee (1-4 mg/mL) significantly increased nuclear Nrf2 up to 17-fold. Since raw coffee was inactive under the tested conditions, the effect was related to roasting products. Coffee-induced Nrf2 translocation was, however, only slightly reversed by catalase. Therefore, the Nrf2 activity of coffee can only partially be explained by MRP-induced, H2O 2-dependent mechanisms. Thus, it can be concluded that MRPs may increase the antioxidative capacity inside the cell by inducing Nrf2-regulated signalling pathways not only in different cell types, but also in intact gut tissue. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-14:Pub.2013.nat.dchph.llmch.activa
Keywords: Coffee; Hydrogen peroxide; Intact human gut tissue; Maillard products; Nrf2; Roasting products

A diet rich in Mailllard reaction products protects LDL against copper induced oxidation ex vivo, a human intervention trial - Dittrich, Ralf; Dragonas, Charalampos; Kannenkeril, Dennis; Hoffmann, Inge; Müller, Andreas; Beckmann, Matthias; Pischetsrieder, Monika (Food Research International, 2009)
Maillard reaction products (MRPs) have antioxidative properties in vitro but the influence of a diet rich in MRPs on oxidative damage in vivo remains unknown. In this study, the influence of thermally processed foods rich in MRPs on copper induced oxidation of human low-density lipoprotein (LDL) in vitro was examined. Moreover, oxidative resistance of LDL (OR) in blood plasma of eight healthy subjects was monitored, who consumed diets poor and rich in MRPs in weekly turn for 3 weeks. Dark beer, bread crust, and roasted coffee led to a statisticaIly significant increased OR in vitro compared to pale beer, bread crumb, and raw coffee. The consumption of a diet rich in MRPS significantly increased plasma OR compared to the diet poor in MRPs by 35.5%. This study indicates that thermally processed foods rich in MRPs inhibit the LDL oxidation in vitro and have the ability to reduce oxidative modification of LDL in viv
UnivIS-Import:2015-04-14:Pub.2009.nat.dchph.llmch.adietr
Keywords: Beer; Coffee; Diet; LDL oxidation; Maillard reaction products

Advanced glycation end products (AGE) and the cytokine TNF-alpha, TGF-beta and IL-6 stimulate the expression of the receptor of AGE (RAGE) in hepatic stellate cells - Lohwasser, Christina; Pischetsrieder, Monika; Schuppan, Detlef (Hepatology, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.advanc

Advanced Glycation End Products Augments Signaling from Toll-like Receptors - Dinarello, Charles A.; Reznikov, Leonid; Waksman, Javier; Pischetsrieder, Monika; Shaldon, Stanley (Blood Purification, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.advanc

Advanced Maillard Products of Disaccharides: Analysis and Relation to Reaction Conditions - Pischetsrieder, Monika; Severin, Theodor (Chemical Markers for Processed and Stored Foods, 1996)
The degradation of 1,4-glycosidic linked disaccharides, such as maltose and lactose under the condition of the Maillard reaction has been investigated. Two aminoreductones could be isolated which are derived from the 4-deoxyglucosone. Breakdown via the 1-deoxyglucosone pathway leads to 11 typical disaccharide-products. These compounds are not found in glucose reaction mixtures. All these substances can be analyzed using an HPLC system. The correlation between product composition and reaction temperature, time and pH-value has been investigated.
UnivIS-Import:2015-04-20:Pub.1996.nat.dchph.llmch.advanc

Aged garlic extract and S-allyl cysteine prevent formation of advanced glycation end-products - Ahmad, Muhammad Saeed; Pischetsrieder, Monika; Ahmed, Nessar (European Journal of Pharmacology, 2007)
Hyperglycaemia causes increased protein glycation and the formation of advanced glycation endproducts which underlie the complications of diabetes and ageing. Glycation is accompanied by metal-catalysed oxidation of glucose and Amadori products to form free radicals capable of protein fragmentation. Aged garlic extract is a potent antioxidant with established lipid-lowering effects attributed largely to a key ingredient called S-allyl cysteine. This study investigated the ability of aged garlic extract and S-allyl cysteine to inhibit advanced glycation in vitro. Bovine serum albumin (BSA) was glycated in the presence of Cu2+ ions and different concentrations of aged garlic extract and protein fragmentation was examined by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Lysozyme was glycated by glucose or methylglyoxal in the presence of different concentrations of aged garlic extract or S-allyl cysteine with subsequent analysis of glycationderived crosslinking using SDS-PAGE. Amadori-rich protein was prepared by dialysing lysozyme that had been glycated by ribose for 24 h. This ribated lysozyme was reincubated and the effects of aged garlic extract, S-allyl cysteine and pyridoxamine on glycation-induced crosslinking was monitored. Aged garlic extract inhibited metal-catalysed protein fragmentation. Both aged garlic extract and S-allyl cysteine inhibited formation of glucose and methylglyoxal derived advanced glycation endproducts and showed potent Amadorin activity when compared to pyridoxamine. S-allyl cysteine inhibited formation of carboxymethyllysine (CML), a non-crosslinked advanced glycation endproduct derived from oxidative processes. Further studies are required to assess whether aged garlic extract and S-allyl cysteine can protect against the harmful effects of glycation and free radicals in diabetes and ageing.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.agedga
Keywords: Glycation; Aged garlic extract; S-allyl cysteine; Diabetes; Antioxidant

Analysis and biological relevance of advanced glycation end-products of DNA in eukaryotic cells - Breyer, Viola; Frischmann, Matthias; Bidmon, Clemens; Schemm, Annelen; Schiebel, Katrin; Pischetsrieder, Monika (Febs Journal, 2008)
Advanced glycation end-products (AGEs) of DNA are formed spontaneously by the reaction of carbonyl compounds such as sugars, methylglyoxal or dihydroxyacetone in vitro and in vivo. Little is known, however, about the biological consequences of DNA AGEs. In this study, a method was developed to determine the parameters that promote DNA glycation in cultured cells. For this purpose, the formation rate of N2-carboxyethyl-2′- deoxyguanosine (CEdG), a major DNA AGE, was measured in cultured hepatic stellate cells by liquid chromatography (LC)-MS/MS. In resting cells, a 1.7-fold increase of CEdG formation rate was observed during 14 days of incubation. To obtain insights into the functional consequences of DNA glycation, CEdG was introduced into a luciferase reporter gene vector and transfected into human embryonic kidney (HEK 293 T) cells. Gene activity was determined by chemiluminescence of the luciferase. Thus, CEdG adducts led to a dose-dependent and highly significant decrease in protein activity, which is caused by loss of functionality of the luciferase in addition to reduced transcription of the gene. When the CEdG-modified vector was transformed into Escherichia coli, a loss of ampicillin resistance was observed in comparison to transformation with the unmodified plasmid. These results indicate that CEdG accumulates in the genomic DNA of resting cells, which could lead to diminished protein activity. © 2008 The Authors.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.analys
Keywords: Advanced glycation end-products; DNA; Eukaryotic cells; Maillard reaction; N

Analysis of Chemically Labile Glycation Adducts in Seed Proteins: Case Study of Methylglyoxal-Derived Hydroimidazolone 1 (MG-H1). - Antonova, Kristina; Vikhnina, Maria; Soboleva, Alena; Mehmood, Tahir; Heymich, Marie-Louise; Leonova, Tatiana; Bankin, Mikhail; Lukasheva, Elena; Gensberger-Reigl, Sabrina; Medvedev, Sergej; Smolikova, Galina; Pischetsrieder, Monika; et al. (International Journal of Molecular Sciences, 2019)
Seeds represent the major source of food protein, impacting on both human nutrition and animal feeding. Therefore, seed quality needs to be appropriately addressed in the context of viability and food safety. Indeed, long-term and inappropriate storage of seeds might result in enhancement of protein glycation, which might affect their quality and longevity. Glycation of seed proteins can be probed by exhaustive acid hydrolysis and quantification of the glycation adduct Nepsilon-(carboxymethyl)lysine (CML) by liquid chromatography-mass spectrometry (LC-MS). This approach, however, does not allow analysis of thermally and chemically labile glycation adducts, like glyoxal-, methylglyoxal- and 3-deoxyglucosone-derived hydroimidazolones. Although enzymatic hydrolysis might be a good solution in this context, it requires aqueous conditions, which cannot ensure reconstitution of seed protein isolates. Because of this, the complete profiles of seed advanced glycation end products (AGEs) are not characterized so far. Therefore, here we propose the approach, giving access to quantitative solubilization of seed proteins in presence of sodium dodecyl sulfate (SDS) and their quantitative enzymatic hydrolysis prior to removal of SDS by reversed phase solid phase extraction (RP-SPE). Using methylglyoxal-derived hydroimidazolone 1 (MG-H1) as a case example, we demonstrate the applicability of this method for reliable and sensitive LC-MS-based quantification of chemically labile AGEs and its compatibility with bioassays.
Keywords: Advanced glycation end products (AGEs); enzymatic hydrolysis; glycation; methylglyoxal-derived hydroimidazolone 1 (MG-H1); seeds; seed ageing; seed quality; sodium dodecyl sulfate (SDS)

Analysis of Chlorate in Chemical Leavening Agents Used for Bakery Products by Liquid Chromatography-Mass Spectrometry - Gensberger-Reigl, Sabrina; Rodrigues Guimarães Abreu, Vera Lúcia; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2022)
Chlorate is a food contaminant that is mainly attributed to the use of chlorinated water and disinfectants. The present study investigated if chlorate could also occur as a process contaminant in chemical leavening agents for baking products. Thus, a sensitive and rapid ultrahigh-performance liquid chromatography-tandem mass spectrometry method was developed and validated. Chlorate was quantified using an isotopically labeled internal standard after complete degassing of carbonate-based products. The limit of detection/limit of quantification was 0.02 and 0.1 mg/kg, respectively, with recovery rates between 97.0 and 101.2% (concentration levels: 0.3, 1.4, or 5.0 mg/kg). Samples of baking powder, sodium bicarbonate, ammonium bicarbonate, and potassium carbonate were analyzed. Chlorate was detected in all samples of baking powder in concentrations of 0.23-1.87 mg/kg. Potassium carbonate contained the highest chlorate levels, with a maximum of 60.9 mg/kg. These results indicate that baking powder and, particularly, potassium carbonate can be relevant sources of chlorate in food.
CRIS-Team Scopus Importer:2022-11-25
Keywords: baking powder; chlor-alkali electrolysis; chlorate; potassium carbonate; sodium bicarbonate; UHPLC-MS/MS

Analysis of DNA-bound advanced glycation end-products by LC and mass spectrometry - Bidmon, Clemens; Frischmann, Matthias; Pischetsrieder, Monika (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2007)
Sugars and sugar degradation products readily react in vitro with guanine derivatives, resulting in the formation of DNA-bound advanced glycation end-products (DNA-AGEs). The two diastereomers of N2-(1-carboxyethyl)-2′-deoxyguanosine (CEdGA,B) and the cyclic adduct of methylglyoxal and 2′-deoxyguanosine (mdG) (N2-7-bis(1-hydroxy-2-oxopropyl)-2′-deoxyguanosine have also been detected in cultured cells and/or in vivo. LC-MS/MS methods have been developed to analyze sensitively DNA adducts in vitro and in vivo. In this paper, the chemical structures of possible DNA-AGEs and the application of LC-MS/MS to measure DNA-AGEs are reviewed. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.analys
Keywords: Advanced glycation end-products; N2-(1-carboxyethyl)-2'-deoxyguanosine; CEdG A; B; DNA; LC–MS/MS

Analysis of Glycated and Ascorbylated Proteins by Gas Chromatography- Mass Spectrometry - Hasenkopf, Katrin; Rönner, Birgit; Hiller, Hartmut; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2002)
Proteins or poly-L-lysine which were incubated in the presence of ascorbic acid, dehydroascorbic acid (ascorbylation), or various sugars (glycation) were analyzed by gas chromatography-mass spectrometry (GC-MS). To also detect more labile reaction products, the Maillard modified proteins or poly-L-lysine were enzymatically hydrolyzed and reacted with N-methyl-N-(tert-butyldimethylsilyl)-trifluoroacetamide to form the N(O)-tert-butyldimethylsilyl (tBDMS) derivatives prior to GC analysis. Under these conditions, the known Maillard products Nε-(carboxymethyl)lysine (1), oxalic acid mono-Nε-lysinylamide (2), and Nε-(carboxyethyl)lysine (3) could be simultaneously detected and quantified in glycated and ascorbylated proteins. Additionally, Nε-(1-carboxy-3-hydroxypropyl)-L-lysine (4) was identified for the first time as a Maillard product of proteins. Under the conditions applied here, 4 was found only in ascorbylated proteins or poly-L-lysine, but not in glycated proteins. Maillard-modified poly-L-lysine was further subjected to high-performance liquid chromatography (HPLC) analysis after enzymatic hydrolysis and formation of the phenyl isothiocyanate derivatized amino acids. Using this method, Nε-formyl-L-lysine (5), which cannot be distinguished from 2 by GC-MS analysis, was identified for the first time as a glycation product. Compound 5 is mainly formed from ribose, lactose, and fructose. The indicated Maillard products were quantified in β-lactoglobulin (GC-MS) or poly-L-lysine (HPLC) which were glycated or ascorbylated using different precursors.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.analys
Keywords: Ascorbic acid; Ascorbylation; GC-MS; Glycation; Maillard reaction

Analysis of lysozyme in cheese by immunocapture mass spectrometry - Schneider, Nadine; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2010)
The enzyme lysozyme is used as a preservative to prevent late blowing of ripened cheese, caused by Clostridium tyrobutyricum. Since the enzyme is extracted from hen egg white, lysozyme has to be declared on food product labels as a potential allergen. Here, a method is reported that combines immunocapture purification and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) analysis for the detection of lysozyme in cheese samples. Cheese extracts were treated with magnetic particles coated with a monoclonal antibody directed against lysozyme. After immunocapture purification, lysozyme was detected by MALDI-TOF-MS. The limit of detection of the assay was about 5 mg/kg lysozyme in cheese. The method reliably distinguished between cheese samples which had been produced with and without lysozyme. Thus, the novel assay allows the reliable, sensitive, and specific detection of lysozyme in a food matrix. The assay could be easily adapted to other target peptides and proteins in complex food matrices and, therefore, has a broad application potential, e.g. for the analysis of allergens. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.analys
Keywords: Cheese; Immunocapture mass spectrometry; Lysozyme; Matrix-assisted laser desorption/ionization mass spectrometry

Analysis of nisin A, nisin Z and their degradation products by LCMS/MS - Pischetsrieder, Monika; Schneider, Nadine; Werkmeister, Knut (Food Chemistry, 2011)
The peptides nisin A and nisin Z belong to type-A lantibiotics applied as preservatives in cheese production. The present study optimised and validated a liquid chromatography-tandem mass spectrometry (LCMS/MS) method for the analysis of nisin A in cheese. Since nisin A was not detectable in nisin-containing commercial cheese samples, an additional LCMS/MS method for the quantification of nisin Z was developed and validated. Quantification was performed by external calibration and standard addition. The latter method provided a non-significantly higher recovery rate for the tested cheese matrix. During the production of processed cheese, nisin A and nisin Z undergo significant degradation. Six degradation products of nisin A or nisin Z, respectively, were detected and assigned to nisin A/Z + H2O, nisin A/Z1-32, and nisin A/Z1-32 + H2O. In two out of eight commercial processed cheese samples, 1.6, resp. 1.7 mg nisin Z/kg cheese was measured, whereas nisin A was not detectable in any of the samples. © 2011 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.analys
Keywords: Cheese; Lantibiotic; LCMS/MS; Nisin; Nisin degradation products; Nisin modifications

Analysis of Protein Glycation Products by MALDI-TOF/MS - Kislinger, Thomas; Humeny, Andreas; Becker, Cord-Michael; Peich, Carlo; Pischetsrieder, Monika (Annals of the New York Academy of Sciences, 2005)
Matrix-assisted laser desorption ionization-mass spectrometry with time-of-flight detection (MALDI-TOF/MS) is a promising tool to analyze advanced glycation end product (AGE)-modified proteins. The combination of soft ionisation (MALDI) with time-of-flight mass detection allows analysis of peptides and proteins of a molecular mass up to 300 kDa with minimal sample workup. Because the direct structural analysis of intact AGE proteins is not possible due to the formation of broad and poorly resolved peaks, peptide mapping was introduced into the analysis of AGE proteins by MALDI-TOF/MS, allowing site-specific analysis of defined AGEs. When methylglyoxal-modified lysozyme was subjected to MALDI-TOF/MS peptide mapping, methylimidazolone and argpyrimidine attached to the arginine residue and carboxyethyl (CEL) bound to the lysine were detected on peptideaa1-7 (KVFGRCE). In contrast, only one methylimidazolone was found on peptideaa8-35 (LAAAMKRHGLDNYRGYSLGNWVCAAKFE) and peptideaa120-129 (VQAWIRGCRL), respectively. The analysis of AGE protein, which had been incubated with glucose, revealed the presence of am Amadori product and a carboxymethyl residue (CML) on peptideaa1-7 and peptideaa8-35, as well as an imidazolone A on peptideaa120-129. Furthermore, the early Maillard reaction of lysozyme, which had been glycated by seven different sugars, was monitored by MALDI-TOF/MS peptide mapping. Finally, this approach was successfully applied for site- and product-specific relative quantification of AGEs. For example, kinetics of CML and Amadori product formation on peptide aa1-7, as well as imidazolone A formation on peptide aa120-129, were determined. © 2005 New York Academy of Sciences.
UnivIS-Import:2015-04-16:Pub.2005.nat.dchph.llmch.analys
Keywords: Advanced glycation end products; Maillard reaction; MALDI-TOF/MS; Mass spectrometry; Peptide mapping

Analysis of Protein Glycation Products by Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry - Kislinger, Thomas; Humeny, Andreas; Pischetsrieder, Monika (Current Medicinal Chemistry, 2004)
The term protein glycation summarizes non-enzymatic reactions between amino groups of proteins and sugars or sugar degradation products, leading to early glycation products (intact sugar attached) and advanced glycation end-products (AGEs). Protein glycation is involved in the progression of several diseases, such as diabetes, uremia, and atherosclerosis. However, qualitative and quantitative analysis of in vitro or in vivo glycated proteins is still a challenging task. The introduction of matrix-assisted laser desorption ionization time-of-flight technique (MALDI-TOF) changed mass spectrometry (MS) into a valuable tool for biomedical analysis, because the soft ionization procedure allows the measurement of proteins up to 100 kDa. In the last few years, MALDI-TOF-MS was applied to the investigation of glycation processes: the analyses of plasma proteins from diabetic or uremic patients allowed a precise determination of the average number of sugar residues attached to serum albumin or immunoglobulins of each patient. Thus, a more individualized diagnosis of each patient was achieved by MALDI-TOF-MS than by other diagnostic tools. In a similar way, the glycation rate of hemoglobin, isolated from diabetic blood and of β-2-microglobulin isolated from amyloid plaques from uremic patients was determined. The application of MALDI-TOF-MS for in vitro studies revealed important new insights into glycation mechanisms. Whereas the measurement of the intact proteins allows the determination of the average glycation rate, peptide mapping prior to MALDI-TOF-MS can reveal the exact structures of the glycation products and the glycation site. Furthermore, when the unmodified peptide is used as internal standard, MALDI-TOF-MS can also be used for reliable, site specific relative quantification of defined glycation products. © 2004 Bentham Science Publishers Ltd.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.analys
Keywords: Advanced glycation end-products; Amadori product; Maillard reaction; MALDI-TOF-MS; Mass spectrometry; Peptide mapping; Protein glycation

Analysis of sugar degradation products with alpha-dicarbonyl structure in carbonated soft drinks by UHPLC-DAD-MS/MS - Gensberger, Sabrina; Glomb, Marcus; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2013)
Sugar-sweetened carbonated soft drinks (CSDs) are broadly consumed worldwide. The added sugar, particularly high-fructose corn syrup (HFCS), can be an important source of sugar degradation products, such as α-dicarbonyl compounds. This study recorded the α-dicarbonyl profile in CSDs by ultrahigh-performance liquid chromatography with hyphenated diode array-tandem mass spectrometry after derivatization with o-phenylenediamine. Thus, 3-deoxy-d-erythro-hexos-2-ulose (3-DG), d-lyxo-hexos-2-ulose (glucosone), 3-deoxy-d-threo-hexos-2-ulose (3-DGal), 1-deoxy-d-erythro-hexos-2,3-diulose (1-DG), 3,4-dideoxyglucosone-3-ene (3,4-DGE), methylglyoxal, and glyoxal were identified as major α-dicarbonyls and, with the exception of glyoxal, quantified (recovery rates, 85.6-103.1%; RSD, 0.8-3.6%). Total α-dicarbonyl concentration in 25 tested commercial products ranged between 0.3 and 116 μg/mL and was significantly higher in HFCS-sweetened CSDs compared to CSDs sweetened with HFCS and sucrose or with sucrose alone. Predominant was 3-DG (≤87 μg/mL) followed by glucosone (≤21 μg/mL), 3-DGal (≤7.7 μg/mL), 1-DG (≤2.8 μg/mL), methylglyoxal (≤0.62 μg/mL), and 3,4-DGE (≤0.45 μg/mL). © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.analys
Keywords: α-dicarbonyl compounds (α-DCs); carbonated soft drinks (CSD); high-fructose corn syrup (HFCS); o-phenylenediamine (OPD); sugar degradation products

Analysis of the endogenous peptide profile of milk: Identification of 248 mainly casein-derived peptides - Baum, Florian; Fedorova, Maria; Ebner, Jennifer; Hoffmann, Ralf; Pischetsrieder, Monika (Journal of Proteome Research, 2013)
Milk is an excellent source of bioactive peptides. However, the composition of the native milk peptidome has only been partially elucidated. The present study applied matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) directly or after prefractionation of the milk peptides by reverse-phase high-performance liquid chromatography (RP-HPLC) or OFFGEL fractionation for the comprehensive analysis of the peptide profile of raw milk. The peptide sequences were determined by MALDI-TOF/TOF or nano-ultra-performance liquid chromatography-nanoelectrospray ionization-LTQ-Orbitrap-MS. Direct MALDI-TOF-MS analysis led to the assignment of 57 peptides. Prefractionation by both complementary methods led to the assignment of another 191 peptides. Most peptides originate from αS1-casein, followed by β-casein, and α S2-casein. κ-Casein and whey proteins seem to play only a minor role as peptide precursors. The formation of many, but not all, peptides could be explained by the activity of the endogenous peptidases, plasmin or cathepsin D, B, and G. Database searches revealed the presence of 22 peptides with established physiological function, including those with angiotensin-converting- enzyme (ACE) inhibitory, immunomodulating, or antimicrobial activity. © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.analys_8
Keywords: bioactive peptides: milk; cathepsin; ESI-MS: caseins; HPLC prefractionation; MALDI-TOF-MS; OFFGEL fractionation; peptide profiling; plasmin

Analysis of the peptide profile of milk and its changes during thermal treatment and storage - Meltretter, Jasmin; Schmidt, Alexander; Humeny, Andreas; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2008)
In this study a new method was developed for analysis of the low molecular weight protein fraction of milk, allowing a simple and fast overview of the peptide profile of various milk samples. For this purpose, immobilized metal affinity chromatography (IMAC) was coupled with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). By this technique, two major peptides in milk could be identified as fragments of alpha-s1-casein. During heat treatment of raw milk, five new peptides were generated, the origin of which could be assigned to the casein fraction. Storage experiments with extended shelf life milk at 4 degrees C did not show any changes in the peptide profile, whereas in ultra high temperature milk stored at room temperature, one peptide increased significantly, which was identified as the N-terminus of alpha-s1-casein. The peptide was assumed to be formed in an enzymatic reaction, which was confirmed in a storage experiment with sterilized milk. Analyses of different commercially available milk samples confirmed the results obtained with the heated and stored milk. Furthermore, differences in the peptide profiles of the samples, probably due to different cow breeds or lactation stages, were observed. These results establish IMAC prior to MALDI-TOF-MS as a valid tool for the rapid analysis of the peptide profile of milk.
Keywords: Milk; peptides; proteolysis; heat treatment; storage; immobilized metal affinity chromatography; matrix-assisted laser desorption/ionization mass pectrometry

Analytical Methods to Determine the Influence of Maillard Products on Inflammatory Reactions of Hepatic and Intestinal Cells in Vitro - Lohwasser, Christina; Schuppan, Detlef; Pischetsrieder, Monika (Biologically-Active Phytochemicals in Food, 2001)
UnivIS-Import:2015-04-20:Pub.2001.nat.dchph.llmch.analyt

Antioxidative, antifungal and additive activity of the antimicrobial peptides leg1 and leg2 from chickpea - Heymich, Marie-Louise; Nißl, Laura; Hahn, Dominik; Noll, Matthias; Pischetsrieder, Monika (Foods, 2021)
The fight against food waste benefits from novel agents inhibiting spoilage. The present study investigated the preservative potential of the antimicrobial peptides Leg1 (RIKTVTSFDLPALRFLKL) and Leg2 (RIKTVTSFDLPALRWLKL) recently identified in chickpea legumin hydrolysates. Checkerboard assays revealed strong additive antimicrobial effects of Leg1/Leg2 with sodium benzoate against Escherichia coli and Bacillus subtilis with fractional inhibitory concentrations of 0.625 and 0.75. Additionally, Leg1/Leg2 displayed antifungal activity with minimum inhibitory concentrations of 500/250 µM against Saccharomyces cerevisiae and 250/125 µM against Zygosaccharomyces bailii. In contrast, no cytotoxic effects were observed against human Caco-2 cells at concentrations below 2000 µM (Leg1) and 1000 µM (Leg2). Particularly Leg2 showed antioxidative activity by radical scavenging and reducing mechanisms (maximally 91.5/86.3% compared to 91.2/94.7% for the control ascorbic acid). The present results demonstrate that Leg1/Leg2 have the potential to be applied as preservatives protecting food and other products against bacterial, fungal and oxidative spoilage.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Antifungal activity; Antimicrobial peptides; Antioxidative peptides; Chickpea peptides; Cytotoxicity; Leg1; Leg2

Application of mass spectrometry for the detection of glycation and oxidation products in milk proteins - Meltretter, Jasmin; Pischetsrieder, Monika (Annals of the New York Academy of Sciences, 2008)
Protein mass spectometry techniques, such as electrospray ionization mass spectrometry or matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS), are effective methods to screen for protein modifications derived from the Maillard reaction. The analysis of the intact proteins reveals the major modification, most commonly the Amadori product, whereas partial enzymatic hydrolysis prior to mass spectrometry additionally allows the detection of minor adducts. Therefore, a mass spectrometric method was developed for the analysis of whey protein modifications occurring during heat treatment. The two main whey proteins, α-lactalbumin and β-lactoglobulin, were incubated with lactose in a milk model and modifications were recorded using MALDI-TOF-MS. The analysis of the intact proteins revealed protein species with 0-4 lactulosyl residues. Partial enzymatic hydrolysis with endoproteinase AspN prior to mass spectrometric analysis enabled the detection of further modifications and their localization in the amino acid sequence. Detected modifications were lactulosyllysine, N ε-(carboxymethyl)lysine, lysine aldehyde, methionine sulfoxide, cyclization of N-terminal glutamic acid to a pyrrolidone, and oxidation of cysteine or tryptophan. Protein modifications in heated milk and commercially available dairy products can be analyzed after the separation of the milk proteins using one-dimensional SDS-PAGE. © 2008 New York Academy of Sciences.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.applic
Keywords: α-lactalbumin; β-lactoglobulin; Advanced glycation end products; Maillard reaction; Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; Milk products; Oxidation

Assessment of heat treatment of dairy products by MALDI-TOF-MS - Meltretter, Jasmin; Birlouez-Aragon, Inés; Becker, Cord-Michael; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2009)
The formation of the Amadori product from lactose (protein lactosylation) is a major parameter to evaluate the quality of processed milk. Here, MALDI-TOF-MS was used for the relative quantification of lactose-adducts in heated milk. Milk was heated at a temperature of 70, 80, and 1001C between 0 and 300min, diluted, and subjected directly to MALDI-TOF-MS. The lactosylation rate of a-lactalbumin increased with increasing reaction temperature and time. The results correlated well with established markers for heat treatment of milk (concentration of total soluble protein, soluble a-lactalbumin and b-lactoglobulin at pH 4.6, and fluorescence of advanced Maillard products and soluble tryptophan index; r = 0.969-0.997). The method was also applied to examine commercially available dairy products. In severely heated products, protein pre-purification by immobilized metal affinity chromatography improved spectra quality. Relative quantification of protein lactosylation by MALDI-TOF-MS proved to be a very fast and reliable method to monitor early Maillard reaction during milk processing. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.assess
Keywords: Amadori product; Maillard reaction; MALDI-TOF-MS; Milk; Relative quantification

Assessment of protein glycation markers in infant formulas - Birlouez-Aragon, Inés; Pischetsrieder, Monika; Leclère, J.; Morales, Francesco; Hasenkopf, Katrin; Kientsch-Engel, Rose; Ducauze, Christian J.; Rutledge, Doug (Food Chemistry, 2004)
The typical formulation of infant formulas (IF) may enhance damage of proteins during spray drying or sterilization. Lactose reacts with amino groups of proteins resulting in the formation of lactulosyllysine (LL). The latter is further degraded to give advanced glycation end-products (AGEs). Furthermore, oxidation reactions, which are catalyzed by iron can further promote AGE formation. In this study, six parameters for protein modification were measured for 41 commercially available IF samples: lysine blockage, tryptophan degradation and LL formation by HPLC, the AGEs Nε- carboxymethyllysine (CML) and oxalic acid monoalkylamide (OMA) by ELISA. The FAST index was used as a rapid method for monitoring AGEs. IF showed increased lysine loss (6-fold), LL formation (2-3-fold) and AGEs levels (3-5 times) (CML, OMA, and FAST index) compared to similarly treated cow's milk, indicating more severe protein modifications in the former. Further studies on the technological processes are required to minimize heat-induced damage of IF during manufacturing. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.assess
Keywords: Advanced glycation end-products; Carboxymethyllysine; Fluorescence; Infant formulas; Lactulosyllysine; Nutritional quality; Protein glycation

Associated links among mtDNA glycation, oxidative stress and colony sectorization in Metarhizium anisopliae - Li, Lin; Pischetsrieder, Monika; St. Leger, Raymond J.; Wang, Chengshu (Fungal Genetics and Biology, 2008)
Mycelial colonies of filamentous fungi often deteriorate when maintained on artificial media, and this can take the form of sterile sectors. We previously established that sectorization by the entomopathogenic fungus Metarhizium anisopliae correlates with intracellular accumulation of reactive oxygen species (ROS). In this study we demonstrate that: (1) H2O2 increases rates of sectorization; (2) a stable strain of M. anisopliae eliminates intracellular ROS more rapidly than an unstable strain; (3) mitochondrial DNA from sectors undergoes a non-enzymatic glycation of deoxyguanosine that is not shown by genomic DNA; (4) the membrane potential of mitochondria in sector cells is decreased in comparison to wild type cells indicating loss of function; (5) DNA glycation changes the properties of DNA and (6) treating wild type mycelia with H2O2 reproduced the glycation pattern shown in sectors. H2O2 also reproduced the morphological changes in mitochondria and lipid droplets that occur in sector cells. Fungal sectorization thus displays aging related developmental impairments resulting from oxidative stress, suggesting a new research direction for studies on fungal colony deterioration. Mitochondrial DNA has a very high AT bias. We speculate that reducing the consequences of glycation could provide an adaptive reason for this. © 2008 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.associ
Keywords: Lipid droplets; Metarhizium anisopliae; mtDNA glycation; Oxidative stress; Sectorization

A systematic approach to identify novel marker peptides for the heat treatment and storage of milk - Dalabasmaz, Sevim; Pischetsrieder, Monika (Lebensmittelchemie, 2021)

Binding of Maillard products to proteins: formation of pyrrole carbimines - Nissl, Jürgen; Pischetsrieder, Monika; Klein, Ellen; Severin, Theodor (Carbohydrate Research, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dchph.llmch.bindin

Bio-templated bioactive glass particles with hierarchical macro-nano porous structure and drug delivery capability - Zheng, Kai; Bortuzzo, Judith Agnes; Liu, Yufang; Li, Wei; Pischetsrieder, Monika; Roether, Judith; Lu, Miao; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2014)
Hierarchically porous bioactive glass particles (BGPs) were synthesized by a facile sol-gel process using pollen grains as the templates. The synthesized pollen-templated bioactive glass particles (PBGPs) exhibited dual macro-nano porous structure. The macro pores ( 1μm) were inherited from the template of pollen grains while the nano pores ( 9.5nm) were induced by the intrinsic mechanism of the sol-gel process. PBGPs possessed a high specific surface area (111.4m/g) and pore volume (0.35cm/g). Hydroxyapatite (HA) formation on PBGPs was detected within 3 days after immersion in simulated body fluid (SBF). Due to their larger specific surface area and pore volume, PBGPs could be loaded with more tetracycline hydrochloride (TCH) than non-templated BGPs and conventional melt-derived 45S5 BGPs. In addition, PBGPs exhibited a low initial burst release (within 10% of the loaded amount) within 18h and a sustained release with a two-stage release pattern for up to 6 days in phosphate buffered saline (PBS). The antibacterial assay confirmed that the TCH-loaded PBGPs could release TCH within 5 days, and the released TCH could reach the minimum inhibitory concentration (MIC) against Escherichia coli. MTT assay indicated that PBGPs showed non-cytotoxic effects toward human hepatocellular carcinoma (Hep G2) cells after co-culture for up to 72h in vitro. These results showed that the biocompatible hierarchically macro-nano porous PBGPs are potential for bone regeneration and local drug delivery applications.
Keywords: Bio-template; Bioactive glass; Drug delivery; Hierarchical pores

Characterization of ascorbylated proteins by immunochemical methods - Huber, Birgit; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 1998)
L-Ascorbic acid (AA) binds covalently to proteins in a Maillard-type reaction (protein ascorbylation). An immunochemical screening method was developed to determine the products formed during protein ascorbylation. Thus, sheep serum albumin (SSA) was incubated with L-dehydroascorbic acid (DHA) to get highly modified ascorbylated SSA (DHA-SSA), and a polyclonal anti-DHA -protein antiserum was prepared using DHA-SSA as antigen. Noncompetitive and competitive ELISAs were performed to characterize the reactive epitopes. It was found that (1) the antibody binds to ascorbylated lysine but not to arginine or histidine residues; (2) the formation of reactive products is highly dependent on the presence of oxygen; (3) proteins that were glycated by sugars, such as glucose or ribose, show significant binding to the anti-DHA-protein antibody, indicating that the reactive epitope can also be generated by carbohydrates other than AA; (4) CML-protein [CML = Aε-(carboxymethyl)lysine] and CML can inhibit the antibody binding completely. These results show that the anti-DHA-protein antiserum consists mainly of anti-CML antibodies. Using specific anti-CML and anti-oxalic acid monoamide (OMA) antibodies (Pischetsrieder, M.; Larisch, B.; Seidel, W. J. Agric. Food Chem. 1997, 45, 2070-2075), it was found that both antisera bind significantly to DHA-proteins. Therefore, it can be concluded that CML is an important product formed during the reation of AA and proteins and that it is the main immunological epitope of ascorbylated protein. However, other predominant modifications on ascorbylated proteins besides CML and OMA cannot be excluded.
UnivIS-Import:2015-03-05:Pub.1998.nat.dchph.llmch.charac
Keywords: Immunochemical method; L-Ascorbic acid; Maillard reaction; N; Protein ascorbylation

Chemical and physiological relevance of glucose degradation products in peritoneal dialysis - Mittelmaier, Stefan; Niwa, Toshimitsu; Pischetsrieder, Monika (Journal of Renal Nutrition, 2012)
Fibrosis and vascular sclerosis are main complications that limit the long-term application of peritoneal dialysis (PD). Low biocompatibility has been largely attributed to the presence of glucose degradation products (GDPs), which are formed during the heat sterilization of PD fluids. GDPs readily modify proteins in the peritoneum, leading to a decline of their biological function. After absorption, GDPs can also promote systemic protein glycation. Additionally, GDPs may augment DNA glycation, a process enhanced in uremia. Apart from their glycating activity, GDPs induce cytotoxicity and interfere with cell signaling in peritoneal mesothelial cells. Targeted screening revealed the nature of the6major GDPs with α-dicarbonyl structure as 3-deoxyglucosone, 3-deoxygalactosone, glucosone, glyoxal, methylglyoxal, and 3,4-dideoxyglucosone-3-ene. Valid quantification of these GDPs was achieved by ultrahigh-performance liquid chromatography/diode array detector/tandem mass spectrometry. Identification and quantification of single GDPs allow a structure-dependent risk evaluation. As a consequence, PD fluids and processes can be improved to reduce the GDP burden of patients undergoing PD. © 2012 National Kidney Foundation, Inc.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.chemic

Chemistry and Clinical Relevance of Carbohydrate Degradation in Drugs - Pischetsrieder, Monika; Gensberger-Reigl, Sabrina; Atzenbeck, Lisa; Weigel, Ingrid (Drug Discovery Today, 2016)
Carbohydrate degradation products are formed during heat sterilization in drugs containing (poly-)glucose as osmotic agents. Given this situation, peritoneal dialysis fluids (PDFs) and infusion fluids are of particular clinical relevance, because these drugs deliver process contaminants either over a longer period or directly into the circulation of patients who are critically ill. For the development of suitable mitigation strategies, it is important to understand the reaction mechanisms of carbohydrate degradation during sterilization and how the resulting products interact with physiological targets at the molecular level. Furthermore, reliable, comprehensive, and highly sensitive quantification methods are required for product control and toxicological evaluation.

Chemistry of glucose and biochemical pathways of biological interest - Pischetsrieder, Monika (Peritoneal Dialysis International, 2000)
Glucose degradation, yielding GDPs, can take place in vivo or during heat treatment of glucose solutions. AGEs are formed from the interaction of D-glucose with reactive amino-acid side chains of proteins. Both GDPs and AGEs have been shown to impair cellular function. GDPs have additional damaging effects because they strongly promote AGE formation (as compared to D-glucose).
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.chemis
Keywords: 3-Deoxyglucosone; Advanced glycation end-products; Amadori product; Glucose degradation products

Coffee and Maillard products activate NF-kappaB in macrophages via H2O2 production - Muscat, Sonja; Pelka, Joana; Hegele, Jörg; Weigle, Bernd; Münch, Gerald; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2007)
In this study, we investigated the immunomodulatory activity of coffee and Maillard reaction products on macrophages in vitro. Stimulation of macrophages with coffee, but not with raw coffee extract in PBS, led to a 13-fold increased nuclear NF-jB translocation. A Maillard reaction mixture (25 mM D-ribose/L-lysine, 30 min at 1208C) increased NF-jB translocation 18-fold (in PBS) or six-fold (in medium). MRPs also induced a two-fold increased NF-jB translocation in untransfected human embryonic kidney (HEK) cells as well as in HEK cells stably transfected with the receptor for advanced glycation endproducts (RAGE), indicating that the effect was not RAGE mediated. On the other hand, catalase totally abolished coffee- and MRP-induced NF-jB translocation. Consequently, up to 366 lM hydrogen peroxide was measured in the coffee preparation and Maillard mixtures used for cell stimulation. Stimulation of macrophages with MRPs did not lead to significantly increased IL-6 or NO release. Thus, it can be concluded that coffee and MRPs induce NF-jB translocation in macrophages via the generation of hydrogen peroxide.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.coffee
Keywords: Coffee; Hydrogen peroxide; Immunomodulation; Maillard reaction products; NF-kappaB

Comprehensive analysis of nonenzymatic post-translational beta-lactoglobulin modifications in processed milk by ultrahigh-performance liquid chromatography-tandem mass spectrometry - Meltretter, Jasmin; Wüst, Johannes; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2013)
Nonenzymatic post-translational protein modifications (nePTMs) result in changes of the protein structure that may severely influence physiological and technological protein functions. In the present study, ultrahigh-performance liquid chromatography-electrospray ionization tandem mass spectrometry (UHPLC-ESI-MS/MS) was applied for the systematic identification and site-specific analysis of nePTMs of β-lactoglobulin in processed milk. For this purpose, β-lactoglobulin, which had been heated with lactose under conditions to force nePTM formation (7 d/60 C), was screened for predicted modifications by using full scans and enhanced resolution scan experiments combined with enhanced product ion scans. Thus, the main glycation, glycoxidation, oxidation, and deamidation products of lysine, arginine, methionine, cysteine, tryptophan, and asparagine, as well as the N-terminus, were identified. Using these MS data, a very sensitive scheduled multiple reaction monitoring method suitable for the analysis of milk products was developed. Consequently, 14 different PTM structures on 25 binding sites of β-lactoglobulin were detected in different milk products. © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.compre
Keywords: β-lactoglobulin; glycation; mass spectrometry; oxidation; processed milk; protein modification

Comprehensive species- and processing-specific peptide profiling of pasteurized, extended shelf-life and ultra-high temperature milk from cow, goat, sheep, buffalo, and mare - Zenk, Nora; Laumer, Franziska; Dalabasmaz, Sevim; Stützer, Joachim; Mauser, Andreas; Pischetsrieder, Monika (Food Chemistry, 2024)
The present study aimed to identify endogenous milk peptides for species differentiation independent of heat exposure. Thus, comprehensive milk peptide profiles from five species and three types of heat treatments were analyzed by micro-flow liquid chromatography ion mobility quadrupole time-of-flight mass spectrometry (microLC-IM-QTOF) with subsequent database search leading to ≥ 3000 identified peptides. In the milks, 1154 peptides were unique for cow, 712 for sheep, 466 for goat, 197 for buffalo, and 69 for mare. Most peptides were detected in extended-shelf life (ESL) milk (2010), followed by ultra-high temperature (UHT) processed (1474) and pasteurized milk (1459 peptides), with 693 peptides present in all milk types. A blind test set of 64 samples confirmed eight species-specific, but heat-independent marker peptides in milk from cow, seven from goat, six from sheep, nine from buffalo, and three from mare. The generated peptide profiles can also be used to identify species- and heat-specific markers.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Endogenous peptide profiling; Mammalian milk; Marker peptide; microLC-QTOF-MS/MS; Milk heat treatment; Species specification

Concentrations of N epsilon-Carboxymethyllysine in Human Breast Milk, Infant Formulas, and Urine of Infants - Dittrich, Ralf; Hoffmann, Inge; Stahl, Peter; Müller, Andreas; Beckmann, Matthias; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2006)
Maillard products, such as Nε-carboxymethyllysine (CML), are readily formed during the manufacturing of infant formulas. Little has been known, however, about the presence of CML in human breast milk and about the uptake of CML by infants. In this study, CML was measured in the serum and breast milk of 32 healthy mothers by ELISA. CML concentrations in breast milk (137 ± 82.7 ng/mL) were significantly lower than in the serum (399 ± 67.8 ng/mL, p < 0.001) and on average 35-fold lower than in infant formulas (4754 ± 4299.5 ng/mL). CML was also measured in the urine of 21 infants, which were fed with breast milk or formulas. Although there was a tendency toward higher urinary CML excretion in infants fed with hypoallergenic formulas compared to breast-fed ones, the differences were not significant. Neonates that were delivered by vaginal birth had significantly higher concentrations of CML compared to those delivered by caesarean section (1306 ± 653 vs 601 ± 220 ng/mL, p = 0.012). It is conclued that CML passes from the serum into the breast milk, but the levels are by far lower than in infant formulas. In very young neonates (≤3 days), the mode of delivery has a greater influence on urinary CML excretion than the nutrition. © 2006 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2006.nat.dchph.llmch.concen
Keywords: Advanced glycation end-products; Breast milk; Infant formulas; Maillard products; N; Newborn; Urine

Cytotoxicity of Maillard reaction products determined with a peptide spot library - Muscat, Sonja; Pischetsrieder, Monika; Maczurek, Annette; Rothemund, Sven; Münch, Gerald (Molecular Nutrition & Food Research, 2009)
The reaction of reactive carbonyl compounds (RCCs) with lysine and arginine (Maillard reaction) is a common modification of proteins in thermally processed foods. In this study, the toxicity of Maillard reaction products (MRPs) formed from defined amino acids or dipeptides (bound to a cellulose membrane) with ribose, glycerinaldehyde or methylglyoxal was investigated. Murine RAW 264.7 macrophages were cultivated on the cellulose membrane and the effect of MRPs on cell viability was determined. The toxicity of MRPs was dependent on the RCC used and increased in the order of ribose < glycerinaldehyde < methylglyoxal. The dipeptides were more cytotoxic than the amino acids, with Lys-Lys MRPs being the most toxic of all tested MRPs. Cell numbers did not fall below the starting point, indicating that the MRPs rather inhibited proliferation than actually caused cell death. To develop an assay, in which whole membranes with multiple peptide spots could be tested simultaneously, we measured cell numbers on larger cellulose membranes using image analysis of the intracellularly formed formazan crystals. Although this method was technically feasable, it appears that uneven cell attachment on the membrane would require a way to detemine starting cell number by a non-destructive assay to yield more robust data. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.cytoto
Keywords: Cell viability; Glycation; Maillard products; Peptide library; Proliferation

Degradation and de novo formation of nine major glucose degradation products during storage of peritoneal dialysis fluids - Gensberger-Reigl, Sabrina; Weigel, Ingrid; Stützer, Joachim; Auditore, Andrea; Nikolaus, Tim; Pischetsrieder, Monika (Scientific Reports, 2022)
Reactive glucose degradation products (GDPs) are formed during heat sterilization of glucose-containing peritoneal dialysis fluids (PDFs) and may induce adverse clinical effects. Long periods of storage and/or transport of PDFs before use may lead to de novo formation or degradation of GDPs. Therefore, the present study quantified the GDP profiles of single- and double-chamber PDFs during storage. Glucosone, 3-deoxyglucosone (3-DG), 3-deoxygalactosone (3-DGal), 3,4-dideoxyglucosone-3-ene (3,4-DGE), glyoxal, methylglyoxal (MGO), acetaldehyde, formaldehyde, and 5-hydroxymethylfurfural (5-HMF) were quantified by two validated UHPLC-DAD methods after derivatization with o-phenylenediamine (dicarbonyls) or 2,4-dinitrophenylhydrazine (monocarbonyls). The PDFs were stored at 50 °C for 0, 1, 2, 4, 13, and 26 weeks. The total GDP concentration of single-chamber PDFs did not change considerably during storage (496.6 ± 16.0 µM, 0 weeks; 519.1 ± 13.1 µM, 26 weeks), but individual GDPs were affected differently. 3-DG (− 82.6 µM) and 3-DGal (− 71.3 µM) were degraded, whereas 5-HMF (+ 161.7 µM), glyoxal (+ 32.2 µM), and formaldehyde (+ 12.4 µM) accumulated between 0 and 26 weeks. Acetaldehyde, glucosone, MGO, and 3,4-DGE showed time-dependent formation and degradation. The GDP concentrations in double-chamber fluids were generally lower and differently affected by storage. In conclusion, the changes of GDP concentrations during storage should be considered for the evaluation of clinical effects of PDFs.
CRIS-Team Scopus Importer:2022-03-25

Design of a Prediction Model for the Differentiation of Pasteurized Milk from Heated ESL Milk by Peptide Profiling. - Dalabasmaz, Sevim; Pischetsrieder, Monika (Proteomics, 2019)
This study designed a prediction model to differentiate pasteurized milk from heated extended shelf life (ESL) milk based on milk peptides. For this purpose, quantitative peptide profiles of a training set of commercial samples including pasteurized (n=20), pasteurized-ESL (n=13) and heated-ESL (n=16) milk were recorded by MALDI-TOF-MS. Seven peptides were selected as putative markers, and cutoff levels and performance measures of each marker were defined by ROC analysis. The accuracy of these peptides in the training set ranged between 71 and 90%. A prediction model was established based on the combined cutoff levels and evaluated by an independent blind test set. The processing method of 19 out of 20 unknown milk samples was predicted correctly achieving 95% accuracy. Five peptides of the prediction model were identified as αS1-casein182-199 (m/z 2014.0), αS1-casein180-199 (m/z 2216.1), αS1-casein1-24 (m/z 2910.6), β-casein108-125 (m/z 2126.0), and β-casein106-125 (m/z 2391.2) indicating thermal release and the action of plasmin and cathepsins. Thus, the present study demonstrated that the milk peptide profile reflects even minor differences in production parameter

Detection of central nervous system tissue in meat and meat products with a newly developed immunoassay selective for Myelin proteolipid protein - Sandmeier, Barbara; Bäuerlein, Rainer; Villmann, Carmen; Düthorn, Tina; Gareis, Manfred; Becker, Cord-Michael; Pischetsrieder, Monika (Food Chemistry, 2007)
Bovine spongiform encephalopathy (BSE) is most likely transmitted by the consumption of central nervous system (CNS) tissue of infected animals. In this study, an immunochemical assay for CNS in meat and meat products was developed using an antibody against Myelin proteolipid protein (PLP), which is very specifically expressed in the CNS. Solvent extraction of CNS-contaminated meat yielded a highly enriched PLP fraction. Subsequent Western blot analysis specifically detected the PLP band at 29 kDa. The detection limit for unprocessed CNS in raw meat was less than 0.025% and the quantification limit was calculated to be 0.049%. The PLP epitope was relatively stable during storage at 5 °C or -21 °C and during heating at 75 °C and 95 °C. Amounts of 0.1% CNS could be reliably detected in cooked bologna type sausage, cooked liver sausage and fermented sausage. Thus, the new assay allows highly specific and sensitive determination of CNS contaminations in meat and meat products. © 2007 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.detect
Keywords: Bovine spongiform encephalopathy; Central nervous system; Myelin proteolipid protein; Solvent extraction; Western blot

Detection of DNA-bound advanced glycation end-products by immunoaffinity chromatography coupled to HPLC-diode array detection - Schneider, Marc; Georgescu, Adriana; Bidmon, Clemens; Tutsch, Martin; Fleischmann, Erwin; Popov, Doina; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2006)
Sugars and sugar degradation products are formed during food processing, but also endogenously in vivo. In vitro, nucleosides and DNA react readily with these carbonyl compounds during the formation of the two diastereomers of N 2-carboxyethyl-2′-deoxyguanosine (CEdGA,B), leading to a loss of DNA integrity. Only little is known about DNA glycation in vivo and about the influence of nutrition on CEdG formation. In this study, we developed a sensitive method to analyze DNA glycation by HPLC. For this purpose, immunoaffinity chromatography (IAC) using a polyclonal antibody against N 2-carboxyethylguanine (CEguanine) was coupled to HPLC-DAD. In some samples, peak identity was confirmed by LC-MS/MS. The recovery of CEguanine from the IAC columns was 52.5% = 3.6 (n = 4). Thus, it was possible for the first time to detect CEdGA,B, N2-carboxyethylguanosine (CEG A,B), and CEguanine in 11 human urine samples. However, due to imprecision of IAC, valid quantification of the adducts could not be achieved. Furthermore, CEdG was also detected in the DNA of cultured human smooth muscle cells (SMCs) and bovine aorta endothelium cells (BAECs). In BAECs, CEdG A,B were found by HPLC-DAD and LC-MS/MS after immunoaffinity purification, whereas in SMCs DNA-advanced glycation end-products were only detected with the more sensitive LC-MS/MS method. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.llmch.detect
Keywords: Advanced glycation end-products; DNA; Immunoaffinity chromatography; Maillard reaction

Detection of Maillard products of lactose in heated or processes milk by HPLC/DAD - Pischetsrieder, Monika; Groß, Ursula; Schoetter, Christiane (Zeitschrift für Lebensmittel-Untersuchung und -Forschung, 1999)
Two HPLC methods with diode array detection were used to separate Maillard products from milk components. The Maillard products 4-(β-D-galactopyranosyloxy)-2-hydroxy-2-methyl-2H-pyran-3(6H)-one (2), 1-[3-(/3-D-galactopyranosyloxy)-2-furanyl]-1-ethanohe (4), 4-(β-D-galactopyranosyloxy)-5-(hydroxymethyl)-2-methyl-3(2H)-furanone (5), isomaltol (7), maltol (9), 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (6), and 5-hydroxymethyl-2-furfuraldehyde (8) were determined using a water-methanol gradient. Furthermore, 4,5-dihydroxy-2-(β-D-galactopyranosyloxy)-5-methyl-2-cyclopenten-1-one (3) was separated from the milk components by applying the interaction reagent octylamine. Several heated or processed milk samples were analyzed, and formation of the Maillard products was determined and quantified. Thus it was found that 2 and 3 are early products of the Maillard reaction in milk, whereas after prolonged heating 4, 5, and particularly 9 and 6 become more important. Compounds 7 and 8 were not detected, even if the samples were heated under stringent conditions. © Springer-Verlag 1999.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.detect
Keywords: Diode array detection; High performance liquid chromatography; Maillard reaction; Milk

Determination of dideoxyosone precursors of AGEs in human lens proteins - Linetsky, Mikhail; Johar, S.R. Kaid; Meltretter, Jasmin; Padmanabha, Smitha; Parmar, Trilok; Vasavada, Abhay R.; Pischetsrieder, Monika; Nagaraj, Ram H. (Archives of Biochemistry and Biophysics, 2011)
Dideoxyosones (DDOs) are intermediates in the synthesis of advanced glycation endproducts (AGEs), such as pentosidine and glucosepane. Although the formation of pentosidine and glucosepane in the human lens has been firmly established, the formation of DDOs has not been demonstrated. The aim of this study was to develop a reliable method to detect DDOs in lens proteins. A specific DDO trapping agent, biotinyl-diaminobenzene (3,4-diamino-N-(3-[5-(2- oxohexahydro-1H-thieno[3,4-d]imidazol-4-yl)pentanoyl]aminopropyl)benzamide) (BDAB) was added during in vitro protein glycation or during protein extraction from human lenses. In vitro glycated human lens protein showed strong reaction in monomeric and polymeric crosslinked proteins by Western blot and ELISA. Glycation of BSA in the presence of BDAB resulted in covalent binding of BDAB to the protein and inhibited pentosidine formation. Mass spectrometric analysis of lysozyme glycated in the presence of BDAB showed the presence of quinoxalines at lysine residues at positions K1, K33, K96, and K116. The ELISA results indicated that cataractous lens proteins contain significantly higher levels of DDO than non-cataractous lenses (101.9 ± 67.8 vs. 31.7 ± 19.5 AU/mg protein, p < 0.0001). This study provides first direct evidence of DDO presence in human tissue proteins and establishes that AGE crosslink synthesis in the human lens occurs via DDO intermediates. © 2011 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.determ
Keywords: Advanced glycation endproducts; Cataract; Dideoxyosones; Glycation; Human lens proteins

Determination of Glycated Nucleobases in Human Urine by a New Monoclonal Antibody Specific for N²-Carboxyethyl-2'-deoxyguanosine - Schneider, Marc; Thoß, Gerlinde; Hübner-Parajsz, Christa; Kientsch-Engel, Rose; Stahl, Peter; Pischetsrieder, Monika (Chemical Research in Toxicology, 2004)
Sugars and sugar degradation products react in vivo readily with proteins (glycation) resulting in the formation of a heterogeneous group of reaction products, which are called advanced glycation end products (AGEs). AGEs notably change the structure and function of proteins so that extended protein-AGE formation is linked to complications such as nephropathy, atherosclerosis, and cataract. DNA can be glycated in vitro in a similar way as proteins, and the two diastereomers of N2-carboxyethyl-2′-deoxyguanosine (CEdG A,B) were identified as major DNA AGEs. It was postulated that DNA AGEs play an important role in aging, diabetes, and uremia. However, at the moment, sensitive methods to measure the extent and impact of DNA AGEs in vivo do not exist. In this study, we developed a monoclonal antibody, which recognized CEdGA,B with high affinity and specificity (MAb M-5.1.6). The I50 value for CEdGA,B was 2.1 ng/mL, whereas other modified nuclueobases and AGE proteins showed negligible cross-reactivity. Unmodified 2′-deoxyguanosine was only weakly recognized with an I 50 value > 600 000 ng/mL, which is the limit of solubility. MAb M-5.1.6 was then used to measure the urinary excretion of AGE-modified nucleobases in a competitive enzyme-linked immunosorbent assay. The recovery of CEdGA,B from human urine was between 87.4 and 99.7% with coefficients of variations between 8.0 and 22.2%. The detection limit was 0.06 ng/mL, and the determination limit was 0.15 ng/mL with a linear range between 0.3 and 100 ng/mL. CEdG equivalents were analyzed in urine samples from 121 healthy volunteers, and concentrations between 1.2 and 117 ng CEdG equiv/mg creatinine were detected.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.determ

Determination of the Maillard Product Oxalic acidmonolysinylamide (OMA) in Heated Milk Products by ELISA - Hasenkopf, Katrin; Übel, B.; Bordiehn, T.; Pischetsrieder, Monika (FOOD/NAHRUNG, 2001)
Oxalic acid monolysinylamide (OMA), a Maillard product which had initially been identified as a reaction product of L-ascorbic acid, was formed, dependent on the reaction conditions, also from other carbohydrate sources. At elevated temperatures and in the presence of oxygen, the reaction of lactose with proteins resulted in the formation of relatively high amounts of OMA. Using a polyclonal antibody, which bound with high specificity and affinity to OMA-modified proteins, a competitive enzyme linked immunosorbent assay (ELISA) was developed to measure OMA formation in heat-treated milk products. The assay performance was characterized for OMA-modified beta-lactoglobulin diluted in buffer or pasteurized milk. For the latter, the least detectable dose was determined as 1.4 ng/ml with a linear range for quantification between 2 ng/ml and 200 ng/ml. For some samples intra- and interassay variation were determined. The ELISA was used to measure OMA-formation in heated milk and commercially available infant formula.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.determ

Development and validation of an enzyme-linked immunosorbent assay (ELISA) for quantification of lysozyme in cheese - Schneider, Nadine; Weigel, Ingrid; Werkmeister, Knut; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2010)
A competitive enzyme-linked Immunosorbent assay (ELISA) was developed to quantify the amount of the preservative and potential allergen lysozyme in cheese using a commercially available monoclonal antibody against hen egg white lysozyme. The limit of detection for lysozyme in a cheese matrix amounted to 2.73 ng/mL, and the working range comprises 3.125-800 ng/mL. Intra- and interassay coefficients of variation were lower than 12%. Neither cross-reactivity with α-lactalbumin and human lysozyme nor unspecific interference with matrix components was observed. The recovery of lysozyme-spiked cheese ranged from 87.4 to 93.6% at four concentrations (50, 100, 200, and 400 mg/kg). The ELISA method was also compared to a high-performance liquid chromatography (HPLC) method, confirming the reliability and accuracy of the ELISA. A total of 21 commercially available cheese samples produced with and without lysozyme were analyzed with ELISA as well as HPLC. Both methods showed good agreement with a correlation index of R2 = 0.990. © 2009 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.develo
Keywords: Allergen; Cheese; ELISA; Lysozyme; Monoclonal antibody

Development and validation of an HPLC method to quantify 3,4-dideoxyglucosone-3-ene in peritoneal dialysis fluids - Frischmann, Matthias; Spitzer, Johanna; Fünfrocken, Michael; Mittelmaier, Stefan; Deckert, Melanie; Fichert, Thomas; Pischetsrieder, Monika (Biomedical Chromatography, 2009)
A method was developed and validated to quantify 3,4-dideoxyglucosone-3-ene in peritoneal dialysis fluids by high-performance liquid chromatography with UV detection after derivatization with o-phenylenediamine. The advantages of this method compared with direct HPLC analysis are (i) the possibility of quantifying 3,4-dideoxyglucosone-3-ene simultaneously together with other glucose degradation products, (ii) the compatibility of the method with MS detection for unequivocal identification of the analyte and (iii) a bathochromic shift of the UV absorbance maximum which leads to higher selectivity. The validated method was used to measure 3,4-dideoxyglucosone-3-ene concentrations additionally to the glucose degradation products 3-deoxyglucosone, methylglyoxal, glyoxal, 5-hydroxymethylfurfural, 2-furaldehyde, formaldehyde and acetaldehyde in 19 commercial products for peritoneal dialysis. Copyright © 2009 John Wiley & Sons, Ltd.
UnivIS-Import:2015-04-14:Pub.2009.nat.dchph.llmch.develo
Keywords: 3; 4-Dideoxyglucosone-3-ene (3; 4-DGE); Glucose degradation products (GDP); HPLC; Peritoneal dialysis fluid (PD fluid)

Development of a Dot Blot Assay for the Rapid Detection of Central Nervous System Tissue on Meat and Contact Surfaces - Bäuerlein, Rainer; Sandmeier, Barbara; Villmann, Carmen; Hammon, Antje; Gareis, Manfred; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2008)
As a potential transmitter of bovine spongiform encephalopathy (BSE), tissue from bovine central nervous system (CNS) is not accepted in meat and meat products. Western blot analysis of the CNS marker myelin proteolipid protein (PLP) detects CNS contamination selectively and sensitively. In this study, a rapid dot blot assay using an anti-PLP antibody was developed to screen CNS contamination of meat and contact surfaces. The detection limit was 0.01% bovine brain in minced bovine muscle. When applied to a swab test, down to 0.5 mg of CNS tissue on meat or other surfaces was detectable. Other offal tissues or peripheral nerves did not interfere with the assay. The test allows a differentiation between mammalian and avian CNS but not among mammalian species. The swab test was applied immediately after slaughtering at several areas of the bovine head. CNS was not detectable at any region which may enter the food chain. © 2008 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.develo
Keywords: Bovine spongiform encephalopathy; Central nervous system; Dot blot; Meat; Myelin proteolipid protein; PLP; Swab test

Development of a Metabolically Stable Neurotensin Receptor 2 (NTS2) Ligand - Held, Cornelia; Plomer, Manuel; Hübner, Harald; Meltretter, Jasmin; Pischetsrieder, Monika; Gmeiner, Peter (ChemMedChem, 2013)
Subtype-selective neurotensin receptor2 (NTS2) ligands can be used as molecular probes to investigate the physiological role of neurotensinergic systems and serve as lead compounds to initiate the development of drugs for the treatment of tonic pain. Starting from our recently described NTS2 ligand 1, structural variants of type 2 were synthesized to further improve binding affinity and selectivity to gain metabolic stability. The peptide-peptoid hybrid 2b showed excellent NTS2 binding affinity (K=2.8nM) and 22000-fold selectivity over NTS1, as well as metabolic stability over 32h in a serum degradation assay. Employing a MAPK-driven luciferase reporter gene assay and an IP accumulation assay, the neurotensin mimetic 2b displayed respective inhibitions of constitutive activity exceeding 4.3- and 3.9-fold that of the inverse agonist activity of the endogenous ligand neurotensin. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Distribution of protein oxidation products in the proteome of thermally processed milk - Meyer, Bianca; Baum, Florian; Vollmer, Gregor; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2012)
During thermal milk processing, severe oxidation can occur, which alters the technological and physiological properties of the milk proteins. Due to differences in composition and physicochemical properties, it can be expected that the particular milk proteins are differently affected by oxidative damage. Therefore, the protein-specific distribution of oxidation products in the heated milk proteome was investigated. Raw and heated milk samples were separated by one-dimensional gel electrophoresis. Protein oxidation was visualized by Western blot after derivatization of protein carbonyls with 2,4-dinitrophenylhydrazine. Thus, α-lactalbumin displayed enhanced oxidation compared to α-lactoglobulin, despite its lower concentration in milk. Highly selective oxidation was detected for a previously unassigned minor milk protein. The protein was identified by its peptide mass fingerprint as a variant of αS1-casein (αS1-casein*). Similar oxidation patterns were observed in several commercial milk products. © 2012 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.distri
Keywords: aS1-casein; milk proteins; milk proteome; processed milk; protein carbonyls; protein oxidation

DNA-Glycation leads to Depurination by the loss of N2-Carboxyethylguanine in vitro - Seidel, Wolfgang; Pischetsrieder, Monika (Cellular and Molecular Biology, 1998)
D-Glucose reacts with nucleosides, mainly guanosine, and DNA in a similar way as with proteins, and DNA-bound advanced glycation endproducts (AGE) are formed. Guanosine (Gua) was incubated with D-glucose or dihydroxyacetone (DHA) under variation of temperature and reaction time, and the formation of the glycation products N2-carboxyethylguanosine (CEG) and N2-carboxymethylguanosine (CMG) was monitored by HPLC/DAD. DHA proved to be a very potent glycating agent which specifically produces CEG. When deoxyguanosine (dGua) was glycated under the same conditions, formation of the glycation product N2-carboxyethyldeoxyguanosine (CEdG) resulted in a significant decrease in stability of the N-glycosidic bond. As a consequence more than 25% of CEdG was hydrolysed to give the corresponding guanine derivative CEguanine, whereas unmodified dGua was stable under these conditions. Glycated DNA was then incubated and depurination by the loss of CEguanine was monitored by HPLC. Significant release of CEguanine was observed, whereas free guanine was neither formed from glycated nor from control DNA in detectable amounts. These data suggest that CEdG which is formed during the glycation of DNA in vitro causes increased depurination of DNA and produces abasic sites.
UnivIS-Import:2015-03-05:Pub.1998.nat.dchph.llmch.dnagly

Effect of advanced glycation end products on endotoxin-induced TNF-alpha, IL-1beta and IL-8 in human peripheral blood mononuclear cells - Reznikov, Leonid; Waksman, Javier; Azam, Tania; Kim, Soo-Hyun; Bufler, Philip; Niwa, Toshimitsu; Werman, Ariel; Zhang, Xiaohong; Pischetsrieder, Monika; Shaldon, Stanley; Dinarello, Charles A. (Clinical Nephrology, 2004)
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.effect

Effect of roasting on phenolic, antioxidant and browning properties of carob powder - Sahin, Hilal; Topuz, Ayhan; Pischetsrieder, Monika; Feramuz, Özdemir (European Food Research and Technology, 2009)
Roasted carob powder was obtained using different time-temperature combinations and some quality characteristics such as total phenolic content (TPC), total antioxidant activity (TAA), browning index (BI) at 420 nm, UV absorbance (UV-A) at 294 nm, and pH has been investigated. Both the roasting temperature and time significantly (P < 0.01) affected the quality characteristics of the product. However, the roasting time was found to be a critical factor in determining the overall quality of the product. While the TPC, TAA, BI and UV-A values of the samples increased with the increasing roasting temperature and time, the pH of the samples decreased gradually. The quality characteristics of the carob powders changed markedly in between 20 and 60 min of roasting which indicates that the heat-induced reactions accelerate particularly in that period of roasting. The correlations between all these chemical properties of carob powder were found to be significant (P < 0.0001) during roasting. © Springer-Verlag 2009.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.effect
Keywords: Antioxidant activity; Browning index; Carob powder; Maillard reaction; Roasting; Total phenolic

Endogenous mitochondrial oxidative stress in MnSOD deficient mouse embryonic fibroblasts promotes mitochondrial DNA glycation - Weigel, Ingrid; Pischetsrieder, Monika; Breyer, Viola; Huang, Ting-Ting (Free Radical Biology and Medicine, 2012)
The accumulation of somatic mutations in mitochondrial DNA (mtDNA) induced by reactive oxygen species (ROS) is regarded as a major contributor to aging and age-related degenerative diseases. ROS have also been shown to facilitate the formation of certain advanced glycation end-products (AGEs) in proteins and DNA and N 2-carboxyethyl-2′-deoxyguanosine (CEdG) has been identified as a major DNA-bound AGE. Therefore, the influence of mitochondrial ROS on the glycation of mtDNA was investigated in primary embryonic fibroblasts derived from mutant mice (Sod2 -/+) deficient in the mitochondrial antioxidant enzyme manganese superoxide dismutase. In Sod2 -/+ fibroblasts vs wild-type fibroblasts, the CEdG content of mtDNA was increased from 1.90 ± 1.39 to 17.14 ± 6.60 pg/μg DNA (p<0.001). On the other hand, the CEdG content of nuclear DNA did not differ between Sod2 +/+ and Sod2 -/+ cells. Similarly, cytosolic proteins did not show any difference in advanced glycation end-products or protein carbonyl contents between Sod2 +/+ and Sod2 -/+. Taken together, the data suggest that mitochondrial oxidative stress specifically promotes glycation of mtDNA and does not affect nuclear DNA or cytosolic proteins. Because DNA glycation can change DNA integrity and gene functions, glycation of mtDNA may play an important role in the decline of mitochondrial functions. © 2012 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.endoge
Keywords: Advanced glycation end-products; N2-carboxyethyl-2′-deoxyguanosine; DNA glycation; Mitochondria; Mn superoxide dismutase; Mitochondrial DNA; Oxidative stress; Free radicals

Expression of advanced glycation end products and their cellular recptor RAGE in diabetic nephropathy and nondiabetic renal disease - Tanji, Nozomu; Markowitz, Glen; Fu, Caifeng; Kislinger, Thomas; Taguchi, Akihiko; Pischetsrieder, Monika; Stern, David M.; Schmidt, Ann Marie; D'Agati, Vivette (Journal of the American Society of Nephrology, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.expres

Facile preparation of multifunctional superparamagnetic PHBV microspheres containing SPIONs for biomedical applications - Li, Wei; Zaloga, Jan; Ding, Yaping; Liu, Yufang; Janko, Christina; Pischetsrieder, Monika; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2016)
The promising potential of magnetic polymer microspheres in various biomedical applications has been frequently reported. However, the surface hydrophilicity of superparamagnetic iron oxide nanoparticles (SPIONs) usually leads to poor or even failed encapsulation of SPIONs in hydrophobic polymer microspheres using the emulsion method. In this study, the stability of SPIONs in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) solution was significantly increased after surface modification with lauric acid. As a result, magnetic PHBV microspheres with high encapsulation efficiencies (71.0-87.4%) were prepared using emulsion-solvent extraction/evaporation method. Magnetic resonance imaging (MRI) showed significant contrast for the magnetic PHBV microspheres. The toxicity of these magnetic PHBV microspheres towards human T-lymphoma suspension cells and adherent colon carcinoma HT-29 cells was investigated using flow cytometry, and they were shown to be non-toxic in a broad concentration range. A model drug, tetracycline hydrochloride, was used to demonstrate the drug delivery capability and to investigate the drug release behavior of the magnetic PHBV microspheres. The drug was successfully loaded into the microspheres using lauric acid-coated SPIONs as drug carrier, and was released from the microspheres in a diffusion controlled manner. The developed magnetic PHBV microspheres are promising candidates for biomedical applications such as targeted drug delivery and MRI.

Fat/carbohydrate ratio but not energy density determines snack food intake and activates brain reward areas - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (Scientific Reports, 2015)
The snack food potato chips induces food intake in ad libitum fed rats, which is associated with modulation of the brain reward system and other circuits. Here, we show that food intake in satiated rats is triggered by an optimal fat/carbohydrate ratio. Like potato chips, an isocaloric fat/carbohydrate mixture influenced whole brain activity pattern of rats, affecting circuits related e.g. to reward/addiction, but the number of modulated areas and the extent of modulation was lower compared to the snack food itself.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.fatcar

Fate of the glucose degradation products 3-deoxyglucosone and glyoxal during peritoneal dialysis - Tauer, Andreas; Bender, Thorsten; Fleischmann, Erwin; Niwa, Toshimitsu; Jörres, Achim; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2005)
Conventional fluids for peritoneal dialysis (PD) contain reactive glucose degradation products (GDPs) as a result of glucose breakdown during heat-sterilization. GDPs in PD fluids (PDFs) have been associated with the progressive alteration of the peritoneal membrane during long-term PD by cytotoxic effects and formation of advanced glycation endproducts (AGEs). In this study, we investigated the possible fate of two characteristic GDPs, 3-deoxyglucosone (3-DG) and glyoxal, during PD. In vivo, 3-DG and glyoxal concentrations, which were analyzed by high-performance liquid chromatography (HPLC), decreased in PDFs by 78% and 88% during 4 h of dwell time. The PDFs were then incubated in vitro in the presence of the most important reaction partners of GDPs in the peritoneal cavity. Neither human peritoneal mesothelial cells, human peritoneal fibroblasts, soluble protein, an insoluble collagen surface, nor components of spent dialysate led to a significant reduction of 3-DG or glyoxal after 6 h. Only after long-term incubation, a noticeable decrease of 3-DG was observed (-37% after three weeks), more likely due to spontaneous degradation reaction than formation of advanced glycation endproducts. These results suggest that in the course of PD, 3-DG, and glyoxal are absorbed into the organism and thus might contribute to the systemic pool of reactive carbonyl compounds. © 2005 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2005.med.MKIPIII.MKIPLA.fateof
Keywords: 3-Deoxyglucosone; Advanced glycation endproducts; Continuous ambulatory peritoneal dialysis; Glucose degradation products; Glyoxal

FAU Forschungszentrum Neue Wirkstoffe (FAU NeW) nimmt Arbeit auf - interdisziplinäre Zusammenarbeit zur Entwicklung neuer Wirkstoffe - Pischetsrieder, Monika; Fischer, Dagmar (Deutsche Lebensmittel-Rundschau, 2023)
CRIS-Team Scopus Importer:2024-12-16

First in vitro and in vivo experiences with stay.safe balance, a pH-neutral solution in a dual-chamber bag - Lage, Cristina; Pischetsrieder, Monika; Aufricht, Christoph; Jörres, Achim; Schilling, Holger; Passlick-Deetjen, Jutta (Peritoneal Dialysis International, 2000)
In addition to low pH and high osmolarity, glucose degradation products (GDPs) are considered to play a major role in the bioincompatibility of peritoneal dialysis fluids (PDFs). The formation of GDPs can be reduced by separating the glucose component of the solution (kept at very low pH) from the lactate component of the solution (kept at alkaline pH) during sterilization and storage. This development has been achieved by the use of a dual-chambered bag. Immediately before infusion, the seam between the two chambers is opened, and the contents are mixed. The result is a fluid with a more physiologic pH in the range 6.8 – 7.4. Concentrations of 3-deoxyglucosone (3-DG), methylglyoxal (MG), acetaldehyde (AA), and formaldehyde (FA) in Stay·Safe Balance (Fresenius Medical Care, Bad Homburg, Germany) were remarkably reduced when compared to conventional PD solution [conventional PDF (1.5% glucose): 172 μmol/L, 6 μmol/L, 152 μmol/L, and 7 μmol/L respectively; Stay·Safe Balance (1.5% glucose): 42 μmolL, < 1 μmol/L, < 2 μmol/L, and < 3 μmol/L respectively; conventional PDF (4.25% glucose): 324 μmol/L, 10 μmol/L, 182 μmol/L, and 13 μmol/L respectively; Stay·Safe Balance (4.25% glucose): 60 μmol/L, < 1 μmol/L, < 2 μmol/L, and < 3 μmol/L respectively). Human peritoneal mesothelial cells (HPMCs) were exposed to a control solution, a conventional PDF [CAPD 2, 1.5% glucose (Fresenius Medical Care, Bad Homburg, Germany)], and Stay·Safe Balance, either in a co-incubation model (24-hour PDF exposure) or in a  re-incubation model (30-min PDF exposure), followed by 24-hour recovery in culture medium. Interleukin-1β (IL-1β)–stimulated (1 ng/mL) IL-6 secretion from HPMCs was assessed by ELISA. Exposure of HPMCs to conventional PDF resulted in a significant reduction in IL-6 release, which was fully restored following exposure to Stay·Safe Balance. In addition to the short-term investigations, long-term in vitro studies were also carried out. All fluids had near-neutral pH and were changed every second day. After 1, 3, 5, 7, 10, and 13 days of exposure, cell viability was assessed. Whereas exposure to conventional PDF resulted in a significant reduction in HPMC viability after just 3 – 5 days, no significant toxicity of filter-sterilized or dual-chambered fluid was observed for up to 13 days. An observational study with 9 patients suggested that the efficacy of Stay·Safe Balance is equivalent to that of conventional solution. However, even short-term treatment (8 ± 1 weeks) with this more biocompatible solution seems to improve mesothelial cell mass as indicated by a rise in cancer antigen 125 (CA125) from a baseline of 47 ± 37 U/min to 172 ± 90 U/min. Our data indicate that Stay·Safe Balance may help to better preserve peritoneal membrane cell function. An ongoing European multicenter study is expected to confirm these results.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.firsti
Keywords: Biocompatibility; glucose degradation products; advanced glycosylation end-products; pH-neutral peritoneal dialysis solution

Food-derived 1,2-dicarbonyl compounds and their role in diseases - Hellwig, Michael; Gensberger-Reigl, Sabrina; Henle, Thomas; Pischetsrieder, Monika (Seminars in Cancer Biology, 2018)
Reactive 1,2-dicarbonyl compounds (DCs) are generated from carbohydrates during food processing and storage and under physiological conditions. In the recent decades, much knowledge has been gained concerning the chemical formation pathways and the role of DCs in food and physiological systems. DCs are formed mainly by dehydration and redox reactions and have a strong impact on the palatability of food, because they participate in aroma and color formation. However, they are precursors of advanced glycation end products (AGEs), and cytotoxic effects of several DCs have been reported. The most abundant DCs in food are 3-deoxyglucosone, 3-deoxygalactosone, and glucosone, predominating over methylglyoxal, glyoxal, and 3,4-dideoxyglucosone-3-ene. The availability for absorption of individual DCs is influenced by the release from the food matrix during digestion and by their reactivity towards constituents of intestinal fluids. Some recent works suggest formation of DCs from dietary sugars after their absorption, and others indicate that certain food constituents may scavenge endogenously formed DCs. First works on the interplay between dietary DCs and diseases reveal an ambiguous role of the compounds. Cancer-promoting but also anticancer effects were ascribed to methylglyoxal. Further work is still needed to elucidate the reactions of DCs during intestinal digestion and pathophysiological effects of dietary DCs at doses taken up with food and in "real" food matrices in disease states such as diabetes, uremia, and cancer.

Food - Nutrition - Health. Biofunktionalität, Prävention, Technologische Eigenschaften: Peptide profiling of kefir to identify bioactive components - Ebner, Jennifer; Asci Arslan, Ayse; Fedorova, Maria; Kücükcetin, Ahmet; Pischetsrieder, Monika (Ernährungsumschau, 2015)
UnivIS-Import:2015-10-26:Pub.2015.nat.dchph.llmch.foodnu

Formation of Advanced Glycation End Products During CAPD - Tauer, Andreas; Zhang, Xiaohong; Schaub, Thomas; Zimmeck, Thomas; Niwa, Toshimitsu; Passlick-Deetjen, Jutta; Pischetsrieder, Monika (American Journal of Kidney Diseases, 2003)
Advanced glycation end products (AGEs) are formed during the nonenzymatic reaction of sugars with proteins. Conventional peritoneal dialysis fluids (PDFs) lead to the formation of AGEs in the peritoneal membrane that are associated with histopathologic changes and loss of ultrafiltration. PDFs may cause AGE formation because of a high glucose concentration or reactive glucose degradation products (GDPs), which are formed during heat sterilization of PDFs. This formation of GDPs is strongly pH dependent, which is exploited in newly developed double-chamber bag PDFs. Accordingly, 3-deoxyglucosone levels in double-chamber bag PDFs are reduced by approximately 80%, and levels of the GDPs acetaldehyde, formaldehyde, and methylglyoxal are less than the detection limit. Using an in vitro model that mimics regular changes in PDFs during continuous ambulatory peritoneal dialysis treatment, the contribution of high glucose versus GDP concentrations to AGE formation was investigated. The latter was determined by measuring protein bound N ε-(carboxymethyl)- lysine (CML) and imidazolone by enzyme-linked immunosorbent assay. In this model, more than 85% of imidazolone and more than 70% of CML were formed by GDPs, whereas only a minor part resulted from a high glucose concentration per se. New in vivo investigations suggest that GDPs from PDFs also can exert systemic effects after absorption into the blood circulation. Imidazolone levels in blood serum decrease significantly after switching from single- to double-chamber PDFs. In summary, the use of double-chamber PDFs may decrease not only local, but also systemic AGE formation. © 2003 by the National Kidney Foundation, Inc.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.format_7
Keywords: Advanced glycation end products (AGEs); N epsilon-(carboxymethyl)-lysine (CML); continuous ambulatory peritoneal dialysis (CAPD); 3-deoxyglucosone (3-DG); glucose degradation products (GDPs); imidazolone

Formation of aminoreductones from maltose - Schoetter, Christiane; Pischetsrieder, Monika; Lerche, Holger; Severin, Theodor (Tetrahedron Letters, 1994)
Aminoreductones of general structure 3 are obtained by degradation of maltose-derived Amadori compounds (1). 3-Hydroxy-5,6-dihydropyridones (4) are formed as minor compounds. © 1994.
UnivIS-Import:2015-03-05:Pub.1994.nat.dchph.llmch.format

Formation of a novel colored product during the Maillard reaction of D-glucose - Knerr, Thomas; Lerche, Holger; Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 2001)
Reactions between reducing sugars and proteins or amino acids (Maillard reaction) lead to the formation of yellow to brown products (melanoidins) that are important for food preparation and processing, such as baking, roasting, or malt production. Thus far, the structures of the melanoidins have not been elucidated, although some structural insights have been gained from model reactions. In this study, D-glucose was heated with an amine and two colored compounds were detected by HPLC/UV-vis. After purification, the main product was identified as [(4aS,6R,7S,8R,8aR)-4,-4a, 6,7,8,8a-hexahydro- 7,8-dihydroxy-6-hydroxymethyl- 1,4- dipropyl- 1H-pyrano [2,3 -b] pyrazine-2-yl] -1-hydroxy-3-buten-2-one (1a). For the minor compound (2a), some spectral data were obtained, but the structure was not fully characterized, 1a and 2a are the main colored compounds when the reaction is performed in alcoholic solution or on a cellulose surface. Thus, it was concluded that products with an analogous structure are important for the color formation of foodstuffs with low water activity.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.determ_2
Keywords: [(4aS; 6R; 7S; 8R; 8aR)-4; 4a; 6; 7; 8; 8a-hexahydro- 7; 8-dihydroxy-6-hydroxymethyl-1; 4-dipropyl-1H-pyrano[2; 3-b]pyrazine-2- yl]-1-hydroxy-3-buten-2-one; Color formation; D-glucose; Maillard reaction; Melanoidins

Formation of Guanosine Adducts from L-Ascorbic Acid under Oxidative Conditions - Larisch, Bernd; Pischetsrieder, Monika; Severin, Theodor (Bioorganic & Medicinal Chemistry Letters, 1997)
L-Ascorbic acid (AA) was incubated with guanosine under physiological conditions and the reaction was monitored by HPLC-DAD. Four reaction products were isolated and identified as two pairs of diastereomers of N2-(1-Carboxyethyl)-guanosine and N2-(1-Carboxy-3-hydroxypropyl)-guanosine respectively. They were formed from AA in the presence of oxygen as well as from its degradation products L-dehydroascorbic acid and L-xylosone.
UnivIS-Import:2015-03-05:Pub.1997.nat.dchph.llmch.format

Formation of Pyridinium Betaines by Reaction of Hexoses with Primary Amines - Koch, Jürgen; Pischetsrieder, Monika; Polborn, Kurt; Severin, Theodor (Carbohydrate Research, 1998)
The reaction of glucose or fructose with primary amines and the thermal degradation of Amadori products of glucose leads to the formation of 6-formyl-1-alkylpyridinium-3-olates (5), of which 6-formyl-1-propylpyridinium-3-olate was isolated from a reaction mixture. A reference substance can be prepared in a two-step procedure from 5-(hydroxymethyl)-2-furaldehyde. Comparatively high yields of these betaines in relation to other UV-absorbing products are obtained under typical food processing and physiological conditions. With primary amines, the betaines readily form a Schiff base that undergoes Strecker-type degradation when heated in aqueous solution. Copyright (C) 1998 Elsevier Science Ltd.
UnivIS-Import:2015-03-05:Pub.1998.nat.dchph.llmch.format_7
Keywords: 6-Formyl-1-alkylpyridinium-3-olate; D-fructose; D-glucose; Maillard reaction; Pyridinium betaine; Strecker degradation

Formation of tetrahydro-ß-carbolines and ß-carbolines during the reaction of L-tryptophan with D-glucose - Rönner, Birgit; Lerche, Holger; Freilinger, Christine; Bergmüller, Wolfgang; Severin, Theodor; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2000)
The reaction of L-tryptophan (Trp) with D-glucose under conditions that can occur during food processing and preparation was studied by high-performance liquid chromatography with diode array detection (HPLC/DAD). Besides the well-established glucose-tryptophan Amadori product (AP), (1R,3S)-1-(D-gluco-1,2,3,4,5-pentahydroxypentyl)-1,2,3,4-tetrahydro-beta-carboline-3-carboxylic acid (PHP-THbetaC) was identified as an important product of this reaction. For preparation, PHPTH betaC was obtained in high yields when Trp and D-glucose were reacted under strongly acidic conditions after heating in methanol. At elevated reaction temperatures (150 °C) 1-acetyl-beta-carboline (acetyl-betaC), was detected in significant concentrations. The mixtures were heated under variations of reaction time and temperature, and AP, PHP-THbetaC, and acetyl-betaC were quantified. In the presence of air oxygen or mild, food relevant oxidants, such as L-dehydroascorbic acid, PHP-THbetaC was readily oxidized to a product that was identified as the previously unknown 1-(D-gluco-1,2,3,4,5-pentahydroxypentyl)- beta-carboline (PHP-betaC). Formation of PHP-THbetaC and PHP-betaC in foodstuffs would deserve particular interest because multiple physiological activity of THbetaC and betaC derivatives has been shown previously.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.format
Keywords: Maillard reaction; tryptophan; tetrahydro-beta-carboline; beta-carboline

Functionally selective activation of the dopamine receptor D2 is mirrored by the protein expression profiles - Wenk, Deborah; Ignatchenko, Vladimir; Macklin, Andrew; Hübner, Harald; Gmeiner, Peter; Weikert, Dorothée; Pischetsrieder, Monika; Kislinger, Thomas (Scientific Reports, 2021)
The development of functionally selective or biased ligands is a promising approach towards drugs with less side effects. Biased ligands for G protein-coupled receptors can selectively induce G protein activation or β-arrestin recruitment. The consequences of this selective action on cellular functions, however, are not fully understood. Here, we investigated the impact of five biased and balanced dopamine D2 receptor agonists and antagonists on the global protein expression in HEK293T cells by untargeted nanoscale liquid chromatography–tandem mass spectrometry. The proteome analysis detected 5290 protein groups. Hierarchical clustering and principal component analysis based on the expression levels of 1462 differential proteins led to a separation of antagonists and balanced agonist from the control treatment, while the biased ligands demonstrated larger similarities to the control. Functional analysis of affected proteins revealed that the antagonists haloperidol and sulpiride regulated exocytosis and peroxisome function. The balanced agonist quinpirole, but not the functionally selective agonists induced a downregulation of proteins involved in synaptic signaling. The β-arrestin-preferring agonist BM138, however, regulated several proteins related to neuron function and the dopamine receptor-mediated signaling pathway itself. The G protein-selective partial agonist MS308 influenced rather broad functional terms such as DNA processing and mitochondrial translation.
CRIS-Team Scopus Importer:2021-03-05

Funktionelle Lebensmittel - Functional Food - Pischetsrieder, Monika (Naturwissenschaften im Unterricht - Chemie, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.funkti

GABAA receptor modulation by terpenoids from Sideritis extracts. - Kessler, Artur; Sahin-Nadeem, Hilal; Lummis, Sarah C. R.; Weigel, Ingrid; Pischetsrieder, Monika; Büttner, Andrea; Villmann, Carmen (Molecular Nutrition & Food Research, 2014)
Scope GABAA receptors are modulated by Sideritis extracts. The aim of this study was to identify single substances from Sideritis extracts responsible for GABAA receptor modulation. Methods and results Single volatile substances identified by GC have been tested in two expression systems, Xenopus oocytes and human embryonic kidney cells. Some of these substances, especially carvacrol, were highly potent on GABAA receptors composed of α1β2 and α1β2γ2 subunits. All effects measured were independent from the presence of the γ2 subunit. As Sideritis extracts contain a high amount of terpenes, 13 terpenes with similar structure elements were tested in the same way. Following a prescreening on α1β2 GABAA receptors, a high-throughput method was used for identification of the most effective terpenoid substances on GABA-affinity of α1β2γ2 receptors expressed in transfected cell lines. Isopulegol, pinocarveol, verbenol, and myrtenol were the most potent modifiers of GABAA receptor function. Conclusion Comparing the chemical structures, the action of terpenes on GABAA receptors is most probably due to the presence of hydroxyl groups and a bicyclic character of the substances tested. We propose an allosteric modulation independent from the γ2 subunit and similar to the action of alcohols and anesthetics.

GABAA receptor modulation by terpenoids from Sideritis extracts - Kessler, Artur; Sahin-Nadeem, Hilal; Lummis, Sarah; Weigel, Ingrid; Pischetsrieder, Monika; Büttner, Andrea; Villmann, Carmen (Molecular Nutrition & Food Research, 2014)
Scope: GABAA receptors are modulated by Sideritis extracts. The aim of this study was to identify single substances from Sideritis extracts responsible for GABAA receptor modulation. Methods and results: Single volatile substances identified by GC have been tested in two expression systems, Xenopus oocytes and human embryonic kidney cells. Some of these substances, especially carvacrol, were highly potent on GABAA receptors composed of α1β2 and α1β2γ2 subunits. All effects measured were independent from the presence of the γ2 subunit. As Sideritis extracts contain a high amount of terpenes, 13 terpenes with similar structure elements were tested in the same way. Following a prescreening on α1β2 GABAA receptors, a high-throughput method was used for identification of the most effective terpenoid substances on GABA-affinity of α1β2γ2 receptors expressed in transfected cell lines. Isopulegol, pinocarveol, verbenol, and myrtenol were the most potent modifiers of GABAA receptor function. Conclusion: Comparing the chemical structures, the action of terpenes on GABAA receptors is most probably due to the presence of hydroxyl groups and a bicyclic character of the substances tested. We propose an allosteric modulation independent from the γ2 subunit and similar to the action of alcohols and anesthetics. © 2013 The Authors.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.gabaar
Keywords: Patch clamp recordings; Terpene; Two-electrode voltage clamp recordings; Volatile odorants

GABAA receptor modulation by the volatile fractions of Sideritis species used as ‘Greek’ or ‘Turkish’ mountain tea. - Kessler, Artur; Villmann, Carmen; Sahin, Hilal; Pischetsrieder, Monika; et al. (Flavour and Fragrance Journal, 2012)
Sideritis spp. is a member of the Labiateae family, used in traditional folk medicine and as a calming tea preparation. Dichloromethane extracts of the aerial parts of four Sideritis species were prepared, and the volatile fractions were separated via solvent‐assisted flavour evaporation distillation. In vitro electrophysiological techniques were used to investigate the physiological effects of these aroma extracts on ionotropic γ‐aminobutyric acid receptors (GABAA) in comparison to extracts of Lavandula spp. (lavender) obtained by the same approach. The plant extracts of Sideritis spp. and Lavandula spp. increased the maximal current responses gated by the agonist GABA, both in whole cell patch clamp recordings as well as in two electrode voltage clamp assays. Thereby, the volatile fractions caused a dose‐dependent enhancement of GABAergic currents. Differences in activity between the various species were probably due to variations in odorant composition, either on a qualitative or quantitative basis. Thus, the plant material contains volatile organic compounds, which are able to modulate a GABA‐mediated response and thereby possibly contribute to a sedative effect in vivo. Copyright © 2012 John Wiley & Sons, Ltd.<br

GABAA receptor modulation by the volatile fractions of Sideritis species used as ‘Greek’ or ‘Turkish’ mountain tea. - Kessler, Artur; Villmann, Carmen; Sahin, Hilal; Pischetsrieder, Monika; Büttner, Andrea (Flavour and Fragrance Journal, 2012)
Sideritis spp. is a member of the Labiateae family, used in traditional folk medicine and as a calming tea preparation. Dichloromethane extracts of the aerial parts of four Sideritis species were prepared, and the volatile fractions were separated via solvent‐assisted flavour evaporation distillation. In vitro electrophysiological techniques were used to investigate the physiological effects of these aroma extracts on ionotropic γ‐aminobutyric acid receptors (GABAA) in comparison to extracts of Lavandula spp. (lavender) obtained by the same approach. The plant extracts of Sideritis spp. and Lavandula spp. increased the maximal current responses gated by the agonist GABA, both in whole cell patch clamp recordings as well as in two electrode voltage clamp assays. Thereby, the volatile fractions caused a dose‐dependent enhancement of GABAergic currents. Differences in activity between the various species were probably due to variations in odorant composition, either on a qualitative or quantitative basis. Thus, the plant material contains volatile organic compounds, which are able to modulate a GABA‐mediated response and thereby possibly contribute to a sedative effect in vivo. Copyright © 2012 John Wiley & Sons, Ltd.<br

GABAA receptor modulation by the volatile fractions of Sideritis species used as 'Greek' or 'Turkish' mountain tea - Kessler, Artur; Villmann, Carmen; Sahin-Nadeem, Hilal; Pischetsrieder, Monika; Büttner, Andrea (Flavour and Fragrance Journal, 2012)
Sideritis spp. is a member of the Labiateae family, used in traditional folk medicine and as a calming tea preparation. Dichloromethane extracts of the aerial parts of four Sideritis species were prepared, and the volatile fractions were separated via solvent-assisted flavour  evaporation distillation. In vitro electrophysiological techniques were used to investigate the physiological effects of these aroma extracts on ionotropic g-aminobutyric acid receptors (GABAA) in comparison to extracts of Lavandula spp. (lavender) obtained by the same approach. The plant extracts of Sideritis spp. and Lavandula spp. increased the maximal current responses gated by the agonist GABA, both in whole cell patch clamp recordings as well as in two electrode voltage clamp assays. Thereby, the volatile fractions caused a dose-dependent enhancement of GABAergic currents. Differences in activity between the various species were probably due to variations in odorant composition, either on a qualitative or quantitative basis. Thus, the plant material contains volatile organic compounds, which are able to modulate a GABA-mediated response and thereby possibly contribute to a sedative effect in vivo.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.gabaar
Keywords: neurotropic modulation; terpenes; GABAA receptor; ionotropic; electrophysiology

Generation of antimicrobial peptides Leg1 and Leg2 from chickpea storage protein, active against food spoilage bacteria and foodborne pathogens - Heymich, Marie-Louise; Friedlein, Ulrike; Trollmann, Marius; Schwaiger, Karin; Böckmann, Rainer; Pischetsrieder, Monika (Food Chemistry, 2021)
Contamination with bacteria leads to food waste and foodborne diseases with severe consequences for the environment and human health. Aiming to reduce food spoilage and infection, the present study developed novel highly active food-grade antimicrobial peptides affecting a wide range of bacteria. After extraction from chickpea, the storage protein legumin was hydrolyzed by the digestive protease chymotrypsin. Subsequent analysis by ultrahigh-performance micro-liquid chromatography–triple quadrupole time-of-flight tandem mass spectrometry determined the resulting peptide profiles. Virtual screening identified 21 potential antimicrobial peptides in the hydrolysates. Among those, the peptides Leg1 (RIKTVTSFDLPALRFLKL) and Leg2 (RIKTVTSFDLPALRWLKL) exhibited antimicrobial activity against 16 different bacteria, including pathogens, spoilage-causing bacteria and two antibiotic-resistant strains. Leg1/Leg2 showed minimum inhibitory concentrations (MIC) down to 15.6 µmol/L and were thus 10–1,000-fold more active compared to conventional food preservatives. Moreover, Leg1 and Leg2 showed bactericidal activity in contrast to the bacteriostatic activity of conventional preservatives.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Antimicrobial peptides; Chickpea proteins; Chymotryptic hydrolysis; Cicer arietinum L.; Preservative; Virtual screening

Genomic damage and circulating AGE levels in patients undergoing daily versus standard haemodialysis - Fragedaki, Evangelia; Nebel, Michael; Schupp, Nicole; Sebekova, Katarina; Völkel, Wolfgang; Klassen, Andre; Pischetsrieder, Monika; Frischmann, Matthias; Niwa, Toshimitsu; Vienken, Jörg; Heidland, August; Stopper, Helga (Nephrology Dialysis Transplantation, 2005)
Background. Patients with end-stage renal failure, whether on conservative or haemodialysis therapy, have a high incidence of DNA damage. It is not known if improved control of the uraemic state by daily haemodialysis (DHD) reduces DNA lesions. Methods. DNA damage in peripheral blood lymphocytes (PBLs) was evaluated in a cross-sectional study of 13 patients on DHD (2-3 h, 6 times/week), 12 patients on standard haemodialysis (SHD) therapy (4-5 h, 3 times/week) and 12 healthy age-matched volunteer controls. The biomarker of DNA damage used was micronucleus frequency. The assessed plasma parameters of microinflammation and oxidative stress were C-reactive protein (CRP), interleukin-6 (IL-6), neopterin, advanced oxidation protein products (AOPP), and homocysteine. We also measured plasma concentrations of the circulating advanced glycation end products (AGEs) MGI (methylglyoxal-derived imidazolinone), CML (carboxymethyllysine), imidazolone A (3-deoxyglucosone-derived imidazolinone) and AGE-associated fluorescence. Results. Compared to SHD, DHD was associated with significantly lower DNA damage, approaching the normal range. Micronuclei (MN) frequency averaged 29.1 MN±5.9/1000 binucleated (BN) cells in the SHD group, which is significantly elevated (P<0.01), 14.8 MN±4.0/ 1000 BN cells in the DHD group, and 13.2 MN±3.04/1000 BN cells in the controls. CRP and AOPP were in the normal range (and similar between the dialysis groups). In contrast, IL-6 and neopterin were significantly elevated, with lower values associated with DHD as compared with SHD. The increased levels of AGEs tended to be lower in the DHD group, reaching significance for CML and imidazolone A. Conclusions. Overall, it was found that genomic damage in PBLs is lower in patients on DHD than in those on SHD. Lower plasma concentrations of uraemic toxins, including circulating AGEs, may account for the differences. To confirm these data, prospective clinical trials need to be performed. © The Author [2005]. Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.genomi
Keywords: Advanced glycation endproducts; Daily haemodialysis; Micronuclei frequency; Oxidative stress

Global Food-Related Challenges: What Chemistry Has Achieved and What Remains to Be Done - Pischetsrieder, Monika (Angewandte Chemie International Edition, 2018)

Glucose degradation products in peritoneal dialysis - Pischetsrieder, Monika; Gensberger, Sabrina (Uremic toxins by mass spectrometry, 2012)
UnivIS-Import:2015-04-20:Pub.2012.nat.dchph.llmch.glucos
Keywords: α-dicarbonyl-GDPs in PD fluids; (U)HPLC/DAD/MS/MS analysis; Glucose degradation products in PD; PD; osmotic solution into peritoneal cavity

Glycation products in infant formulas: chemical, analytical and physiological properties - Pischetsrieder, Monika; Henle, Thomas (Amino Acids, 2012)
Infant formulas are milk-based products, which are adapted to the composition of human milk. To ensure microbiological safety and long shelf life, infant formulas usually undergo rigid heat treatment. As a consequence of the special composition and the heat regimen, infant formulas are more prone to thermally induced degradation reactions than regular milk products. Degradation reactions observed during milk processing comprise lactosylation yielding the Amadori product lactulosyllysine, the formation of advanced glycation end products (AGEs), and protein-free sugar degradation products, as well as protein or lipid oxidation. Several methods have been developed to estimate the heat impact applied during the manufacturing of infant formulas, including indirect methods such as fluorescence analysis as well as the analysis of defined reaction products. Most studies confirm a higher degree of damage in infant formulas compared to regular milk products. Differences between various types of infant formulas, such as liquid, powdered or hypoallergenic formulas depend on the analyzed markers and brands. A considerable portion of protein degradation products in infant formulas can be avoided when process parameters and the quality of the ingredients are carefully controlled. The nutritional consequences of thermal degradation products in infant formulas are largely unknown.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.glycat
Keywords: Advanced glycation end products (AGE); Infant formula; Maillard reaction; Milk

How to Reduce 3-deoxyglucosone and Acetaldehyde in Peritoneal Dialysis Fluids - Zimmeck, Thomas; Tauer, Andreas; Fünfrocken, Michael; Pischetsrieder, Monika (Peritoneal Dialysis International, 2002)
◆ Objective: 3-Deoxyglucosone (3-DG) and acetaldehyde were found to be the major reactive carbonyl compounds in conventional heat-sterilized peritoneal dialysis fluids (PDFs). The aim of this study was to identify factors in the production of PDFs promoting or inhibiting the formation of acetaldehyde and 3-DG. ◆ Design: Single-chamber bag PDFs with different buffer systems and pH values were analyzed for acetaldehyde. 3-Deoxyglucosone was determined in double-chamber bag PDFs with different pH values, in commercially available samples, and in double-chamber products stored under defined conditions. ◆ Results: Acetaldehyde was found in the presence of lactate and malate, whereas in 2-hydroxybutanoate-buffered solution propionaldehyde was detected instead. Between pH 5.0 and 6.0 the acetaldehyde content in lactate-buffered solutions increased strongly.The concentration of 3-DG in the chamber containing glucose in double-chamber bags increased between pH 3.0 and 5.0 by a factor of 6.3-Deoxyglucosone concentrations in commercially available products vary greatly, reflecting the different pH values of these products. A time- and temperature-dependent reaction leads to a reduction in 3-DG and an increase in 5-hydroxymethyl-furan-2-carbaldehyde during storage. ◆ Conclusion: Acetaldehyde is produced by a reaction that requires both lactate and glucose. Thus, its formation can be prevented by a separation of the reaction partners, glucose and lactate, in a double-chamber bag. In double-chamber bags, pH greatly influences the formation of 3-13G. Minimal formation is observed in the region of pH 3.0. This finding should be taken into account for the development of new double-chamber bag PDFs.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.howtor
Keywords: 3-deoxyglucosone; Acetaldehyde; Chemical analysis; Glucose degradation products; Lactate buffer; Peritoneal dialysis fluids

Identification and quantification of kukoamine A and kukoamine B as novel μ-opioid receptor agonists in potato and other solanaceous plants - Saller, Julia; List, Carina; Hübner, Harald; Gmeiner, Peter; Clark, Timothy; Pischetsrieder, Monika (Food Chemistry, 2023)
Activation of the µ-opioid receptor (µOR) by food components could lead to reward effects or to the modulation of motor functions in the gastrointestinal tract. In an unbiased search for novel µOR agonists in food, a three-step virtual-screening process selected 22 promising candidates with potential to interact with the µOR. Radioligand binding studies showed that ten of these substances indeed bind to the receptor. Functional assays identified kukoamine A as a full agonist (EC50 = 5.6 µM) and kukoamine B as a partial agonist (EC50 = 8.7 µM) to µOR. After extraction, both kukoamines were analyzed by LC–MS/MS in potato, tomato, pepper, and eggplant. Depending on the potato variety, up to 16 µg of kukoamine A and 157 µg of kukoamine B per gram dry weight could be determined in the whole tuber, mainly concentrated in the potato peel. Cooking did not influence the kukoamine contents.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Bioactive food compound; Kukoamine; Potato; Solanaceous plant; Virtual screening; µ-Opioid receptor

Identification and quantification of six major alpha-dicarbonyl process contaminants in high-fructose corn syrup - Gensberger, Sabrina; Mittelmaier, Stefan; Glomb, Marcus; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2012)
High-fructose corn syrup (HFCS) is a widely used liquid sweetener produced from corn starch by hydrolysis and partial isomerization of glucose to fructose. During these processing steps, sugars can be considerably degraded, leading, for example, to the formation of reactive aα- dicarbonyl compounds (aα-DCs). The present study performed targeted screening to identify the major aα-DCs in HFCS. For this purpose, aα-DCs were selectively converted with o-phenylendiamine to the corresponding quinoxaline derivatives, which were analyzed by liquid chromatography with hyphenated diode array-tandem mass spectrometry (LC-DAD-MS/MS) detection. 3-Deoxy-D-erythro-hexos-2- ulose (3-deoxyglucosone), D-lyxo-hexos-2-ulose (glucosone), 3-deoxy-D-threo-hexos-2- ulose (3-deoxygalactosone), 1-deoxy-D-erythro-hexos-2,3-diulose (1- deoxyglucosone), 3,4-dideoxyglucosone-3-ene, methylglyoxal, and glyoxal were identified by enhanced mass spectra as well as MS/MS product ion spectra using the synthesized standards as reference. Addition of diethylene triamine pentaacetic acid and adjustment of the derivatization conditions ensured complete derivatization without de novo formation for all identified aα-DCs in HFCS matrix except for glyoxal. Subsequently, a ultra-high performance LC-DAD-MS/MS method was established to quantify 3- deoxyglucosone, glucosone, 3-deoxygalactosone, 1- deoxyglucosone, 3,4-dideoxyglucosone-3-ene, and methylglyoxal in HFCS. Depending on the aα-DC compound and concentration, the recovery ranged between 89.2% and 105.8% with a relative standard deviation between 1.9% and 6.5%. Subsequently, the aα-DC profiles of 14 commercial HFCS samples were recorded. 3-Deoxyglucosone was identified as the major aα-DC with concentrations up to 730 μg/mL HFCS. The total aα-DC content ranged from 293 μg/mL to 1,130 μg/mL HFCS. Significantly different aα-DC levels were not detected between different HFCS specifications, but between samples of various manufacturers indicating that the aα-DC load is influenced by the production procedures. © 2012 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.identi
Keywords: α-Dicarbonyl compound (α-DC); High-fructose corn syrup (HFCS); o-Phenylenediamine (OPD); Quinoxaline derivatives; Sugar degradation products; Ultra high-performance liquid chromatography (UHPLC)

Identification and quantification of the glucose degradation product glucosone in peritoneal dialysis fluids by HPLC/DAD/MSMS - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Fichert, Thomas; Pischetsrieder, Monika (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2010)
Glucose degradation products (GDPs) formed during heat sterilization of peritoneal dialysis (PD) fluids exert cytotoxic effects and promote the formation of advanced glycation end-products in the peritoneal cavity. As a result, long-term application of continuous ambulatory peritoneal dialysis is limited. The composition and concentration of GDPs in PD fluids must be known to evaluate their biological effects. The present study describes a targeted screening for novel GDPs in PD fluids. For this purpose, dicarbonyl compounds were converted with o-phenylenediamine to give the respective quinoxaline derivatives, which were selectively monitored by HPLC/diode array detector. Glucosone was thereby identified as a novel major GDP in PD fluids. Product identity was confirmed by LC/MSMS analysis using independently synthesized glucosone as a reference compound. Furthermore, a method was developed to quantify glucosone in PD fluids by HPLC/UV after derivatization with o-phenylenediamine. The method's limit of detection was 0.6 μM and the limit of quantitation 1.1 μM. A linear calibration curve was obtained between 1.1 and 113.9 μM (R2 = 0.9999). Analyzed at three different concentration levels, recovery varied between 95.6% and 102.0%. The coefficient of variation ranged between 0.4% and 4.7%. The method was then applied to the measurement of glucosone in typical PD fluids. Glucosone levels in double chamber bag PD fluids varied between not detectable and 6.7 μM. In single chamber bag fluids, glucosone levels ranged between 28.7 and 40.7 μM. © 2010 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.identi_4
Keywords: [alpha]-Dicarbonyl compounds; Glucose degradation products (GDPs); Glucosone; HPLC; Peritoneal dialysis fluid; Quinoxaline derivatives

Identification and Relative Quantification of Bioactive Peptides Sequentially Released during Simulated Gastrointestinal Digestion of Commercial Kefir. - Liu, Yufang; Pischetsrieder, Monika (Journal of agricultural and food chemistry, 2017)
Health-promoting effects of kefir may be partially caused by bioactive peptides. To evaluate their formation or degradation during gastrointestinal digestion, we monitored changes of the peptide profile in a model of (1) oral, (2) gastric, and (3) small intestinal digestion of kefir. Matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy analyses revealed clearly different profiles between digests 2/3 and kefir/digest 1. Subsequent ultraperformance liquid chromatography-electrospray ionization-tandem mass spectrometry identified 92 peptides in total (25, 25, 43, and 30, partly overlapping in kefir and digests 1, 2, and 3, respectively), including 16 peptides with ascribed bioactivity. Relative quantification in scheduled multiple reaction monitoring mode showed that many bioactive peptides were released by simulated digestion. Most prominently, the concentration of angiotensin-converting enzyme inhibitor β-casein203-209 increased approximately 10 000-fold after combined oral, gastric, and intestinal digestion. Thus, physiological digestive processes may promote bioactive peptide formation from proteins and oligopeptides in kefir. Furthermore, bioactive peptides present in certain compartments of the gastrointestinal tract may exert local physiological effects.
Keywords: Kefir; peptide profile; bioactive peptides; gastrointestinal digestion

Identification and Site Specific Relative Quantification of beta-Lactoglobulin Modifications in Heated Milk and Dairy Products - Meltretter, Jasmin; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2008)
During milk processing, proteins can be severely modified by oxidation, condensation, and Maillard reaction, leading to changes in their nutritional and technological properties. In this study, major modifications of β-lactoglobulin, formed during the heating and processing of milk, were screened by mass spectrometry. For this purpose, β-lactoglobulin was isolated from the milk samples by gel electrophoresis and analyzed by matrix-assisted laser desorption/ionization mass spectrometry after in-gel digestion with endoproteinase AspN. In heated milk, lactulosyllysine was detected at lysine 47 and 138 or 141 as well as methionine sulfoxide at methionine 7, 24, and 145. All these modifications increased gradually when raw milk was heated for 20, 40, and 60 min at 120°C. The major modifications were also relatively quantified in dairy products, such as raw, high-temperature, ultra-high-temperature, sterilized, and condensed milk as well as infant formulas. The highest contents of lactulosyllysine at Lys47 were detected in powdered infant formulas, whereas lactulosyllysine at Lys138/141 was predominant in condensed milk samples. Methionine sulfoxide at Met7 and Met24 showed a trend toward higher modification rates in more severely processed products. © 2008 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2008.nat.dchph.llmch.identi
Keywords: β-Lactoglobulin; Glycation; Maillard reaction; Matrix-assisted laser desorption/ionization mass spectrometry; Milk; Oxidation

Identification of [6-Hydroxy-2-(hydroxymethyl)-5-oxo-5,6-dihydro-2 H-pyran-3-yl]-cysteine (HHPC) as a Cysteine-specific Modification Formed from 3,4-Dideoxyglucosone-3-ene (3,4-DGE). - Gensberger-Reigl, Sabrina; Atzenbeck, Lisa; Göttler, Alexander; Pischetsrieder, Monika (Chemical Research in Toxicology, 2019)
Glucose degradation products (GDPs) are formed from glucose and other reducing sugars during heat treatment, for example, in heat-sterilized peritoneal dialysis fluids or foods. Because of their reactive mono- and dicarbonyl structure, they react readily with proteins, resulting in the formation of advanced glycation end products (AGEs), loss of protein functionality, and cytotoxicity. Among the GDPs, 3,4-dideoxyglucosone-3-ene (3,4-DGE) exerts the strongest effects despite its relatively low concentration levels. The goal of the present study was therefore to identify the structure of specific protein modifications deriving from 3,4-DGE. A nonapeptide containing the reactive amino acids lysine, arginine, and cysteine was incubated with 3,4-DGE and the dominant GDPs 3-deoxyglucosone (3-DG) and 3-deoxygalactosone (3-DGal) in concentrations as present in peritoneal dialysis fluids (235 μM 3-DG, 100 μM 3-Gal, and 11 μM 3,4-DGE). Glycation rate and product formation were determined by ultra-HPLC-MS/MS (UHPLC-MS/MS). 3,4-DGE showed the strongest glycation activity. After 2 h of incubation, 3,4-DGE had modified 57% of the nonapeptide, whereas 3-DG had modified only 2% and 3-DGal had modified 29% of the peptide. A stable 3,4-DGE-derived cysteine modification was isolated. Its structure was determined by comprehensive NMR and MS experiments to be [6-hydroxy-2-(hydroxymethyl)-5-oxo-5,6-dihydro-2 H-pyran-3-yl]-cysteine (HHPC), which represents a novel cysteine-AGE derived from 3,4-DGE. The results indicate that 3,4-DGE might contribute to a severe loss of protein functionality by forming cysteine-specific AGEs, such as HHPC.

Identification of aminoreductones as active components in Maillard reaction mixtures inducing nuclear NF-kappaB translocation in macrophages - Wühr, Andrea; Deckert, Melanie; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2010)
Coffee, a highly processed food, and Maillard mixtures are able to activate nuclear factor kB translocation in macrophages via generation of hydrogen peroxide. In this study, a substructure library was prepared and used to identify Maillard products that are responsible for this effect. Three different Maillard reaction products with aminoreductone substructure (C6-aminoreductone, C4-aminoreductone, and aminohexose reductone) strongly induce nuclear factor kB translocation in macrophages. The effect was almost completely blocked by co-incubation with catalase, indicating that cellular activation was mediated by the ability of the test compounds to generate hydrogen peroxide. The cellular effect of a Maillard mixture, which was produced under conditions favoring aminoreductone formation, could be almost completely related to the presence of C6-aminoreductone.
UnivIS-Import:2015-04-14:Pub.2010.nat.dchph.llmch.identi
Keywords: Aminoreductone; Hydrogen peroxide; Macrophages; Maillard reaction products; Nuclear factor kappa B

Identification of colupulone and lupulone as the main contributors to the antibacterial activity of hop extracts using activity-guided fractionation and metabolome analysis - Li, Yan; Dalabasmaz, Sevim; Gensberger-Reigl, Sabrina; Heymich, Marie-Louise; Krofta, Karel; Pischetsrieder, Monika (Food Research International, 2023)
Hop is widely used in beer brewing and as a medicinal product. The present study comprehensively analyzed the main molecular determinants of the antibacterial activity of hop extracts. Minimum inhibitory concentrations (MIC) against Bacillus subtilis between 31.25 and 250 µg/mL were found in the ethanolic extracts of five hop varieties for beer brewing, but not in the tea hop sample. Activity-guided fractionation revealed the highest antibacterial activity for lupulone and adlupulone (MIC 0.98 µg/mL). Metabolome profiling and subsequent multistep statistical analysis detected 33 metabolites out of 1826 features to be associated with the antibacterial activity including humulone, adhumulone, colupulone, lupulone, and adlupulone. Xanthohumol, the three humulone- and three lupulone congeners were quantified in the hop extracts by a validated ultrahigh-performance liquid chromatography–mass spectrometry method. Considering concentrations and MICs, colupulone and lupulone were identified as major contributors to the antibacterial activity of hop extract with the highest antibacterial activity values (concentration/MIC) of 1.59 and 2.56.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Antibacterial activity; Hop; Humulone; Humulus lupulus; Lupulone; Metabolome; Quantification

Identification of DNA adducts of methylglyoxal - Frischmann, Matthias; Bidmon, Clemens; Angerer, Jürgen; Pischetsrieder, Monika (Chemical Research in Toxicology, 2005)
Methylglyoxal (MG) is a sugar degradation product, which is endogenously formed by fragmentation of triose phosphates during glycolysis, ketone body metabolism of acetone, and catabolism of threonine. Food, beverages, and medical products are important exogenous sources with concentrations of up to 100 μM MG. MG is a reactive dicarbonyl compound, which easily modifies amino groups of proteins (glycation reaction) and thereby induces proinflammatory responses. Moreover, increased mutation frequencies in mammalian cells after treatment with MG have been reported, which are caused by stable modifications of DNA bases. Thus far, two types of adducts have been identified, which are formed during the reaction of free guanine or 2′-deoxyguanosine with high MG concentrations. In this study, we investigated the prolonged exposure of DNA to physiological MG concentrations. DNA was incubated with MG, enzymatically hydrolyzed to release the free nucleosides, and then analyzed by LC-MS/MS. We detected four products, which were derived from the reaction of 2′-deoxyguanosine and 2′-deoxyadenosine with 1 and 2 equiv of MG each. The adducts with 1 equiv of MG were identified as N2-(1- carboxyethyl)-2′-deoxyguanosine (CEdG) and N6-(1-carboxyethyl)- 2′-deoxyadenosine. LC-MS/MS was optimized for these compounds, and incubation of DNA was repeated using physiological concentrations of 10 μM MG. Thereby, CEdG proved to be the most sensitive and suitable marker for the reaction of DNA with MG (negative MRM mode, three mass transitions [M - 1] - 338→178, 338→106, and 338→149). © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.identi

Identification of eugenol as the major determinant of GABA(A)-receptor activation by aqueous Syzygium aromaticum L. (clove buds) extract - Sahin, Sümeyye; Eulenburg, Volker; Heinlein, Anja; Villmann, Carmen; Pischetsrieder, Monika (Journal of Functional Foods, 2017)
The spice Syzygium aromaticum L. (clove buds) exerts topical anesthetic and analgesic effects. Since GABA(A) receptors are an emerging drug target for pain treatment, the effects of aqueous clove extracts on the human alpha 1 beta 2-GABA(A) receptor were tested by two-electrode voltage clamp technique applying a three-step test system. The extract significantly and specifically potentiated the GABA-induced currents by an allosteric mechanism in concentration-dependent manner (0.5-5 mu g/mL up to 426 +/- 23%) HPLC-based activity-guided fractionation revealed eugenol as main determinant of this GABAergic activity. Acetyleugenol, an important component of clove bud oil, showed even higher activity than eugenol (1 mu g/mL; 308 +/- 26% versus 234 +/- 29%), but was detected in the aqueous extract only in trace amounts. Thus, the analgesic effects of clove might be partially mediated by positive modulation of the GABAA receptor and eugenol is a major contributor to this activity. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Acetyleugenol; Analgesic activity; Clove buds; Eugenol; GABA(A) receptor; Two-electrode voltage clamp technique

Identification of H2O2 as a major antimicrobial component in coffee - Müller, Ulla; Sauer, Tanja; Weigel, Ingrid; Pichner, Rohtraud; Pischetsrieder, Monika (Food & Function, 2011)
Coffee shows distinct antimicrobial activity against several bacterial genera. The present study investigated molecular mechanisms and active ingredients mediating the antimicrobial effect of coffee. Depending on concentration, roasted, but not raw coffee brew inhibited the growth of Escherichia coli and Listeria innocua. Several coffee ingredients with known antibacterial properties were tested for their contribution to the observed effect. In natural concentration, caffeine, ferulic acid and a mixture of all test compounds showed very weak, but significant activity, whereas trigonelline, 5-(hydroxymethyl)furfural, chlorogenic acid, nicotinic acid, caffeic acid, and methylglyoxal were not active. Antimicrobial activity, however, was completely abolished by addition of catalase indicating that H2O2 is a major antimicrobial coffee component. In accordance with this assumption, bacterial counts during 16 h of incubation were inversely related to the H 2O2 concentration in the incubation solution. Pure H 2O2 showed slightly weaker activity. The H 2O2 dependent antimicrobial activity of coffee could be mimicked by a reaction mixture of d-ribose and l-lysine (30 min 120 °C) indicating that H2O2 is generated in the coffee brew by Maillard reaction products. Identification of H2O2 as major antimicrobial coffee component is important to evaluate the application of coffee or coffee extracts as natural preservatives. © 2011 The Royal Society of Chemistry.
UnivIS-Import:2015-04-14:Pub.2011.nat.dchph.llmch.identi

Identification of hydrogen peroxide as a major cytotoxic component in Maillard reaction mixtures and coffee - Hegele, Jörg; Münch, Gerald; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2009)
The cytotoxic activity of Maillard reaction products and coffee was studied using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay and the neutral red uptake (NRU) assay. Equimolar mixtures of sugars and lysine were heated at 12°8C and used to stimulate bovine aorta endothelial cells for 24 h. The cytotoxic activity increased with increase in educt concentration and heating time. Mixtures containing ribose were most active, followed by lactose and glucose. Hydrogen peroxide, which was present in the Maillard mixtures in concentrations between 7 and 87 μM, was identified as one of their major cytotoxic components. H2O2-concentrations increased further up to 130 μM under cell culture conditions. Filter coffee, espresso, and green coffee extract reduced cell viability significantly to 10, 19, and 83% of PBS-treated control. The effect was largely attenuated by the addition of catalase. Nil, 33, and 41 μM H2O2 was measured in green coffee extract, filter coffee, and espresso, respectively, increasing to 13, 369, and 333 μM during cell culture conditions. No additional H2O2 formation was detected when coffee was incubated for up to 5 h without further treatment. In conclusion, hydrogen peroxide is a major product in Maillard mixtures and coffee inducing cell death in vitro. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.identi
Keywords: Bovine aorta endothelial cells; Coffee; Cytotoxicity; Hydrogen peroxide; Maillard reaction

Identification of multiphosphorylated peptides in milk - Baum, Florian; Ebner, Jennifer; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2013)
Multiphosphorylated peptides endogenously present in milk exert anticariogenic activity due to their calcium binding capacity. This study performed comprehensive analysis of multiphosphorylated peptides in raw milk using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Since phosphopeptides are often negatively discriminated during ionization, putative phosphopeptides were identified by three different methods: (i) selective detection in 4-chloro-α- cyanocinnamic acid MALDI matrix compared to α-cyano-4-hydroxycinnamic acid; (ii) higher relative signal intensity in negative compared to positive ionization mode; and (iii) detection of signal pairs with mass differences of -80 Da or multiples thereof before and after enzymatic dephosphorylation. Thus, 18 putative phosphopeptides from raw milk were annotated. Peptide structures were then determined by product ion spectra from targeted liquid chromatography electrospray ionization tandem-MS analysis. Thus, β-casein33-48, β-casein29-48, β-casein1-21, β-casein 2-25, β-casein1-25, β-casein1-27, β-casein1-28, β-casein1-29, β-casein 1-32, αS2-casein1-21, and αS2-casein1-24 were revealed as major peptides with one or four phosphorylation sites in raw milk. © 2013 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2013.nat.dchph.llmch.identi_3
Keywords: casein phosphopeptides; MALDI-TOF-MS; mass spectrometry; milk; native multiphosphorylated peptides

Identification of peptides reflecting the storage of UHT milk by MALDI-TOF-MS peptide profiling. - Dalabasmaz, Sevim; Dittrich, Daniel; Kellner, Ina; Drewello, Thomas; Pischetsrieder, Monika (Journal of Proteomics, 2019)
Proteolysis during the storage of UHT milk is associated with major technological problems, particularly bitter off-flavors and age gelation limiting the shelf life of milk. In this study, untargeted peptide profiling by MALDITOF- MS identified peptides that were formed by proteolysis and reflected the storage of UHT milk. Analysis of nine different commercial UHT samples recorded peptide profiles during and at the end of their shelf life. Relative quantification and sequencing of the peptides revealed that the concentrations of 22 peptides increased significantly during the storage of UHT milk due to the activity of endogenous milk proteases and microbial proteases as well as other unidentified proteolytic mechanisms. Based on highly discriminative AUC values from receiver operator characteristic (ROC) curve analysis, we selected ten peptides as marker candidates. Among those, the peptide β-casein192–206 (m/z 1668.9) was the most suitable marker differentiating expired-UHT from regular-UHT samples with 100% accuracy. Additionally, β-casein191–206 (m/z 1782.0) showed 100% specificity and β-casein139–161 (m/z 2696.4) 100% sensitivity. Thus, β-casein192–206, either by itself or in combination with β-casein191–206 and β-casein139–161, presents a reliable marker to monitor the storage of UHT milk based on proteolytic mechanisms.
Keywords: Peptide profiling; milk proteases; storage; UHT milk; MALDI-TOF-MS

Identification of Potential Bioactive Peptides in Sheep Milk Kefir through Peptidomic Analysis at Different Fermentation Times - Dalabasmaz, Sevim; de la Torre, Esther Prados; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika; Rodríguez-Ortega, Manuel J. (Foods, 2023)
Sheep farming is an important socioeconomic activity in most Mediterranean countries, particularly Spain, where it contributes added value to rural areas. Sheep milk is used in Spain mainly for making cheese, but it can be used also for making other dairy products, such as the lactic-alcoholic fermentation product known as kefir. Dairy products have health benefits because, among other reasons, they contain molecules with biological activity. In this work, we performed a proteomics strategy to identify the peptidome, i.e., the set of peptides contained in sheep milk kefir fermented for four different periods of time, aiming to understand changes in the pattern of digestion of milk proteins, as well as to identify potential bioactive peptides. In total, we identified 1942 peptides coming from 11 different proteins, and found that the unique peptides differed qualitatively among samples and their numbers increased along the fermentation time. These changes were supported by the increase in ethanol, lactic acid, and D-galactose concentrations, as well as proteolytic activity, as the fermentation progressed. By searching in databases, we found that 78 of the identified peptides, all belonging to caseins, had potential biological activity. Of these, 62 were not previously found in any milk kefir from other animal species. This is the first peptidomic study of sheep milk kefir comprising time-course comparison.
CRIS-Team Scopus Importer:2023-09-29
Keywords: biopeptides; dairy; fermented milk; peptidome; proteomics; sheep

Identification of sixteen peptides reflecting heat and/or storage induced processes by profiling of commercial milk samples - Ebner, Jennifer; Baum, Florian; Pischetsrieder, Monika (Journal of Proteomics, 2016)
Peptide profiles of different drinking milk samples were examined to study how the peptide fingerprint of milk reflects processing conditions. The combination of a simple and fast method for peptide extraction using stage tips and MALDI–TOF–MS enabled the fast and easy generation and relative quantification of peptide fingerprints for high-temperature short-time (HTST), extended shelf life (ESL) and ultra-high temperature (UHT) milk of the same dairies. The relative quantity of 16 peptides changed as a function of increasing heat load. Additional heating experiments showed that among those, the intensity of peptide β-casein 196–209 (m/z 1460.9 Da) was most heavily influenced by heat treatment indicating a putative marker peptide for milk processing conditions. Storage experiments with HTST- and UHT milk revealed that the differences between different types of milk samples were not only caused by the heating process. Relevant was also the proteolytic activity of enzymes during storage, which were differently influenced by the heat treatment. These results indicate that the peptide profile may be suitable to monitor processing as well as storage conditions of milk.
Keywords: Milk; MALDI–TOF–MS; Peptide profiling; Processing marker; Storage marker; Heat treatment

Identification of the Beer Component Hordenine as Food-Derived Dopamine D2 Receptor Agonist by Virtual Screening a 3D Compound Database. - Sommer, Thomas; Hübner, Harald; El Kerdawy, Ahmed; Gmeiner, Peter; Pischetsrieder, Monika; Clark, Timothy (Scientific Reports, 2017)
The dopamine D2 receptor (D2R) is involved in food reward and compulsive food intake. The present study developed a virtual screening (VS) method to identify food components, which may modulate D2R signalling. In contrast to their common applications in drug discovery, VS methods are rarely applied for the discovery of bioactive food compounds. Here, databases were created that exclusively contain substances occurring in food and natural sources (about 13,000 different compounds in total) as the basis for combined pharmacophore searching, hit-list clustering and molecular docking into D2R homology models. From 17 compounds finally tested in radioligand assays to determine their binding affinities, seven were classified as hits (hit rate = 41%). Functional properties of the five most active compounds were further examined in β-arrestin recruitment and cAMP inhibition experiments. D2R-promoted G-protein activation was observed for hordenine, a constituent of barley and beer, with approximately identical ligand efficacy as dopamine (76%) and a Ki value of 13 μM. Moreover, hordenine antagonised D2-mediated β-arrestin recruitment indicating functional selectivity. Application of our databases provides new perspectives for the discovery of bioactive food constituents using VS methods. Based on its presence in beer, we suggest that hordenine significantly contributes to mood-elevating effects of beer.

Identification of the Heptapeptide PR7 and Octapeptide SF8 With Potent Antioxidative and Angiotensin Converting Enzyme Inhibitory Activity From the Fermented Dairy By-Product “Buttermilk” - Magouz, Osama; Ibrahim, Mahmoud A.A.; Mehanna, Nabil; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Pischetsrieder, Monika (Food Frontiers, 2024)
The present study aimed to identify antioxidative and angiotensin converting enzyme (ACE) inhibitory peptides in fermented buttermilk after simulated gastric digestion. Following isoelectric focusing fractionation, peptides of the most active fractions were identified by ultrahigh performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS). Subsequently, 23 peptides were synthesized and tested for antioxidative and ACE inhibitory activity. The peptide PR7 (PWDQVKR, αs2-casein 108–114) exerted comparable antioxidative activity to ascorbic acid, whereas the peptide SF8 (SGPLRPFF, butyrophilin 427–434) efficiently inhibited ACE with an IC50 value of 1.57 µM. The binding modes of the five most active ACE inhibitors were predicted using AlphaFold2 multimer software. Molecular mechanics (MM) minimization and molecular dynamics (MD) simulations of all complexes, followed by MM-generalized born surface area (GBSA) binding energy calculations, were predicted. Notably, these peptides manifested good binding affinities to ACE. The estimated MM-GBSA/MD binding energies correlated with the detected IC50 values [correlation coefficient (R2) = 0.79]. Post-MD analyses over 100 ns elucidated the steadiness of the five peptides.
CRIS-Team Scopus Importer:2025-02-04
Keywords: antioxidant and ACE inhibitory peptides; fermented buttermilk; molecular dynamics (MD) simulations; molecular mechanics (MM) minimization; PWDQVKR; SGPLRPFF

Identification of the oleic acide ethanolamide (OEA) isomer cis-vaccenic acid ethanolamide (VEA) as a highly abundant 18:1 fatty acid ethanolamide in blood plasma from rats and humans - Röhrig, Waldemar; Waibel, Reiner; Perlwitz, Christopher; Pischetsrieder, Monika; Hoch, Tobias (Analytical and Bioanalytical Chemistry, 2016)
The endocannabinoid system is important in various physiological pathways, especially the regulation of food intake. It consists of endocannabinoids like 2-arachidonoyl-glycerol (2-AG) or the fatty acid ethanolamide archachidonoyl-ethanolamide (AEA) with binding affinity to cannabinoid receptors. Further, fatty acid ethanolamides (FAEAs) influence the endocannabinoid system without affecting cannabinoid receptors by using independent physiological pathways. Among FAEAs, oleic acid ethanolamide (OEA) gained importance because of its promising ability to reduce food intake. By ultrahigh-performance liquid chromatography–electrospray ionization–tandem mass spectrometry (UHPLC–ESI–MS/MS), we detected a chromatographically separated molecule in plasma samples from rats and humans with identical mass and fragmentation patterns as those of OEA. Via synthesis and extensive analysis of ethanolamides of different cis/trans- and position isomers of oleic acid (cis9-18:1), we could identify the unknown molecule as vaccenic acid (cis11-18:1) ethanolamide (VEA). In this study we identified VEA as the most abundant 18:1 FAEA in rat plasma and the second most abundant 18:1 FAEA in human plasma.
Keywords: OEA; VEA; fatty acid ethanolamides; endocannabinoid system; LC - MS/MS

Identification of the Peptide PyroQ-beta Casein(194-209) as a Highly Specific and Sensitive Marker to Differentiate between Ultrahigh-Temperature Processed (UHT) Milk and Mildly Heated Milk - Dalabasmaz, Sevim; Ebner, Jennifer; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2017)
In this study, a new approach was introduced to identify marker peptides that reflect the thermal treatment of commercial milk samples and differentiate ultrahigh-temperature processed (UHT) milk from mildly heated milk. Peptide profiles of training set samples, pasteurized (n = 20), extended shelf life (n = 29), and UHT (n = 29) milk, were recorded by MALDI-TOF-MS after StageTip microextraction. As marker candidates, 13 peptides were selected, and their cutoff levels were defined. The quality of the cutoff levels was then tested with a blind test set. Thus, the peptide m/z 1701.0, which was identified as pyroQ-beta casein(194-209), could ideally differentiate UHT milk from mildly heated milk with an accuracy of 100%. Due to its high reliability and sensitivity, this peptide may be applied in routine analysis to monitor thermal processing of milk. An additional heating experiment showed that the marker peptide candidates are formed during milk processing by endogenous enzymes and selective thermal cleavage.
Keywords: Peptide profiling; marker peptide; milk; heating; PCA; MALDI-TOF-MS

Immunochemical Detection of Central Nervous Tissue in Retail Meat Products Using Myelin Proteolipid Protein (PLP) as Marker - Hammon, Antje; Düthorn, Tina; Bäuerlein, Rainer; Becker, Cord-Michael; Pischetsrieder, Monika; Pichner, Rohtraud; Gareis, Manfred (Archiv für Lebensmittelhygiene, 2007)
A total of 152 different meat products (emulsion-type sausages, cooked sausages, fermented raw sausages) originating from local butchers shops and supermarkets were analysed for the presence of tissues from the central nervous system (CNS) by a newly developed Western blot assay using myelin proteolipid protein (PLP) as specific marker. Samples tested positive were analysed in parallel with a commercialized ELISA kit based on the detection of glial fibrillary acidic protein (GFAP). Analysing retail meat products by PL Passay, 9.9% of the samples (15 out of 152) showed positive PLP responses. The positive findings were confirmed in five cases (3.3 %) by application of the GFAP-ELISA. With both methods, very strong signals were detected in two sausages originating from a small butcher shop. Repeated sampling and analyses of these products during a period of several months proved the initial findings indicating a systematic contamination or addition of CNS material. The detection of nearly 10 % of CNS-positive sausages demonstrates that intentional or unintentional contaminations of retail meat products are not uncommon. Overall, the PLP assay was confirmed to be a highly sensitive method for the detection of CNS in both heat-treated and raw fermented sausages. Thus it could be applied for routine and food control purposes. © M.&H. Schaper GmbH&Co.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.llmch.immuno
Keywords: Central nervous system (CNS); Meat products; Myelin proteolipid protein (PLP); Western blotting

Immunochemical Detection of Oxalate Monoalkylamide, an Ascorbate-derived Maillard Reaction Product, in the Human Lens - Nagaraj, Ram H.; Shamsi, Farrukh; Huber, Birgit; Pischetsrieder, Monika (Febs Letters, 1999)
Carbohydrates with reactive aldehyde and ketone groups can undergo Maillard reactions with proteins to form advanced glycation end products. Oxalate monoalkylamide was identified as one of the advanced glycation end products formed from the Maillard reaction of ascorbate with proteins. In these experiments, we have analyzed human lens proteins immunochemically for the presence of oxalate monoalkylamide. Oxalate monoalkylamide was absent in most of the very young lenses but was present in old and cataractous lenses. The highest levels were found in senile brunescent lenses. Incubation experiments using bovine lens proteins revealed that oxalate monoalkylamide could form from the ascorbate degradation products, 2,3-diketogulonate and L-threose. These data provide the first evidence for oxalate monoalkylamide in vivo and suggest that ascorbate degradation and its binding to proteins are enhanced during lens aging and cataract formation.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.immuno
Keywords: Ascorbate degradation; Human lens; Maillard reaction; Oxalate monoalkylamide

Immunochemical Detection of Oxalic Acid Monoamides which are formed during the Oxidative Reaction of L-Ascorbic Acid and Proteins - Pischetsrieder, Monika; Larisch, Bernd; Seidel, Wolfgang (Journal of Agricultural and Food Chemistry, 1997)
Covalent binding of L-ascorbic acid (AA) to proteins (protein ascorbylation) occurs during food processing and storage and in vivo. It contributes, for example, to browning and various changes in the physical and physiological properties of proteins. Since oxalic acid monoalkylamides (OMAs) are formed in high yields from AA and primary amines under oxidative conditions, it was determined if OMAs also represent an ascorbylation product of proteins. Therefore a polyclonal anti-OMA antibody was raised, and a high-titer antiserum was obtained which is specific against OMA. In a competitive ELISA total binding inhibition was achieved by ascorbylated protein, indicating that ascorbylation of proteins leads to the formation of OMA. OMA is only formed under aerobic conditions. Proteins, which were glycosylated with other carbohydrates such as glucose, did not show cross-reactivity, indicating that the antiserum can be used to detect OMA as a specific marker for ascorbylation.
UnivIS-Import:2015-03-05:Pub.1997.nat.dchph.llmch.immuno
Keywords: Ascorbylation; Immunochemical detection; L-Ascorbic acid; Maillard reaction; OMA protein; Oxalic acid monoalkylamide

Immunochemical detection of tissue from the central nervous system via myelin proteolipid protein: adaption for food inspection and development of recombinant bivalent Fab mini-antibodies - Weigel, Ingrid; Schulze, Gesine; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2010)
Bovine spongiform encephalopathy (BSE) is transmitted by the ingestion of central nervous system (CNS) tissue of infected animals. Food inspection must, therefore, test for the presence of CNS tissue in meat and meat products. A Western blot assay for the specific CNS tissue marker myelin proteolipid protein (PLP) was optimized with considerably reduced analysis time, solvent consumption, and detection limit (0.001% CNS tissue in minced beef). Further, a PLP-specific recombinant bivalent fragment antigen binding mini-antibody (anti-PLP Fab) was obtained from a commercial phage display library. Western blot analysis with the anti-PLP Fab selectively detected CNS tissue in minced beef with a detection limit of 0.025%. Model experiments for meat processing revealed that assay sensitivity decreased with increasing temperature and prolonged heating time. A market survey with 687 sausage samples was performed using PLP-Western blot and enzyme-linked immunosorbent assay (ELISA) for glial fibrillary acidic protein (GFAP). Five samples were tested clearly positive by both assay systems, whereas in an additional six samples, CNS tissue was detected only by GFAP ELISA and in two samples only by PLP-Western blot.
UnivIS-Import:2015-03-09:Pub.2010.nat.dchph.llmch.immuno
Keywords: Bovine spongiform encephalopathy (BSE); central nervous system (CNS); myelin proteolipid protein (PLP); monoclonal antibody; recombinant bivalent Fab mini-antibodies; phage display library; Western blot

Influence of nonenzymatic posttranslational modifications on constitution, oligomerization and receptor binding of S100A12 - Augner, Kerstin; Eichler, Jutta; Utz, Wolfgang; Pischetsrieder, Monika (PLoS ONE, 2014)
This study examined the effect of methylglyoxal (MGO)-derived nonenzymatic posttranslational modifications (nePTMs) on the binding affinity of S100A12 to its natural receptor for advanced glycation end-products (RAGE). Binding of MGOmodified S100A12 to RAGE decreased significantly with increasing MGO concentration and incubation time. Ca2+-induced S100A12 hexamerization was impaired only at higher MGO concentrations indicating that the loss of affinity is not predominantly caused by disturbance of ligand oligomerization. nePTM mapping showed carboxyethylation of lysine (CEL) and the N-terminus without preferential modification sites. Besides, hydroimidazolone, hemiaminals, argpyrimidine, and tetrahydropyrimidine rapidly formed at R21. Even at the highest modification rate, hexamerization of synthesized CEL-S100A12 was unaffected and RAGE-binding only slightly impaired. Thus, nePTMs at R21 seem to be the major cause of MGOinduced impairment of S100A12 oligomerization and RAGE binding.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.influe

Influence of Software Settings on the Identification Rate, Quantification Results, and Reproducibility in Profiling Post-Translational Modifications by Microflow Liquid Chromatography-Ion Mobility-Quadrupole Time-Of-Flight Analysis Using PEAKS Software - Mauser, Andreas; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Schichtl, Theresa Maria; Dittrich, Daniel; Pischetsrieder, Monika (Journal of Proteome Research, 2024)
The influence of data evaluation parameters on qualitative and quantitative results of untargeted shotgun profiling of enzymatic and nonenzymatic post-translational modifications (PTMs) was investigated in a model of bovine whey protein α-lactalbumin heated with lactose. Based on the same raw data, individual adjustments to the protein database and enzyme settings of PEAKS studio software increased the identification rate from 27 unmodified peptides to 48 and from 322 peptides in total to 535. The qualitative and quantitative reproducibility was also assessed based on 18 measurements of one sample across three batches. A total of 570 peptides were detected. While 89 peptides were identified in all measurements, the majority of peptides (161) were detected only once and mostly based on nonindicative spectra. The reproducibility of label-free quantification (LFQ) in six measurements of the same sample was similar after processing the data by either the PTM algorithm or the LFQ algorithm. In both cases, about one-third of the peptides showed a coefficient of variation of above 20%. However, the LFQ algorithm increased the number of quantified peptides from 75 to 179. Data are available at the PRIDE Archive with the data set identifier PXD050363.
CRIS-Team Scopus Importer:2024-09-27
Keywords: data evaluation; microLC−IM-QTOF; PTM profiling; reproducibility; untargeted proteomics

Influence of the fat/carbohydrate component of snack food on energy intake pattern and reinforcing properties in rodents - Heß, Andreas; Kreß, Stefanie; Rakete, Stefan; Muench, Gerald; Kornhuber, Johannes; Pischetsrieder, Monika; Müller, Christian P. (Behavioural Brain Research, 2019)
Hedonic intake of strongly rewarding foods is independent from biological needs and, thus, a common cause of obesity. The effect of potato chips on energy intake in a snacking model could be explained by their fat/carbohydrate content (FCHc). The present study investigated if the FCHc shapes energy intake patterns and reward processing of satiated rodents. Modulation of energy intake patterns was studied in an established snacking model offering FCHc rich food for 3 x 10 min/day to satiated rats. Reward processing was analyzed by a previously established conditioned place preference tests in satiated mice. The limited access to FCHc rich food led to higher daily energy intake compared to days without access (110 +/- 10 vs. 96 +/- 5 kcal/day) indicating that fat/carbohydrate intake was not fully compensated by reducing standard chow intake during the rest of the day. Furthermore, fat/carbohydrate snacking led to binge eating episodes with up to 55% of the daily energy intake consumed during limited access. Forced withdrawal from fat/carbohydrate snacking opportunities for six weeks increased the total daily energy intake and the relative amount of energy consumed by FCHc after reintroducing fat/carbohydrate snacking. Snack food and fat/carbohydrate food were powerful food reinforcers in satiated mice in contrast to standard chow. Altogether, these data suggest that the FCHc of snack food has strong reinforcing properties, which are probably responsible for the significant modulation of the amount and pattern of food intake in ad libitum fed animals.
CRIS-Team WoS Importer:2019-04-16

Influence of the production technology on kefir characteristics: Evaluation of microbiological aspects and profiling of phosphopeptides by LC-ESI-QTOF-MS/MS - Savastano, Maria Luisa; Pati, Sandra; Bevilacqua, Antonio; Corbo, Maria Rosaria; Rizzuti, Antonio; Pischetsrieder, Monika; Losito, Ilario (Food Research International, 2020)
The influence of production technology, namely, temperature, pH and 2-step fermentation (back-slopping approach), on the microbiological characteristics and on the phosphopeptide profile of kefir obtained with kefir grains was investigated. The growth of yeasts, lactic acid bacteria (LAB) and acetic acetic bacteria (AAB) in both grains and kefir was affected by the incubation temperature and by the use of back-slopping. In particular, at 25 °C the microbiota of kefir grains was mainly composed by LAB and yeasts, while at 18 °C yeasts represented the dominant group in kefir. Back-slopping at 25 °C determined a significant increase of AAB. A comprehensive characterization of potentially bioactive peptides, including caseino-phosphopeptides (CPPs), was performed, for the first time, in kefir obtained with kefir grains, using preliminary enrichment on hydroxyapatite followed by dephosphorylation and analysis by Liquid Chromatography-ElectroSpray Ionization-Quadrupole-Time of Flight-tandem mass spectrometry (LC-ESI-QTOF-MS/MS). As a result, seventy-three phosphopeptides, mostly arising from caseins (79% β-casein, 8% αs1-casein and 9% αs2-casein) and all including from three to five serine residues in their sequences, were identified. Seventy-one of them showed the typical motif “SerP-SerP-SerP-Glu-Glu”, which is crucial for the ability of caseins to bind to minerals. Several peptides were observed, for the first time, from the 1–40 region of β-casein. As for the effect of production technology, phosphopeptide profiles of kefirs obtained at 25 °C and 18 °C were very similar, whereas kefir produced under acidic conditions showed a predominance of smaller peptides, suggesting a higher level of proteolysis. Conversely, kefir obtained through back-slopping at 25 °C contained longer peptides, thus indicating a lower proteolytic activity and a poor reproducibility in the kefir phosphopeptide profile occurring when grains are reused.<br
Keywords: Kefir; LC-ESI-QTOF-MS/MS; caseino-phosphopeptides; kefir grains; fermentation; back-slopping

Influence of Thermally Processed Carbohydrate/Amino Acid Mixtures on the Fermentation by Saccharomyces cerevisiae - Tauer, Andreas; Elss, Sandra; Frischmann, Matthias; Tellez, Patricia; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2004)
The production of alcoholic beverages such as Tequila, Mezcal, whiskey, or beer includes the fermentation of a mash containing Maillard reaction products. Because excessive heating of the mash can lead to complications during the following fermentation step, the impact of Maillard products on the metabolism of Saccharomyces cerevisiae was investigated. For this purpose, fermentation was carried out in a model system in the presence and absence of Maillard reaction products and formation of ethanol served as a marker for the progression of fermentation. We found that increasing amounts of Maillard products reduced the formation of ethanol up to 80%. This effect was dependent on the pH value during the Maillard reaction, reaction time, as well as the carbohydrate and amino acid component used for the generation of Maillard reaction products. Another important factor is the pH value during fermentation: The inhibitory effect of Maillard products was not detectable at a pH of 4 and increased with higher pH-values. These findings might be of relevance for the production of above-mentioned beverages.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.influe
Keywords: Beer; Fermentation; Maillard reaction; Mezcal; Nonenzymatic browning; Saccharomyces cerevisiae; Tequila; Whiskey; Yeast

In Search for new Products - Pischetsrieder, Monika; Meltretter, Jasmin (Deutsche Lebensmittel-Rundschau, 2012)

Intracellular glycation of nuclear DNA, mitochondrial DNA, and cytosolic proteins during senescence-like growth arrest - Breyer, Viola; Becker, Cord-Michael; Pischetsrieder, Monika (DNA and Cell Biology, 2011)
To investigate the accumulation of intracellular advanced glycation end products (AGEs), a method was established for the simultaneous analysis of glycation products of cytosolic proteins, nuclear DNA, and mitochondrial DNA (mtDNA). Nuclear DNA, mtDNA, and cytosolic proteins were simultaneously isolated from one cell lysate by differential centrifugation and combined mechanical and chemical cell disruption methods. The major DNA-AGE N 2-carboxyethyl- 2′-deoxyguanosine (CEdG) was quantified in nuclear DNA and mtDNA by ELISA, whereas the protein-AGEs N-(carboxymethyl)lysine (CML) and N ε-(carboxyethyl)lysine (CEL) were determined by western blot. The method was used to analyze NIH3T3 fibroblasts. In untreated cells, CEdG levels of mtDNA (14.84 ± 3.07 pg CEdG/μg mtDNA) were significantly higher compared with nuclear DNA (4.40 ± 0.64 pg CEdG/μg DNA; p < 0.001). Then, fibroblasts were analyzed after 7 days of senescence-like growth arrest. In senescent fibroblasts, the CEdG content of nuclear DNA significantly increased by 25%. However, the CEdG level of mtDNA significantly decreased to 52%; in parallel, an increase in mitochondrial mass and mtDNA was observed. Senescence did not lead to general accumulation of protein-AGEs, but two protein bands at 32 and 34 kDa showed a significant increase in the CML/CEL modification rate (208%, p < 0.001; 196%, p = 0.0016) in senescent fibroblasts compared with control cells. © Copyright 2011, Mary Ann Liebert, Inc.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.intrac

Investigations on the Reaction of C3 and C6 α-Dicarbonyl Compounds with Hydroxytyrosol and Related Compounds under Competitive Conditions. - Navarro, Marta; Atzenbeck, Lisa; Pischetsrieder, Monika; Morales, Francesco (Journal of agricultural and food chemistry, 2016)
α-Dicarbonyl compounds are intermediates in reactions that lead to the formation of potentially harmful advanced glycation end-products. Carbonyl-trapping capacities of antiglycative substances have been traditionally limited to C2 and C3 α-dicarbonyl structures. Glyoxal (GO)-, methylglyoxal (MGO)-, 3-deoxyglucosone (3-DG)-, 3-deoxygalactosone (3-DGal)-, 3,4-dideoxyglucoson-3-ene-, and glucosone-trapping capacities of hydroxytyrosol (HT), hydroxytyrosol acetate (HTA), and 3,4-dihydroxyphenylacetic acid (DOPAC) in simple (phenolic/dicarbonyl) and competitive model systems (phenolic/dicarbonyl1/dicarbonyl2) were investigated. HT and HTA were more effective for MGO than 3-DG and 3-DGal. Furthermore, DOPAC exerted higher trapping capacity than HT and HTA for C3 and C6 α-dicarbonyl compounds. In the competitive systems, HT-related substances did not show preference for trapping 3-DG or 3-DGal and behaved as in the simple systems. In the presence of MGO, however, HT-related substances were more effective for trapping MGO than C6 structures. The results demonstrate the C6 α-dicarbonyl-trapping capacities of HT, HTA, and DOPAC, with DOPAC exerting the highest activity.
Keywords: hydroxytyrosol; α-dicarbonyl compounds; carbonyl-trapping capacity; 3-deoxyglucosone; 3-deoxygalactosone; methylglyoxal

In vitro formation of Nepsilon -(carboxymethyl)lysine and imidazolones under conditions similar to continous ambulatory peritoneal dialysis (CAPD) - Tauer, Andreas; Knerr, Thomas; Niwa, Toshimitsu; Schaub, Thomas; Lage, Cristina; Passlick-Deetjen, Jutta; Pischetsrieder, Monika (Biochemical and Biophysical Research Communications, 2001)
Conventional peritoneal dialysis fluids (PDFs) lead to formation of advanced glycation end-products (AGE) in the peritoneal membrane. In this study, we investigated in vitro the dependence of AGE formation on regular changes of PDFs, as performed during continuous ambulatory peritoneal dialysis (CAPD), and on the contribution of high glucose concentration versus glucose degradation products (GDPs). Under conditions similar to CAPD, protein glycating activity of a conventional single chamber bag PDF (CAPD 4.25%), two double chamber bag PDFs (CAPD Balance 4.25% and CAPD Bicarbonate 4.25%) and a sterile filtered control was measured in vitro by Ne-(carboxymethyl) lysine (CML) and imidazolones, two well characterized, physiologically relevant AGE structures. Regular changes of PDFs increased AGE formation (CML 3.3-fold and imidazolone 2.6-fold) compared to incubation without changes. AGE formation by CAPD 4.25% was increased compared to control (imidazolones 7.9-fold and CML 3.3-fold) and the use of double chamber bag PDFs led to a decrease of imidazolones by 79% (CAPD Bicarbonate 4.25%) and by 66% (CAPD Balance 4.25%) and to CML contents similar to the control. These results indicate that a major part of AGEs were formed by GDPs in PDFs, whereas only a minor part was due to high glucose concentration. The use of double chamber bag fluids can reduce AGE formation considerably.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.invitr
Keywords: advanced glycation end-products; Ne-(carboxymethyl) lysine; CML; imidazolones; glucose degradation products; peritoneal dialysis; 3-deoxyglucosone

In Vitro Reactivity of the Glucose Degradation Product 3,4-Dideoxyglucosone-3-ene (3,4-DGE) towards Abundant Components of the Human Blood Circulatory System - Auditore, Andrea; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (International Journal of Molecular Sciences, 2022)
3,4-Dideoxyglucosone-3-ene (3,4-DGE) is a glucose degradation product present in processed foods and medicinal products. Additionally, its constant formation from 3-deoxyglucosone in plasma has been suggested. Due to its α,β-unsaturated dicarbonyl moiety, 3,4-DGE is highly reactive and has shown harmful effects in vitro. Here, we investigated the impact of major components of the human blood circulatory system on 3,4-DGE in vitro. Under physiological conditions, plasma concentrations of human serum albumin (HSA) reacted efficiently with 3,4-DGE, resulting in only 8.5% of the initial 3,4-DGE concentration after seven hours (vs. 83.4% without HSA, p < 0.001). Thereby, accessible thiol groups were reduced from 0.121 to 0.064 mol/mol HSA, whereas ketoprofen binding and esterase-like activity of HSA were not affected. Plasma concentrations of glutathione (GSH) reacted immediately and completely with 3,4-DGE, leading to two stereoisomeric adducts. Plasma concentrations of immunoglobulin G (IgG) bound to 3,4-DGE to a lower extent, resulting in 62.6% 3,4-DGE after seven hours (vs. 82.2% in the control, p < 0.01). Immobilized human collagen type IV did not alter 3,4-DGE concentrations. The results indicated that particularly HSA, GSH, and IgG readily scavenge 3,4-DGE after its appearance in the blood stream, which may be associated with a reduced antioxidative and cytoprotective activity for the living cells and, thus, the human organism by blocking free thiol groups.
CRIS-Team Scopus Importer:2022-04-29
Keywords: 3; 4-dideoxyglucosone-3-ene (3; 4-DGE); collagen type IV; diabetes; glucose degradation product; glycation; human serum albumin; immunoglobulin G; L-glutathione; oxidative stress; α; β-unsaturated dicarbonyl

Isolation, Purification and Characterization of Amadoriase Isoenzymes (Fructosyl Amine: Oxygen Oxidoreductase EC 1.5.3.) from Aspergillus sp - Takahashi, Motoko; Pischetsrieder, Monika; Monnier, Vincent (Journal of Biological Chemistry, 1997)
Four 'amadoriase' enzyme fractions, which oxidatively degrade glycated low molecular weight amines and amino acids under formation of hydrogen peroxide and glucosone, were isolated from an Aspergillus sp. soil strain selected on fructosyl adamantanamine as sole carbon source. The enzymes were purified to homogeneity using a combination of ion exchange, hydroxyapatite, gel filtration, and Mono Q column chromatography. Molecular masses of amadoriase enzymes Ia, Ib, and Ic were 51 kDa, and 49 kDa for amadoriase II. Apparent kinetic constants for N(ε)-fructosyl N(α)-t-butoxycarbonyl lysine and fructosyl adamantanamine were almost identical for enzymes Ia, Ib, and Ic, but corresponding values for enzyme II were significantly different. FAD was identified in all enzymes based on its typical absorption spectrum. N- terminal sequence was identical for enzymes Ia and Ib (Ala-Pro-Ser-Ile-Leu- Ser-Thr-Glu-Ser-Ser-Ile-Ile-Val-Ile-Gly-Ala-Gly-Thr-Trp-Gly-) and Ic except that the first 5 amino acids were truncated. The sequence of enzyme II was different (Ala-Val-Thr-Lys-Ser-Ser-Ser-Leu-Leu-Ile-Val-Gly-Ala-Gly-Thr-Trp- Gly-Thr-Ser-Thr-). All enzymes had the FAD cofactor-binding consensus sequence Gly-X-Gly-X-X-Gly within the N-terminal sequence. In summary, these data show the presence of two distinct amadoriase enzymes in the Aspergillus sp. soil strain selected on fructosyl adamantanamine and induced by fructosyl propylamine. In contrast to previous described enzymes, these novel amadoriase enzymes can deglycate both glycated amines and amino acids.
UnivIS-Import:2015-03-05:Pub.1997.nat.dchph.llmch.isolat

Lysozyme allergen in cheese and potential impact on health - Schneider, Nadine; Pischetsrieder, Monika (Handbook of Cheese in Health: Production, Nutrition and Medical Sciences, 2013)
The enzyme lysozyme can be used as a preservative in cheese to prevent late gas blowing caused by Clostridia and provides an alternative to nitrate or the bacteriocin nisin. Lysozyme acts against Gram-positive bacteria by hydrolysing the peptidoglycan layer between the sugar derivatives N-acetylglucosamine and N-acetylmuramic acid. For the use as food additive, it is produced from hen egg white, which contains the highest natural amounts of this enzyme (about 3.5% of the total protein content). However, lysozyme entails allergy risks representing one of the egg allergens besides the major hen egg white proteins ovalbumin, ovotransferrin (conalbumin), and ovomucoid. Different investigations addressing possible allergic reactions to lysozyme-containing cheese by skin prick tests, radioallergosorbent tests and double-blind, placebo-controlled food challenges came to controversial conclusions. Some studies found correlations between the consumption of lysozyme-containing cheese and acute allergic reactions, whereas in a recently published work, egg allergic patients did not show allergy symptoms after the oral intake of cheese containing lysozyme. In summary, it cannot be excluded that sufferers from an egg allergy show adverse reactions to lysozyme used as preservative in cheese. Therefore, the declaration of lysozyme on the packaging of lysozyme-containing cheese is mandatory.
Keywords: Food allergy; Hen's egg; Lysozyme; Preservative

Maillard Reaction of d-Glucose: Identification of a Colored Product with Hydroxypyrrole and Hydroxypyrrolinone Rings Connected by a Methine Group - Lerche, Holger; Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 2003)
Investigation of the colored products formed by the reaction of D-glucose with butylammonium acetate has been extended. The previously unknown 1-N-butyl-4-hydroxy-5-methyl-2-(N-butyl-3-hydroxy-5-(2-hydroxyethyl) pyrrolyl-2-methylidene)-2H-pyrrolin-3-one (2a) was isolated from the reaction mixture and identified after acylation by spectroscopic data. Butylaminammonium acetate was used as a model compound representing the lysine side chains of proteins.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.mailla
Keywords: Color formation; D-glucose; Maillard reaction

Maillard Reaction of Glucose. Identification of a colored product with conjugated pyrrole and furanone rings - Lerche, Holger; Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 2002)
Formation of colored compounds during the Maillard reaction of D-glucose with butylammonium acetate in aqueous solution has been investigated. Butylamine was used as a model compound analogous to the lysine side chains of proteins. The previously unknown, yellow product, 4-hydroxy-5-methyl-2-(N-butyl-3-hydroxy-5-(2-hydroxyethyl) pyrrolyl-2-methylidene)-2H-furan-3-one (1a), was isolated from the reaction mixtures and identified by spectroscopic data.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.mailla
Keywords: Color formation; D-glucose; Maillard reaction

Maillard reaction of maltose-isolation of 4-(glucopyranosyloxy)-5-(hydroxymethyl)-2-methyl-3(2H)-furanone - Pischetsrieder, Monika; Severin, Theodor (Journal of Agricultural and Food Chemistry, 1994)
Heating of a neutral aqueous solution of maltose and a primary amine leads to the formation of 4-(glucopyranosyloxy)-5-(hydroxymethyl)-2-methyl-3(2H)-furanone(6). When a maltose/amine reaction mixture is separated by HPLC, compound 6 appears as a main product along with the previously described compounds 1-5.
UnivIS-Import:2015-03-05:Pub.1994.nat.dchph.llmch.mailla

Maillard reaction products as antimicrobial components for packaging films - Hauser, Carolin; Müller, Ulla; Sauer, Tanja; Augner, Kerstin; Pischetsrieder, Monika (Food Chemistry, 2014)
Active packaging foils with incorporated antimicrobial agents release the active ingredient during food storage. Maillard reaction products (MRPs) show antimicrobial activity that is at least partially mediated by H 2O2. De novo generation of H2O2 by an MRP fraction, extracted from a ribose/lysine Maillard reaction mixture by 85% ethanol, was monitored at three concentrations (1.6, 16.1, and 32.3 g/L) and three temperatures (4, 25, and 37 C) between 0 and 96 h, reaching a maximum of 335 μM H2O2 (32.3 g/L, 37 C, 96 h). The active MRP fraction (16.1 g/L) completely inhibited the growth of Escherichia coli for 24 h and was therefore incorporated in a polyvinyl acetate-based lacquer and dispersed onto a low-density polyethylene film. The coated film generated about 100 μM H2O2 and resulted in a log-reduction of >5 log-cycles against E. coli. Thus, MRPs can be considered as active ingredients for antimicrobial packaging materials. © 2013 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.mailla
Keywords: Active packaging; Antimicrobial films; Hydrogen peroxide; Maillard reaction products; Preservation

Maillard Reaction Products Inhibit Oxidation of Human Low-Density Lipoproteins in Vitro - Dittrich, Ralf; El-Massry, Khaled Farouk; Kunz, Katrin; Rinaldi, Francesco; Peich, Carlo; Beckmann, Matthias; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2003)
Dietary intake of antioxidants has been associated with a reduced risk of cardiovascular diseases, which is very likely caused by their capability of prevent oxidation of low-density lipoproteins (LDL). During food processing and storage, substances with antioxidative properties are formed by Maillard reactions. In this study, the activity of Maillard products to inhibit copper-induced oxidation of human LDL in vitro was investigated. D-Glucose was heated with an equimolar amount of glycine, L-lysine, or L-arginine, for 1 h under reflux. The increase of the antioxidative activity (AOA) of the Maillard mixtures was highly significant compared to the control mixtures. Additionally, two defined Maillard products with amino reductone structure were tested. 3-Hydroxy-4-(morpholino)-3-buten-2-one (1) and amino hexose reductone (2) showed a significant and dose dependent AOA. Compound 1 was about half as active as ascorbic acid, which served as positive control. Thus, it can be concluded that Maillard products, particularly those with amino reductone structure, have the strong potential to inhibit LDL oxidation.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.mailla_0
Keywords: Amino hexose reductone; Amino reductones; LDL oxidation; Low-density lipoprotein; Maillard reaction

Maillard reactions of dextrins and starch - Kramhöller, Barbara; Pischetsrieder, Monika; Severin, Theodor (Zeitschrift für Lebensmittel-Untersuchung und -Forschung, 1993)
When dextrins or starch are heated with propyl-amine in neutral aqueous solution at 100-130° C a brown colouration is observed. From the reaction mixture 3-hydroxy-2-methyl-1-propyl-4(1H)-pyridone 11, 1,4-dihy-dro-2-methyl-1-propyl-4-propylimino-3-pyridinol 12 and 5-hydroxymethyl-1-propyl-pyrrol-2-aldehyde 13 can be extracted with organic solvents and separated by HPLC. Enzymatic hydrolysis effects the release of 1(3-hydroxy-1-propyl-2-pyrrolyl)-1-ethanone 10 from a glycosidically bound precursor.
UnivIS-Import:2015-03-05:Pub.1993.nat.dchph.llmch.mailla

Maillard-Reaktion und AGEs. Auf der Suche nach neuen Produkten - Pischetsrieder, Monika; Meltretter, Jasmin (Deutsche Lebensmittel-Rundschau, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.mailla

MALDI-TOF MS Characterization of glycation products of whey proteins in a glucose/galactose model system and lactose-free milk - Carulli, Saverio; Calvano, Cosima; Palmisano, Francesco; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2011)
The major modifications induced by thermal treatment of whey proteins α-lactalbumin (α-La) and β-lactoglobulin (β-Lg) in a model system mimicking lactose-free milk (L- sugar mix) were investigated by matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS). The analysis of the intact α-La revealed species with up to 7 and 14 adducts from lactose and sugar mix, respectively, whereas for β-Lg 3 and up to 5 sugar moieties were observed in the case of lactose and sugar mix experiments, respectively. A partial enzymatic hydrolysis with endoproteinase AspN prior to mass spectrometric analysis allowed the detection of further modifications and their localization in the amino acid sequence. Using α-cyano-4-chlorocinnamic acid as MALDI matrix, it could be shown that heating α-La and β-Lg with glucose or galactose led to the modification of lysine residues that are not glycated by lactose. The higher glycation degree of whey proteins in a lactose-free milk system relative to normal milk with lactose reflects the higher reactivity of monosaccharides compared to the parent disaccharide. Finally, the analysis of the whey extract of a commercial lactose-free milk sample revealed that the two whey proteins were present as three main forms (native, single, and double hexose adducts). © 2011 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.maldit
Keywords: AspN; glycation; lactose-free milk; MALDI mass spectrometry; whey proteins

Manganese-Enhanced Magnetic Resonance Imaging for Mapping of Whole Brain Activity Patterns Associated with the Intake of Snack Food in Ad Libitum Fed Rats - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (PLoS ONE, 2013)
Non-homeostatic hyperphagia, which is a major contributor to obesity-related hyperalimentation, is associated with the diet's molecular composition influencing, for example, the energy content. Thus, specific food items such as snack food may induce food intake independent from the state of satiety. To elucidate mechanisms how snack food may induce non-homeostatic food intake, it was tested if manganese-enhanced magnetic resonance imaging (MEMRI) was suitable for mapping the whole brain activity related to standard and snack food intake under normal behavioral situation. Application of the MnCl2 solution by osmotic pumps ensured that food intake was not significantly affected by the treatment. After z-score normalization and a non-affine three-dimensional registration to a rat brain atlas, significantly different grey values of 80 predefined brain structures were recorded in ad libitum fed rats after the intake of potato chips compared to standard chow at the group level. Ten of these areas had previously been connected to food intake, in particular to hyperphagia (e.g. dorsomedial hypothalamus or the anterior paraventricular thalamic nucleus) or to the satiety system (e.g. arcuate hypothalamic nucleus or solitary tract); 27 areas were related to reward/addiction including the core and shell of the nucleus accumbens, the ventral pallidum and the ventral striatum (caudate and putamen). Eleven areas associated to sleep displayed significantly reduced Mn2+-accumulation and six areas related to locomotor activity showed significantly increased Mn2+-accumulation after the intake of potato chips. The latter changes were associated with an observed significantly higher locomotor activity. Osmotic pump-assisted MEMRI proved to be a promising technique for functional mapping of whole brain activity patterns associated to nutritional intake under normal behavior.

Mapping the glycoxidation product Nepsilon-carboxymethyllysine in the milk proteome - Meyer, Bianca; Al-Diab, Dima; Vollmer, Gregor; Pischetsrieder, Monika (Proteomics, 2011)
Milk processing leads to severe protein damage caused by the formation of nonenzymatic posttranslational modifications (nePTMs), such as glycation and glycoxidation. As a result, the technological and nutritional function of milk proteins can be critically altered. The present study investigated the protein-specific distribution of the glycoxidation product Ne-carboxymethyllysine (CML) in the proteome of processed milk. For this purpose, raw milk and heated milk were separated by 1-D or 2-DE. The distribution of CML in the milk proteome was examined by immunoblotting. The changes in the protein composition that occurred during heating were monitored by Coomassie staining. Relative modification rates were measured for the major milk protein fractions after 30 and 60 min of heating at 1201C and normalized to the content of the respective protein fraction in the samples. The highest glycoxidation rates were detected in the high molecular weight aggregates that are generated during heating. The casein fraction and the whey protein b-lactoglobulin were affected in a similar manner. The relevance of the results for industrial milk processing was confirmed by analyzing several commercial milk products accordingly. The presented approach allows nonenzymatic posttranslational modification mapping of the entire milk proteome.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.mappin
Keywords: 2-DE; Advanced glycation end-products; Glycoproteomics; Milk proteome; Nepsilon-carboxymethyllysine; Protein-specific modification

Mercapturic acids of acrylamide and glycidamide as biomarkers of the internal exposure to acrylamide in the general population - Böttcher, Melanie; Schettgen, Thomas; Kütting, Birgitta; Pischetsrieder, Monika; Angerer, Jürgen (Mutation Research-Genetic Toxicology and Environmental Mutagenesis, 2005)
Acrylamide (AA), a widely used industrial monomer which is categorised to be carcinogenic, was found to be generated in starch-containing foods during the heating process. This discovery has caused reasonable concern about possible health risks to humans due to dietary acrylamide uptake. In order to gain more information on human metabolism of acrylamide and to contribute to the assessment of the human carcinogenic risk due to AA uptake we measured the mercapturic acid of AA and its epoxide glycidamide (GA) i.e. N-acetyl-S-(2-carbamoylethyl)-l-cysteine (AAMA) and N-(R,S)-acetyl-S-(2- carbamoyl-2-hydroxyethyl)-l-cysteine (GAMA) in human urine. The relation between AAMA and GAMA is important in this context because GA is thought to be the ultimate carcinogenic metabolite of AA. The median levels in smokers (n = 13) were found to be about four times higher than in non-smokers (n = 16) with median levels of 127 μg/l versus 29 μg/l for AAMA and 19 μg/l versus 5 μg/l for GAMA. Therefore cigarette smoke proved to be an important source of acrylamide exposure. The level of AAMA in the occupationally non-exposed collective (n = 29) ranged from 3 to 338 μg/l, the level of GAMA from
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.mercap
Keywords: Acrylamide; Biological monitoring; General population; Mercapturic acids; Metabolism; Risk estimation

Metal cations promote α-dicarbonyl formation in glucose-containing peritoneal dialysis fluids. - Gensberger-Reigl, Sabrina; Auditore, Andrea; Huppert, Jochen; Pischetsrieder, Monika (Glycoconjugate Journal, 2021)
Heat sterilization of peritoneal dialysis fluids (PDFs) leads to the formation of glucose degradation products (GDPs), which impair long-term peritoneal dialysis. The current study investigated the effects of metal ions, which occur as trace impurities in the fluids, on the formation of six major α-dicarbonyl GDPs, namely glucosone, glyoxal, methylglyoxal, 3-deoxyglucosone, 3-deoxygalactosone, and 3,4-dideoxyglucosone-3-ene. The chelation of metal ions by 2-[bis[2-[bis(carboxymethyl)amino]ethyl]amino]acetic acid (DTPA) during sterilization significantly decreased the total GDP content (585 μM vs. 672 μM), mainly due to the decrease of the glucose-oxidation products glucosone (14 μM vs. 61 μM) and glyoxal (3 μM vs. 11 μM), but also of methylglyoxal (14 μM vs. 31 μM). The glucose-dehydration products 3-deoxyglucosone, 3-deoxygalactosone, and 3,4-dideoxyglucosone-3-ene were not significantly affected by chelation of metal ions. Additionally, PDFs were spiked with eleven different metal ions, which were detected as traces in commercial PDFs, to investigate their influence on GDP formation during heat sterilization. Iron(II), manganese(II), and chromium(III) had the highest impact increasing the formation of glucosone (1.2-1.5 fold increase) and glyoxal (1.3-1.5 fold increase). Nickel(II) and vanadium(III) further promoted the formation of glyoxal (1.3 fold increase). The increase of the pH value of the PDFs from pH 5.5 to a physiological pH of 7.5 resulted in a decreased formation of total GDPs (672 μM vs 637 μM). These results indicate that the adjustment of metal ions and the pH value may be a strategy to further decrease the content of GDPs in PDFs.
Keywords: Glucose degradation products (GDPs); alpha-Dicarbonyls; Peritoneal dialysis fluid; Metal cations

Methionine sulfoxide profiling of milk proteins to assess the influence of lipids on protein oxidation in milk - Wüst, Johannes; Pischetsrieder, Monika (Food and Function, 2016)
Thermal treatment of milk and milk products leads to protein oxidation, mainly the formation of methionine sulfoxide. Reactive oxygen species, responsible for the oxidation, can be generated by Maillard reaction, autoxidation of sugars, or lipid peroxidation. The present study investigated the influence of milk fat on methionine oxidation in milk. For this purpose, quantitative methionine sulfoxide profiling of all ten methionine residues of β-lactoglobulin, α-lactalbumin, and αs1-casein was carried out by ultrahigh-performance liquid chromatography–electrospray ionization tandem mass spectrometry with scheduled multiple reaction monitoring (UHPLC–ESI–MS/MS–sMRM). Analysis of defatted and regular raw milk samples after heating for up to 8 min at 120 °C and analysis of ultrahigh-temperature milk samples with 0.1%, 1.5%, and 3.5% fat revealed that methionine oxidation of the five residues of the whey proteins and of residues M 123, M 135, and M 196 of αs1-casein was not affected or even suppressed in the presence of milk fat. Only the oxidation of residues M 54 and M 60 of αs1-casein was promoted by lipids. In evaporated milk samples, formation of methionine sulfoxide was hardly influenced by the fat content of the samples. Thus, it can be concluded that lipid oxidation products are not the major cause of methionine oxidation in milk.

Modified peptides as indicators for thermal and nonthermal reactions in processed milk - Meltretter, Jasmin; Wüst, Johannes; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2014)
Site-specific relative quantification of β-lactoglobulin modifications in heated milk and dairy products was performed to determine their thermal and nonthermal origins and to evaluate marker candidates for milk processing. Therefore, formation kinetics of 19 different structures at 26 binding sites were analyzed by ultrahigh-performance liquid chromatography-tandem mass spectrometry with multiple reaction monitoring (UHPLC-MS/MS/MRM) after specific protein hydrolysis. The results indicate that (i) site-specific analysis of lactulosyllysine may be a more sensitive marker for mild heat treatment than its overall content; (ii) Nε-carboxymethyllysine, N-terminal ketoamide, and asparagine deamidation are of thermal origin and may be good markers for rather intensive heat treatment, whereas Nε-carboxyethyllysine reflects thermal and nonthermal processes; (iii) the relevance of methylglyoxal-derived arginine modifications is low compared to that of other modifications; (iv) oxidation of methionine and cysteine is a rather weak indicator of thermal impact; and (v) the tryptophan modifications formylkynurenine and kynurenine are of nonthermal origin and further degraded during processing.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.modifi
Keywords: heat marker; mass spectrometry; milk; protein modification; β-lactoglobulin

Molekulare Ernährungsphysiologie. Neurotrition - wie Lebensmittel auf die Gehirnfunktion wirken - Sahin, Sümeyye; Büttner, Andrea; Pischetsrieder, Monika (Chemie in Unserer Zeit, 2019)
Was passiert in unserem Körper, wenn wir Kaffee trinken und warum verlieren auch oft gesunde Menschen die Kontrolle, wenn Kartoffelchips oder Schokolade locken? Die molekulare Ernährungsphysiologie versucht, die Wirkungen von Lebensmitteln definierten molekularen Inhaltsstoffen zuzuordnen. Beim Kaffee weiß man, dass und wie das Koffein uns wachhält. Auch einigen anderen Mechanismen sind die Lebensmittelchemiker auf der Spur.<br
Keywords: Molekulare Ernährungsphysiologie; Sensorik; Lebensmittel; Gehirnaktivität; GABA-Rezeptor

Monitoring of the dopamine D2 receptor agonists hordenine and N-methyltyramine during the brewing process and in commercial beer samples - Sommer, Thomas; Dlugash, Gelena; Hübner, Harald; Gmeiner, Peter; Pischetsrieder, Monika (Food Chemistry, 2019)
The phenethylamine alkaloid hordenine, present in germinated barley, was identified recently as a functionally selective dopamine D2 receptor agonist contributing potentially to the rewarding effects of drinking beer. Here, it was shown that the hordenine precursor N-methyltyramine binds with a similar affinity to the dopamine D2 receptor as hordenine (K-i 31.3 mu M) showing also selectivity towards the G protein-mediated pathway over the beta-arrestin pathway. Using a newly developed UHPLC-ESI-MS/MS method to monitor beer production, we demonstrated that hordenine and N-methyltyramine were released continuously from barley malt during mashing and were stable during fermentation and conditioning. The amounts released from different base malt types were in a similar range but tended to be higher from caramel malts. Hordenine and N-methyltyramine concentrations in 24 types of beer varied between 1.05-6.32 and 0.59-4.61 mg/L, respectively. Thus, the human uptake of the alkaloids during beer consumption is in the low milligram range.
Keywords: Beer; Brewing; Dopamine D2 receptor agonist; Fermentation; Hordenine; Mashing; N-Methyltyramine

Multistep ultrahigh performance liquid chromatography/tandem mass spectrometry analysis for untargeted quantification of glycating activity and identification of most relevant glycation products - Mittelmaier, Stefan; Pischetsrieder, Monika (Analytical Chemistry, 2011)
The use of advanced glycation end-products (AGEs) as biomarkers for diagnosis and clinical studies is still hampered by insufficient knowledge on clinically relevant structures formed from precursors associated with defined disease states. The present study conducted untargeted analysis of the glycating activity of AGE-precursors by ultrahigh performance liquid chromatography/ tandem mass spectrometry multiple reaction monitoring (UHPLC/MSMS-MRM), monitoring the loss of a nonapeptide as the glycation target. Thus, the glycating activities of seven important AGE-precursors were determined (glucose 13% and the reactive carbonyl compounds glucosone 39%, 3-deoxyglucosone 15%, 3-deoxygalactosone 26%, 3,4-dideoxyglucosone-3-ene 79%, methylglyoxal 94%, and glyoxal 97% peptide loss; 12 h/37 °C). Furthermore, UHPLC/MSMS with simultaneous precursor ion scan and information-dependent acquisition of enhanced resolution spectra and subsequent product ion scan was applied for untargeted analysis of the major AGE-structures derived from various AGE-precursors. The 20 most important modifications could be assigned to 8 AGE-structures previously reported in the literature. Seven loosely bound AGEs not yet covered by conventional methods were detected and assigned to hemiaminals. Five AGE structures did not match any known products. The method can be applied to analyze glycating activity and AGE-structures formed from various other precursors under defined reaction conditions, supporting the selection and evaluation of diagnostic AGE-markers for clinical studies. © 2011 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.multis

Myelin Proteolipid Protein (PLP) as a Marker Antigen of Central Nervous System Contaminations for Routine Food Control - Villmann, Carmen; Sandmeier, Barbara; Seeber, Silke; Hannappel, Ewald; Pischetsrieder, Monika; Becker, Cord-Michael (Journal of Agricultural and Food Chemistry, 2007)
Spreading transmissible spongiform encephalopathies (TSE) have been widely attributed to transmission by ingestion of mammalian central nervous system (CNS) tissue. Reliable exclusion of this epidemiological important route of transmission relies on an effective surveillance of food contamination. Here, myelin proteolipid protein (PLP) is identified as a specific and largely heat-resistant marker for detection of food contaminations by CNS tissue. PLP is a component of oligodendritic glial sheaths of neuronal processes that is specifically expressed in the CNS. A highly selective polyclonal antibody was developed directed against an epitope present in the full-length PLP protein, but absent from the developmentally regulated splice variant DM-20. In combination with a hydrophobic extraction of PLP from tissue samples, the antibody reliably detected PLP from spinal cord, cerebellum, and cortex of different mammalian species. Consistent with earlier reports on PLP expression, no cross-reactivity was observed with peripheral nerve or extraneural tissue, except for a very faint signal obtained with heart. When applied to an artificial CNS contamination present in sausages, the antibody reliably detected a low concentration (1%) of the contaminant. Application of heat, as used during conventional sausage manufacturing, led to a predominant alteration of arginine residues in the PLP protein and a partial loss of immunoreactivity. In contrast, a stretch of hydrophilic amino acids112-122 proved to be heat-resistant, preserving the immunogenicity of this PLP epitope during heating. Taken together, the excellent CNS specificity of PLP immunodetection and the presence of a heat-resistant epitope have permitted the development of a highly sensitive immunoassay for CNS contamination in routine food control. © 2007 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.llmch.myelin
Keywords: CNS; Food contamination; Myelin proteolipid protein; Polyclonal antibody

N2-(1-Carboxyethyl)deoxyguanosine, a nonenzymatic glycation adduct of DNA induces single strand breaks and increases mutation frequencies - Pischetsrieder, Monika; Seidel, Wolfgang; Münch, Gerald; Schinzel, Reinhard (Biochemical and Biophysical Research Communications, 1999)
N2-(1-Carboxyethyl)deoxyguanosine (CEdG) is a major nonenzymatic glycation product of DNA. The effect of CEdG modification, which was specifically prepared by incubation with dihydroxyacetone, on plasmid DNA topology was evaluated by gel electrophoresis. A time-dependent decrease of supercoiled plasmid-DNA was observed in parallel to the increase of CEdG adducts; the half-life time of the supercoiled plasmid-DNA was estimated to be approximately 16-18 h. CEdG-modified plasmid DNA showed a 25-fold re duced transformation efficiency. When modified DNA was used to transform Escherichia coli cells, a 6-fold increase in mutation frequency was determined by measuring loss of alpha-complementation. For the mutator strain BMH71-18mutS, an 8-fold increase in mutation frequency was observed. Although the exact mechanism of DNA damage is unclear, the occurrence of spontaneous depurination is likely. These findings suggest that a defined DNA glycation reaction can lead to DNA damage in vivo.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.n21car

N²-carboxyethyl-2'-deoxyguanosine, a DNA glycation marker, in kidneys and aortas of diabetic and uremic patients - Li, H.; Nakamura, Sakurako; Miyazaki, Shigeru; Morita, T.; Suzuki, M.; Pischetsrieder, Monika; Niwa, Toshimitsu (Kidney International, 2006)
Advanced glycation end product (AGE)-mediated modification of proteins is enhanced both in the kidneys and aortas of diabetic and uremic patients. However, AGE modification of deoxyribonucleic acid (DNA) has not yet been reported in these patients. We performed immunohistochemistry of kidneys and aortas using a monoclonal antibody against N2-carboxyethyl-2′- deoxyguanosine (CEdG), a marker of AGE-linked DNA. A total of 20 kidneys and 20 aortas were obtained by autopsy. The kidney samples consisted of two groups: nondiabetic nonkidney disease (control) and diabetic nephropathy. The aorta samples consisted of four groups: nondiabetic nonkidney disease (control), diabetes, hemodialysis, and diabetic hemodialysis. In the kidneys CEdG was detected predominantly in the nuclei of epithelial cells, mesangial cells, and endothelial cells of the glomeruli, parietal epithelial cells, and tubular cells. The number of CEdG-positive cells in the glomeruli was significantly increased in diabetic nephropathy compared with control. In the aortic walls, CEdG was detected predominantly in the nuclei of macrophages and myofibroblasts. The number of CEdG-positive cells in the aorta was significantly increased in hemodialysis patients and diabetic hemodialysis patients compared with control. The highest number of CEdG-positive cells in the aorta was observed in diabetic hemodialysis patients. In conclusion, AGE-mediated modification of DNA is enhanced in the kidney of diabetic nephropathy and the aorta of uremic atherosclerosis, and may induce a loss of genetic integrity in these diseases. © 2006 International Society of Nephrology.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.llmch.ncarbo
Keywords: Advanced glycation end products; Aorta; Diabetes; Hemodialysis; Kidney; N

N -(Carboxymethyl)lysine adducts of proteins are ligands for RAGE (receptor for AGE) that activate cell signalling pathways and modulate gene expression - Kislinger, Thomas; Fu, Caifeng; Huber, Birgit; Qu, Wu; Taguchi, Akihiko; Yan, Shi Du; Hofmann, Marion A.; Yan, Shi Fang; Pischetsrieder, Monika; Stern, David M.; Schmidt, Ann Marie (Journal of Biological Chemistry, 1999)
Recent studies suggested that interruption of the interaction of advanced glycation end products (AGEs), with the signal-transducing receptor receptor for AGE (RAGE), by  administration of the soluble, extracellular ligand-binding domain of RAGE, reversed vascular hyperpermeability and suppressed accelerated atherosclerosis in diabetic rodents. Since the precise molecular target of soluble RAGE in those settings was not elucidated, we tested the hypothesis that predominant specific AGEs within the tissues in disorders such as diabetes and renal failure, Ne-(carboxymethyl)lysine (CML) adducts, are ligands of RAGE. We demonstrate here that physiologically relevant CML modifications of proteins engage cellular RAGE, thereby activating key cell signaling pathways such as NF-kB and modulating gene expression. Thus, CML-RAGE interaction triggers processes intimately linked to accelerated vascular and inflammatory complications that typify disorders in which inflammation is an established component.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.ncarbo

Neue Aspekte im Lebensmittelhygienerecht: Die Verordnung (EG) Nr. 852/2004 über Lebensmittelhygiene - neue Vorschriften für die Produktion von Lebensmitteln? - Bronowicka, Agneta; Laechelin, J.; Pischetsrieder, Monika; Franke, Peter (Deutsche Lebensmittel-Rundschau, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.llmch.neueas

Neue Sorgfaltspflichten für Unternehmen des Agrarund Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Wieck, Christine; Spiller, Achim; Nieberg, Hiltrud; Rudloff, Bettina; Iweala, Sarah; Balmann, Alfons; Balmann, Alfons; Birner, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; et al. (Berichte Uber Landwirtschaft, 2023)
Nachhaltigkeitsfragen in der Agrar- und Ernährungswirtschaft haben in den letzten Jahrzehnten an Bedeutung gewonnen. Neben vielfältigen Umweltproblemen rücken für agrarwirtschaftliche Lieferketten immer stärker auch Menschenrechtsprobleme in den Fokus der Diskussion. Unternehmen stehen zunehmend in der Verantwortung, Beiträge zur Erreichung von Nachhaltigkeitszielen zu leisten. Diese Verpflichtung galt bisher im Wesentlichen nur für den Geschäftsbereich des jeweiligen Unternehmens. Die Verantwortung für das Handeln der Lieferanten, erst recht für das Handeln von mittelbaren Lieferanten auf den Vorstufen der Wertschöpfungskette, war bisher selten Thema des Unternehmensmanagements und rechtlich nicht vorgesehen. Deshalb sind die im Gutachten diskutierten Lieferkettensorgfaltspflichtenregelungen ein Paradigmenwechsel für die Unternehmen. Sorgfaltspflichten ergeben sich insbesondere aus dem Anfang 2023 in Kraft getretenen deutschen Lieferkettensorgfaltspflichtengesetz (LkSG) und der im Sommer 2023 in Kraft getretenen EU-Verordnung für entwaldungsfreie Lieferketten (EUDR). Derzeit wird in der EU der Richtlinienvorschlag zur allgemeinen Sorgfaltspflicht (CSDDD) verhandelt. Dieser geht im Hinblick auf Sorgfaltspflichten zum Umwelt- und Klimaschutz, durch Einführung einer zivilrechtlichen Haftung und auch durch die Zahl der einbezogenen Unternehmen über das LkSG hinaus. Im vorliegenden Gutachten werden die Sorgfaltspflichtenregelungen, die ein weitgehend neues Politikinstrument darstellen, mit Fokus auf den Agrar- und Ernährungssektor untersucht. Die Schlussfolgerungen und viele der Empfehlungen dürften sich auf andere Wirtschaftssektoren übertragen lassen. Zu berücksichtigen ist, dass bisher nur begrenzte Erfahrungen über die konkrete Umsetzung der bereits beschlossenen Sorgfaltspflichtenregelungen vorliegen und die CSDDD sich noch im Gesetzgebungsverfahren befindet. Eine zentrale Schlussfolgerung des Beirats ist: Der WBAE begrüßt grundsätzlich die Gesetzgebung zu Sorgfaltspflichten von Unternehmen, mahnt aber auch eine auf Wirksamkeit und Effizienz ausgerichtete Ausgestaltung und Umsetzung der Regelungen für alle Beteiligten an. Dafür hält der WBAE einen intensiven Dialog mit den internationalen Handelspartnern, insbesondere den LMIC (low and middle income countries), sowie die Bereitstellung von Unterstützungsmaßnahmen für erforderlich. Darauf aufbauend kommt der WBAE zu den folgenden spezifischen Schlussfolgerungen: • Der Aufbau von Risikomanagementsystemen zur Einhaltung grundlegender Arbeitsschutz- und Menschenrechte in den von den Sorgfaltspflichtengesetzen direkt betroffenen Unternehmen ist sinnvoll. Die direkten Kosten sind vergleichsweise überschaubar, da Unternehmen der Agrar- und Ernährungswirtschaft schon viel Erfahrung mit Qualitätssicherungssystemen in komplexen Wertschöpfungsketten haben. Es können aber auch Kosten bei den Vorlieferanten und durch nicht-intendierte Effekte entstehen: Einige Unternehmen könnten deshalb eher einen Rückzug aus Gebieten oder Wirtschaftsbereichen mit schwierigen menschenrechtlichen Situationen („cut and run”) bzw. andere Umgehungsstrategien wählen, statt in die Entwicklung ihrer Lieferanten zu investieren. Zertifizierungssysteme könnten eine wesentliche Rolle in der effizienten und effektiven Umsetzung spielen, weisen aber derzeit noch größere Schwachstellen auf. • In juristischer Hinsicht wird die Steuerungswirkung des LkSG durch das Fehlen einer Haftungsregelung begrenzt; ein zweites Problem liegt bei dem notwendigen Nachweis des Verschuldens. Einzelne, von Verstößen gegen Sorgfaltspflichten Geschädigte werden häufig nicht in der Lage sein, entsprechende Beweise vorzulegen. Deshalb wird es zentral auf die Behörden der Handelspartnerländer und auf Gewerkschaften sowie zivilgesellschaftliche Organisationen ankommen, wenn nicht noch im weiteren Gesetzgebungsprozess eine Beweislastumkehr vorgesehen wird. Der Entwurf der CSDDD sieht eine zivilrechtliche Haftung mit Anspruch auf Schadensersatz vor. Unternehmen sollten sich vor der Haftung weitgehend durch vertragliche Zusicherungen und Zertifizierung schützen können („safe harbour”). Hier fehlt es bislang an einer Konkretisierung, welche Systeme dafür geeignet sein könnten. • Wirksamkeit und Effizienz der Sorgfaltspflichtenregelungen hängen wesentlich von der konkreten Ausgestaltung der Umsetzung und Kontrolle ab. Hierbei kommt abgestimmten Schnittstellen von Unternehmen und Behörden eine besondere Bedeutung zu. Da die Sorgfaltspflichtenregelungen ein neues Instrument darstellen, sind zudem Unterstützungsangebote für Unternehmen sowie ein Monitoring und eine Wirkungsüberprüfung der Gesetze notwendig, um Probleme frühzeitig zu erkennen und ggfs. Anpassungen vornehmen zu können. • Auf europäischer Ebene gibt es zusätzlich zu den Vorhaben zu Sorgfaltspflichten eine Vielzahl weiterer Regulierungen aus den Bereichen Handels- und Investitions- sowie Umwelt- und Agrarpolitik, die unterschiedliche Instrumente zur Verbesserung der Nachhaltigkeit nutzen. Es bestehen dabei Unterschiede nicht nur zwischen den unterschiedlichen Ansätzen für Sorgfaltspflichten, sondern auch zwischen Sorgfaltspflichten und anderen Regulierungsansätzen, was Risiken für die Zielerreichung und die Akzeptanz sowie hohe Umsetzungskosten mit sich bringt. Dies erschwert die Umsetzung und wirft Fragen bezüglich der Auswahl des richtigen Policy-Mixes auf. Die unternehmensbezogenen Sorgfaltsplichten ergänzen – aber ersetzen nicht – die zwischen Staaten vereinbarten Handels- und Investitionsschutzabkommen. • Aufgrund des hohen Internationalisierungsgrades der Agrar- und Ernährungswirtschaft, der schon jetzt weiten Verbreitung von Qualitätsstandards und der Erfahrungen mit vielen Arten von nicht-tarifären Handelsmaßnahmen kann es sein, dass die negativen Auswirkungen von Sorgfaltspflichtenregelungen auf Handelsvolumen und -partner geringer sein werden, als häufig vermutet wird. Mit fortschreitender globaler Normendiffusion würden sich auch Verdrängungs- und Verlagerungseffekte verringern. Die Resilienz von Agrarlieferketten wird durch die Sorgfaltspflichten auf der einen Seite unterstützt, z.B. indem die Verbindung der Partner gefördert und zum Lernen ermutigt wird, auf der anderen Seite könnte sich jedoch auch die Anzahl der Handelspartner reduzieren, was einen gegenläufigen Effekt hätte. Die Gefahr von Marktspaltungen ist real, jedoch hängt dies stark von der Angebots- und Nachfragesituation ab, die für die einzelnen Produkte sehr unterschiedlich sein kann. • Sorgfaltspflichten stellen ein unilaterales Vorgehen Deutschlands bzw. der EU dar. Die Wahl des unilateralen Vorgehens trotz multilateraler Möglichkeiten und die extraterritoriale Wirkung der Sorgfaltspflichten, ohne dass die Handelspartner während der Erarbeitung der Gesetze konsultiert wurden, ist kritisch zu betrachten. Für die Erreichung der Ziele der Sorgfaltspflichtenregelungen, wie den Schutz von Arbeits- und Menschenrechten entlang von internationalen Lieferketten, ist die Zusammenarbeit mit den Regierungen der Handelspartnerländer erforderlich. Gerade vor dem Hintergrund der kolonialen Vergangenheit Europas sind eine Partnerschaftsorientierung und die Einbeziehung von Erfahrungswissen der lokalen Stakeholder auf Seiten der Handelspartnerländer für die Ausgestaltung wichtig. Entsprechend bedarf es u.a. einer Förderung von eigenen Ansätzen der Handelspartner für eine Verbesserung der Situation vor Ort, einer Zusammenarbeit mit Handelspartnern beim Monitoring und bei der Überprüfung der Wirkung der Gesetze sowie ernsthafter Anstrengungen für multilaterale Ansätze. • Löhne und unternehmerische Einkommen, die kein existenzsicherndes Niveau erreichen, stellen ein grundlegendes Problem dar und bedingen viele der aufgezeigten Menschen- und Arbeitsrechtsrisiken in agrarischen Wertschöpfungsketten. Daher sollte die Einhaltung von Mindestlöhnen ein zentraler Bestandteil der Sorgfaltspflichtenregelungen sein, was auch eine positive Wirkung auf die Ernährungssicherung haben könnte. Angemessene Mindestlöhne tragen maßgeblich zur Verwirklichung des Rechts auf Nahrung bei. • Die Verankerung von Umwelt- und Klimazielen in den Lieferkettensorgfaltspflichten (CSDDD) stößt derzeit noch an erhebliche Grenzen und sollte deshalb nur schrittweise umgesetzt werden, sobald die dafür notwendigen Mess- und Monitoringsysteme vorliegen. • Für eine Einbindung zusätzlicher Ziele, wie existenzsichernde Einkommen, Gendergerechtigkeit oder Klima- und Biodiversitätsschutz, in die Sorgfaltspflichtenregeln ist es notwendig, die Handelspartner einzubeziehen und durch Konkretisierung aus programmatischen Zielen messbare unternehmerische Sorgfaltspflichten zu entwickeln. Auch für die Erreichung dieser Ziele ist allerdings ein Policy-Mix mit kohärenter Instrumentenabstimmung nötig. Sorgfaltspflichtenregelungen für Unternehmen entbinden die Staaten nicht von der Verpflichtung, sich weiterhin mit den ihnen zur Verfügung stehenden politischen Instrumenten zur Erreichung von Nachhaltigkeitszielen einzusetzen. Die folgenden Empfehlungen sollen einen Beitrag zu einer effektiven und effizienten Umsetzung leisten und verhindern, dass Sorgfaltspflichten bei zu starker Fokussierung auf wirkungslose Formalien zu “Bürokratiemonstern” werden. Dies soll auch dazu beitragen, dass Unternehmen sich für positive Entwicklungen bei ihren Lieferanten einsetzen, statt sich aus Risikogebieten/-sektoren zurückzuziehen. Gleichzeitig betonen die Empfehlungen vor dem Hintergrund der aktuellen Herausforderungen des geopolitischen Umfelds der EU die Bedeutung eines partnerschaftlichen Ansatzes in der Zusammenarbeit mit LMIC. Insgesamt unterstützt der WBAE die Einführung von gesetzlichen Sorgfaltspflichten in Lieferketten und empfiehlt deren schrittweisen Ausbau als lernendes System. Er fordert alle beteiligten Akteure aus Wirtschaft, Politik und Zivilgesellschaft auf, sich dafür einzusetzen, dass eine echte Verbesserung der Situation der Menschen im Agrar- und Ernährungssektor stattfindet und dass somit die Sorgfaltspflichtenregelungen ein Erfolg für Menschen- und Arbeitsrechte, Umwelt- und Klimaziele werden.<br
CRIS-Team Scopus Importer:2024-12-16

Non-homeostatic intake of snack foods: Molecular triggers and effects on brain activity pattern - Hoch, Tobias; Heß, Andreas; Pischetsrieder, Monika (The Chemical Sensory Informatics of Food: Measurement, Analysis, Integration, 2015)
Craving for special types of food like snack food can tremendously influence our energy balance. The result: obesity due to a non-homeostatic, hedonic food intake, i.e. an intake of energy independent of hunger and satiety. The intake of potato chips – an often craved highly palatable snack food – has a great influence on whole brain activity pattern. Especially the reward system as well as circuits regulating food intake, sleep and locomotor activity are affected. Furthermore, we could show that the fat and carbohydrate content is a main contributor to the palatability of potato chips. These first steps of the identification of the molecular triggers and the corresponding effects on brain activity pattern of the non-homeostatic intake of highly palatable snack food are reviewed in this chapter.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.nonhom

Novel milk-clotting enzyme from sour orange flowers (Citrus aurantium L.) as a coagulant in Iranian white cheese - Nasiri, Elham; Hesari, Javad; Shekarforoush, Seyed Shahram; Azadmard Damirchi, Sodeif; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (European Food Research and Technology, 2020)
The aim of this work was to evaluate the partially purified protease of sour orange flower extract (OFR) by determining the protein profile and milk-clotting activity as well as chemical and sensory characteristics of cheese throughout 45 days of ripening. Three rennets were used to produce cheeses, (1) the sour orange flower rennet at a level of 0.2 g/L milk (OFR), (2) standard calf rennet at a level of 0.02 g/L milk (CR), and (3) OFR (0.1 g/L)/CR (0.01 g/L). OFR cheese acidity was higher compared to that of the calf rennet (CR) and OFR/CR (50:50) samples. Significantly (p < 0.05) higher proteolytic activity was observed in OFR cheese through measuring the soluble nitrogen (SN), non-protein nitrogen (NPN), and total free amino acids (FAA) content. Protein profiles of cheeses determined with SDS-PAGE also confirmed higher levels of casein hydrolysis in OFR cheese. Reversed-phase high-performance liquid chromatography revealed the noticeable qualitative and quantitative differences between peptide profiles of all treatments. Higher casein degradation and production of peptide plus amino acids in OFR and OFR/CR cheeses suggested faster and more intensive ripening. The flavor and texture acceptance scores were reduced on the last day of storage in OFR cheese, while OFR/CR cheese received the highest score for flavor. In conclusion, the blend of OFR/CR may be regarded as an alternative for calf rennet in white brined cheese production which accelerates ripening process and causes development of a unique flavor in the final product.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Protease; Ripening; Sour orange flowers; White brined cheese

Nuclear translocation of NF-kappaB in intact human gut tissue upon stimulation with coffee and roasting products - Sauer, Tanja; Raithel, Martin; Kressel, Jürgen; Muscat, Sonja; Münch, Gerald; Pischetsrieder, Monika (Food and Function, 2011)
In the healthy gut, NF-kB is a critical factor of the intestinal immune system, whereas inflammatory bowel diseases are associated with chronic activation of NF-kB. Previous studies indicated that coffee induces nuclear translocation of NF-kB in macrophages, an effect attributed to roasting products. In the present work, coffee extract or roasting products induced nuclear translocation of NF-kB in macrophages, Caco-2 cells, and primary human intestinal microvascular endothelial cells (up to fivefold, p < 0.001). Since the effect clearly depended on the cell type, ex vivo experiments were performed with intact human gut tissue from biopsies. The uniformity of the specimens and tissue viability during ex vivo incubation for up to 2 h were verified. Roasting products led to a concentration dependent significant increase of nuclear translocation of NF-kB in human gut tissue (up to 2.85 fold increase, p ¼ 0.0321), whereas coffee extract induced a trend towards higher nuclear NF-kB concentration. NF-kB activation in macrophages and Caco-2 cells by roasting products was significantly blocked by co-incubation with catalase (p=0.011 and p=0.024) indicating involvement of H2O2-signaling. Monitoring of extracellular H2O2 indicated that roasting products in coffee constantly generate H2O2 by spontaneous oxygen reduction, which is only partially detoxified by cellular antioxidative systems. Thus, it can be concluded that ex vivo stimulation of intact human gut tissue is a valuable model to study nutritional effects on complex tissue systems. Furthermore, the consumption of coffee and roasting products may be able to induce nuclear NF-kB translocation in the human gut.
UnivIS-Import:2015-04-14:Pub.2011.nat.dchph.llmch.nuclea

On-line haemodiafiltration versus haemodialysis: stable haematocrit with less erythropoietin and improvement of other relevant blood parameters - Vaslaki, Lajos; Major, Lajos; Berta, Klara; Karatson, Andras; Misz, Mihay; Pethoe, Ferenc; Ladanyi, Erzebet; Fodor, Bertalan; Stein, Günter; Pischetsrieder, Monika; Zima, Thomas; Wojke, Ralf; et al. (Blood Purification, 2006)
Background: Controlled randomised studies to prove improved cardiovascular stability and improved anaemia management during on-line haemodiafiltration (oHDF) are scarce. Methods: 70 patients were treated with both haemodialysis (HD) and oHDF in a cross-over design during 2 x 24 weeks at a dialysis dose of eKt/ V ≥ 1.2. Patients randomised into group A started on HD and switched over to oHDF, whereas patients in group B began with oHDF and were treated with HD afterwards. Intradialytic morbid events (IME), such as symptomatic hypotension or muscle cramps, were noted in case of appearance. Blood parameters reflecting anaemic status, phosphate status, lipid metabolism, oxidative stress, and accumulation of advanced glycation end products were recorded either monthly or at the end of each study phase. Results: The mean incidence of IME was 0.15 IME per treatment, and there was no statistical difference between oHDF and HD. A higher haematocrit (oHDF 31.5% vs. HD 30.5%, p < 0.01) at a lower erythropoietin dose (oHDF 4,913 vs. HD 5,492 IU/week, p = 0.02) was found during oHDF, when the sequence of HD and oHDF had not been taken into account. For the study groups, the results were less distinct: in group A, a higher haematocrit (HD 30.4% vs. oHDF 32.0%, p < 0.01) at a comparable erythropoietin dose (HD 5,421 vs. oHDF 5,187 IU/week, ns) was observed during oHDF, whereas in group B an identical haematocrit (oHDF 30.8% vs. HD 30.7%, ns) was achieved at a reduced erythropoietin dose (oHDF 4,622 vs. HD 5,568 IU/week, p < 0.01). During oHDF, lower levels of free and protein-bound pentosidine and of serum phosphate were found. Conclusion: In contrast to other studies, no benefit regarding cardiovascular stability for oHDF was found, but oHDF could well offer a potential benefit regarding anaemia correction, inflammation, oxidative stress, lipid profiles, and calcium-phosphate product. Copyright © 2006 S. Karger AG.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.llmch.online
Keywords: Anaemia; Erythropoietin; Haematocrit; Haemodialysis; oHDF and high-flux HD; comparison; On-line haemodiafiltration; Pentosidine; Phosphate

On the reaction of L-ascorbic acid with propylamine under various conditions: quantification of the main products by HPLC/DAD - Larisch, Bernd; Groß, Ursula; Pischetsrieder, Monika (European Food Research and Technology, 1998)
The reaction of L-ascorbic acid (AA) with proteins (protein ascorbylation) has a considerable impact on food processing and health. So far four products have been isolated and identified which can be formed from AA and lysine derivatives. Thus, 2-deoxy-2-(propylamino)ascorbic acid, 3-deoxy-3-(propylamino) ascorbic acid, oxalic acid monopropylamide and oxalic acid dipropylamide were synthesized and an HPLC system for their separation and quantification was developed. Then, mixtures of AA and propylamine, as a model compound for lysine derivatives, were reacted under various conditions and product yields were determined in relation to reaction time, temperature, amine concentration and pH value. The results were discussed in detail and can help to evaluate the contribution of the four products to protein and lysine ascorbylation under different conditions. © Springer-Verlag 1998.
UnivIS-Import:2015-03-05:Pub.1998.nat.dchph.llmch.onther
Keywords: HPLC/DAD; L-Ascorbic acid; Maillard reaction; Product quantification

Peptide profiling of bovine kefir reveals 236 unique peptides released from caseins during its production by starter culture and kefir grains - Ebner, Jennifer; Asci Arslan, Ayse; Fedorova, Maria; Hoffmann, Ralf; Kücükcetin, Ahmet; Pischetsrieder, Monika (Journal of Proteomics, 2015)
Kefir has a long tradition in human nutrition due to its presupposed health promoting effects. To investigate the potential contribution of bioactive peptides to the physiological effects of kefir, comprehensive analysis of the peptide profile was performed by nano-ESI-LTQ-Orbitrap MS coupled to nano-ultrahigh-performance liquid chromatography. Thus, 257 peptides were identified, mainly released from β-casein, followed by αS1-, κ-, and αS2-casein. Most (236) peptides were uniquely detected in kefir, but not in raw milk indicating that the fermentation step does not only increase the proteolytic activity 1.7- to 2.4-fold compared to unfermented milk, but also alters the composition of the peptide fraction. The influence of the microflora was determined by analyzing kefir produced from traditional kefir grains or commercial starter culture. Kefir from starter culture featured 230 peptide sequences and showed a significantly, 1.4-fold higher proteolytic activity than kefir from kefir grains with 127 peptides. A match of 97 peptides in both varieties indicates the presence of a typical kefir peptide profile that is not influenced by the individual composition of the microflora. Sixteen of the newly identified peptides were previously described as bioactive, including angiotensin-converting enzyme (ACE)-inhibitory, antimicrobial, immunomodulating, opioid, mineral binding, antioxidant, and antithrombotic effects. Biological significance: The present study describes a comprehensive peptide profile of kefir comprising 257 sequences. The peptide list was used to identify 16 bioactive peptides with ACE-inhibitory, antioxidant, antithrombotic, mineral binding, antimicrobial, immunomodulating and opioid activity in kefir. Furthermore, it was shown that a majority of the kefir peptides were not endogenously present in the raw material milk, but were released from milk caseins by proteases of the microbiota and are therefore specific for the product. Consequently, the proteolytic activity and the composition of the peptide profile can be controlled by the applied microflora (grains or starter culture). On the other hand, a considerable portion of the peptide profile was identified to be typical for kefir in general and independent from production parameters.In summary, the generated kefir peptide profile helped to reveal its origin and to identify bioactive peptides in kefir, which may advance the understanding of health benefits of this food product. The results further indicate that subsets of the kefir peptide list can be used as markers to control food authenticity, for example, to distinguish different types of kefir.
UnivIS-Import:2015-03-09:Pub.2015.nat.dchph.llmch.peptid
Keywords: Bioactive peptides; Caseins; Kefir; Nano-ESI-LTQ-Orbitrap MS; Peptide profiling; Starter culture

Peptidomics in Food - Dalabasmaz, Sevim; Pischetsrieder, Monika (Comprehensive Foodomics, 2020)
Peptides are important food components with bioactive properties (including, e.g., antimicrobial, antioxidative, ACE-inhibitory or anticariogenic effects) and technological function. By now, targeted and untargeted mass spectrometry, mainly MALDI-TOF-MS and LC–ESI-high resolution MS/MS, allow for the comprehensive analysis of the peptide composition in food. Food peptidomics or food peptide profiling are crucial techniques to identify and quantify bioactive peptides in food and to understand the influence of peptides on food quality. Bioinformatic tools facilitate linking peptide structures and functions. Additionally, peptide profiles can complement the analytical toolbox to assure food authenticit
Keywords: ACE-Inhibitory activity; Antimicrobial activity; Antioxidative activity; Bioactive peptides; Food authentication; LC–MS/MS; MALDI-TOF-MS; Milk products; Peptide databases; Peptide profile; Peptidomics; Phosphopeptides; Quantification. Targeted analysis Untargeted analysis

Perturbed development of striatal dopamine transporters in fatty versus lean Zucker rats: a follow-up small animal PET study - Cumming, Paul; Maschauer, Simone; Riss, Patrick; Grill, Eva; Pischetsrieder, Monika; Kuwert, Torsten; Prante, Olaf (Molecular Imaging and Biology, 2015)
Purpose: Post-synaptic dopamine D2/3 receptors are reduced in animal models of obesity, and in obese humans, concordant with similar findings in habitual drug users. However, corresponding pre-synaptic changes in brain dopamine are less documented in obesity models. Therefore, we used positron emission tomography (PET) with the dopamine transporter (DAT) ligand N-(3-[18F]fluoropropyl)-2-β-carbomethoxy-3-β-(4′-methylphenyl) tropane ([18F]FP-CMT) to test the hypothesis that DAT availability is attenuated in adult fatty Zucker (FZ) rats versus lean littermates (LZ).
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.llmch.pertub
Keywords: Dopamine transporters; DAT; Positron emission tomography; Striatum; Obesity; Zucker rats

Phosphoglucose isomerase deficiency in Escherichia coli K-12 is associated with increased spontaneous mutation rate - Boteva, Elitsa; Handzhiyski, Yordan; Kotseva, Maria; Datsenko, Kirill A.; Wanner, Barry L.; Pischetsrieder, Monika; Mironova, Roumyana (Advances in Microbiology, 2018)
Phosphoglucose isomerase (PGI) is a key enzyme in early glycolysis, which catalyzes the reversible isomerization of glucose 6-phosphate (G6Ph) to fructose 6-phosphate. We have constructed an Escherichia coli K12 strain with a deleted pgi gene (Δpgi ) and shown that this strain in comparison with the parental strain 1) accumulates higher amount of G6Ph, 2) grows slowly, and 3) exhibits higher spontaneous mutation frequency to rifampicin resistance (Rifr), when grown on high glucose minimal medium. Intriguingly, the spontaneous mutation rate to Rifr was inversely related to the degree of E. coli chromosomal DNA modification with sugar derivatives. We measured higher concentrations of Amadori products, fluorophores (360 nm excitation/440 nm emission) and carboxymethyl residues in the chromosomal DNA of the E. coli parental strain than in DNA of the isogenic Δpgi strain. To explain this apparent paradox we hypothesized that PGI might be implicated in repair of G6Ph-derived lesions in DNA. In favor of our hypothesis, we further demonstrate that protein extract from the E. coli PGI proficient strain but not from the PGI deficient strain catalyzes the release of G6Ph from G6Ph-modified single stranded DNA oligonucleotide and from its hybrid duplex with a complementary peptide nucleic acid.<br
Keywords: Phosphoglucose isomerase; Glucose 6-phosphate; E. coli; Mutations; DNA repair

Phosphoproteomic Analysis of Dopamine D2 Receptor Signaling Reveals Interplay of G Protein- and β-Arrestin-Mediated Effects - Wenk, Deborah; Khan, Shahbaz; Ignatchenko, Vladimir; Hübner, Harald; Gmeiner, Peter; Weikert, Dorothée; Pischetsrieder, Monika; Kislinger, Thomas (Journal of Proteome Research, 2023)
Leveraging biased signaling of G protein-coupled receptors has been proposed as a promising strategy for the development of drugs with higher specificity. However, the consequences of selectively targeting G protein- or β-arrestin-mediated signaling on cellular functions are not comprehensively understood. In this study, we utilized phosphoproteomics to gain a systematic overview of signaling induced by the four biased and balanced dopamine D2 receptor (D2R) ligands MS308, BM138, quinpirole, and sulpiride in an in vitro D2R transfection model. Quantification of 14,160 phosphosites revealed a low impact of the partial G protein agonist MS308 on cellular protein phosphorylation, as well as surprising similarities between the balanced agonist quinpirole and the inverse agonist sulpiride. Analysis of the temporal profiles of ligand-induced phosphorylation events showed a transient impact of the G protein-selective agonist MS308, whereas the β-arrestin-preferring agonist BM138 elicited a delayed, but more pronounced response. Functional enrichment analysis of ligand-impacted phosphoproteins and treatment-linked kinases confirmed multiple known functions of D2R signaling while also revealing novel effects, for example of MS308 on sterol regulatory element-binding protein-related gene expression. All raw data were deposited in MassIVE (MSV000089457).
CRIS-Team Scopus Importer:2023-01-20
Keywords: biased signaling; dopamine D2 receptor; functional selectivity; G protein; GPCRs; phosphoproteomics; proteome analysis; quinpirole; sulpiride; β-arrestin

Pilot study on the naphthalene exposure of German adults and children by means of urinary 1- and 2-naphthol levels - Preuß, Ralf; Koch, Holger; Wilhelm, Michael; Pischetsrieder, Monika; Angerer, Jürgen (International Journal of Hygiene and Environmental Health, 2004)
Concentrations of 1- and 2-naphthol were measured in urine of 72 adults and 35 young children from Germany to assess the internal exposure to naphthalene of the general population. Naphthols could be detected in more than 90% of the urine samples. Levels of naphthols (sum of 1- and 2-naphthol) were 4-fold higher in smokers (median: 37.6 μg/g creatinine) compared to non-smoking adults (8.2 μg/g creatinine). On a creatinine basis young children had slightly lower naphthol levels in urine compared with adults (7.5 μg/g creatinine). Preliminary reference values for the sum of 1- and 2-naphthol in urine as means of the 95th percentile are proposed: 41.2 μg/g creatinine (non-smoking adults) and 23.5 μg/g creatinine (young children). It is concluded that 1- and 2-naphthol levels in urine are suitable for human biomonitoring of the naphthalene exposure in environmental medicine.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.pilots
Keywords: Adults; Biological monitoring; Children; Environmental medicine; Metabolites; Naphthalene; Naphthol; Urine

Pomegranate (Punica granatum L,) wine polyphenols affect Nrf2 activation and antioxidant enzyme expression in human neuroblastoma cells (SH-SY5Y) - Li, Xuan; Liu, Linwei; Pischetsrieder, Monika (Journal of Functional Foods, 2017)
Pomegranate (Punica granatum L.) phenolic compounds may prevent oxidative stress-induced neurodegenerative diseases. The present study investigated cytoprotective effects of pomegranate wine extracts and their phenolic compounds in neuroblastoma cells SH-SY5Y. The extracts significantly activated nuclear factor erythroid 2-related factor 2 (Nrf2; ≤2.6-fold) and inhibited nuclear factor κB (NF-κB) nuclear translocation (≥26% activity) without cytotoxic effects. Moreover, pomegranate wine extract time-dependently elevated heme oxygenase-1 (HO-1) expression (≤2.9-fold) and promoted superoxide dismutase (SOD) activity (≤1.4-fold), while it had no significant effect on glutathione peroxidase (GPx) activity. The main phenolic components of the extracts, gallic acid, ellagic acid, and punicalagin also led to a significant inhibition of NF-κB and the activation of Nrf2 translocation and subsequent increase of HO-1 expression and SOD activity, dependent on concentration and incubation time. Thus, pomegranate wine and its phenolic components may have a protective effect on neuronal cells by triggering Nrf2 and inhibiting NF-κB signaling.
Keywords: Pomegranate (Punica granatum L.); polyphenols; neuroblastoma cell; Nrf2; antioxidant enzyme

Potential DNA-protein cross-link products formed by sugar degradation products: identification of N6-[2-(N²-2'-deoxyguanosyl)propionyl]lysine - Peich, Carlo; Seidel, Wolfgang; Hanak, Nicole; Waibel, Reiner; Schneider, Marc; Pischetsrieder, Monika (European Food Research and Technology, 2005)
Sugar degradation products are formed during heat treatment of food as well as endogenously in vivo. As reactive carbonyl compounds, they react readily with proteins or DNA to form protein- or DNA-bound advanced glycation end products (glycation reaction or Maillard reaction). In this study, we investigated the formation of potential DNA-protein cross-link products from sugar degradation products. 2′-Deoxyguanosine, l-lysine and different carbohydrates were incubated at 37 °C. The sugar degradation products dihydroxyacetone and d,l-glyceraldehyde lead to the formation of two new cross-link products. The new compounds were isolated by preparative high-performance liquid chromatography and identified by spectral data as the two diastereomers of N 6-[2-(N 2-2′-deoxyguanosyl) propionyl]lysine. In this structure, the ε-amino group of lysine and the exocyclic amine group of 2′-deoxyguanosine are linked via a carboxyethyl group, derived from the carbohydrate component. The binding sites and the binding types were confirmed by synthesis of the analogous products from N 2-(1-carboxyethyl)guanosine and N α -acetyllysine methyl ester. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.potent
Keywords: 2′-Deoxyguanosine; Advanced glycation end products; Dihydroxyacetone; DNA-protein cross-link; Glyceraldehyde; N; Sugar degradation products

Prevalence and stability of lysozyme in cheese - Schneider, Nadine; Werkmeister, Knut; Becker, Cord-Michael; Pischetsrieder, Monika (Food Chemistry, 2011)
The use of the preservative and potential allergen hen egg white lysozyme in cheese production has to be declared. In the present study, an HPLC method with fluorescence detection (HPLC-FLD) was optimised and validated for the analysis of lysozyme in cheese. Lysozyme was detected in concentrations between 30.8 and 386.2 mg/kg cheese in 30 out of 46 analysed commercial cheese samples. During cheese production and storage for 0-54 weeks a lysozyme satellite peak (LSP) was detected, which totals up to 18% of the lysozyme content. Mass spectrometry and peptide mass fingerprint revealed that LSP possesses the same primary structure as lysozyme. Since disulphide scrambling could not be detected, LSP was assigned to a conformational isomer of lysozyme. As a consequence, LSP was included in the HPLC-FLD analysis of lysozymes in cheese. © 2011 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.preval
Keywords: Cheese; Fluorescence detection; Hen egg white lysozyme; HPLC; Lysozyme degradation

Profiles, antioxidative and ACE inhibitory activity of peptides released from fermented buttermilk before and after simulated gastrointestinal digestion - Magouz, Osama; Mehanna, Nabil; Khalifa, Mohamed; Sakr, Hanaa; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Pischetsrieder, Monika (Innovative Food Science & Emerging Technologies, 2023)
Bioactive peptides, released from buttermilk by fermentation and/or gastrointestinal proteases, may have health promoting effects. Thus, a comprehensive analysis of the peptide fraction of fermented buttermilk, before and after different phases of simulated gastrointestinal digestion, was performed using ultra high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/MS). Results showed that digestion simulation substantially changed the peptide profile of fermented buttermilk. A total of 81, 120 and 46 peptides were identified in fermented buttermilk, its gastric and intestinal digests, respectively. These peptides released mostly from β-casein followed by αs1-casein, κ-casein and β-lactoglobulin. In addition, 14 peptides released from milk fat globule membrane proteins (lactadherin, butyrophilin and GlyCAM-1). Bioactivity, mainly angiotensin converting enzyme (ACE) inhibitory activity, has been reported before for only 54 of the detected peptides. Radical scavenging, ferric reducing and ACE inhibitory activities of fermented buttermilk peptides increased significantly after digestion, indicating promotion in fermented buttermilk-peptide bioactivity by gastrointestinal digestion.<br

Profiling of antioxidative enzyme expression induced by various food components using targeted proteome analysis. - Bartenbacher, Sven; Östreicher, Christiane; Pischetsrieder, Monika (Molecular nutrition & food research, 2017)
SCOPE A method was developed for targeted proteome analysis of the expression profile of a set of antioxidative enzymes in rat macrophages and applied to screen the antioxidative potential of several food components/foods. METHODS AND RESULTS Expression profiles of heme oxygenase 1, peroxiredoxin 1, thioredoxin reductase 1, glutathione reductase, glutathione-S transferase P1, and superoxide dismutase 1 were analyzed by nanoLC-MS/MS in selected scheduled reaction monitoring (sSRM) mode monitoring 2-3 peptides per protein and 3 transitions per peptide. Relative quantification was performed by metabolic labeling. The validated method was used to profile the activity of capsaicin, carnosol, diallyl trisulfide, maslinic acid, quercetin, sulforaphane, cinnamaldehyde and coffee extract to modulate the expression levels of antioxidative enzymes. Carnosol and sulforaphane most effectively induced protein expression, leading to upregulation of at least 5 out of the 6 antioxidative enzymes by a maximum factor of 22.80±6.71 (heme oxygenase 1 by carnosol). Heme oxygenase 1 was most susceptible to nutritive modulation, whereas glutathione reductase expression rates were hardly affected. CONCLUSION Targeted mass proteome analysis allows comprehensive evaluation of antioxidative effects by food ingredients. Simultaneous expression analysis of a set of proteins provided valuable insights how various enzymes were differently affected by food components. This article is protected by copyright. All rights reserved.

Profiling of multiphosphorylated peptides in kefir and their release during simulated gastrointestinal digestion - Savastano, Maria Luisa; Liu, Yufang; Ebner, Jennifer; Dittrich, Daniel; Haus, Sabrina; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (ACS Omega, 2019)
Casein phosphopeptides are multiphosphorylated milk peptides, which can have anticariogenic activity and improve mineral absorption by binding bivalent metal ions. The present study investigated phosphopeptides in kefir, because fermentation may lead to their enhanced release from milk proteins. After selective enrichment by hydroxyapatite extraction, phosphopeptides and their phosphorylation degree were identified by MALDI-TOF-MS before and after enzymatic dephosphorylation. Peptide structures were determined by UHPLC–ESI–MS/MS revealing 27 phosphopeptides in kefir, including nine peptides containing the motif pSpSpSEE, which binds minerals most efficiently. The majority (18) of phosphopeptides derived from β-casein, but only three from the most abundant milk protein αs1-casein. After simulated gastrointestinal digestion, MALDI-TOF-MS analysis detected eight putative phosphopeptides in kefir; four of which were assigned by UHPLC–ESI–MS/MS to αs2-casein124-133, αs2-casein137-146, β-casein30-40, and κ-casein147-161. These results indicate that kefir is a good dietary source of multiphosphorylated peptide
Keywords: casein phosphopeptides; gastrointestinal digestion; kefir; MALDI-TOF-MS; pSpSpSEE; UHPLC–ESI–MS/MS

Proteome research in food science - Pischetsrieder, Monika; Bäuerlein, Rainer (Chemical Society Reviews, 2009)
The proteome is the totality of proteins present in a biological sample. In contrast to the static genome, the proteome is highly dynamic, influenced by the genome and many external factors, such as the state of development, tissue type, metabolic state, and various interactions. Thus, the proteome reflects very closely the biological (and chemical) processes occurring in a system. For proteome analysis, gel based and shotgun methods are most widely applied. Because of the potential to generate a systematic view of protein composition and biological as well as chemical interactions, the application of proteome analysis in food science is steadily growing. This tutorial review introduces several fields in food science, where proteomics has been successfully applied: analysis of food composition, safety assessment of genetically modified food, the search for marker proteins for food authentication, identification of food allergens, systematic analysis of the physiological activity of food, analysis of the effects of processing on food proteins and the improvement of food quality. © 2009 The Royal Society of Chemistry.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.proteo

Proteomic Response of Human Umbilical Vein Endothelial Cells to Histamine Stimulation - Emirbayer, Pelin Esma; Sinha, Ankit; Ignatchenko, Vladimir; Hoyer, Stefanie; Dörrie, Jan; Schaft, Niels; Pischetsrieder, Monika; Kislinger, Thomas (Proteomics, 2017)
The histamine receptors (HRs) represent a subclass of G protein-coupled receptors (GPCRs) and comprise four subtypes. Due to their numerous physiological and pathological effects, HRs are popular drug targets for the treatment of allergic reactions or the regulation of gastric acid secretion. Hence, an understanding of the functional selectivity of HR ligands has gained importance. These ligands can bind to specific GPCRs and selectively activate defined pathways. Supporting the activation of a therapeutically necessary pathway without the activation of other signaling cascades can result in drugs with more specific activity and fewer side effects. To evaluate the cellular consequences resulting from receptor binding, comprehensive analyses of cellular protein alterations upon incubation with ligands are required. For this purpose, endothelial cells are treated with histamine, as the endogenous ligand of HRs, to obtain a global overview of its cellular effects. Quantitative proteomics and pathway analyses of histamine-treated and untreated cells reveal enrichment of the nuclear factor-B and tumor necrosis factor signaling pathways, cytokine-cytokine receptor interactions, complement and coagulation cascades, and acute inflammatory processes upon histamine treatment. This strategy offers the opportunity to monitor HR-mediated signaling in a multidimensional manner.
Keywords: histamine; label-free quantification; parallel reaction monitoring; secretome; Shotgun proteomics

Pyrodixal phosphate prevents progression of diabetic nephropathy - Nakamura, Sakurako; Li, Hongyan; Adijiang, Ayinuer; Pischetsrieder, Monika; Niwa, Toshimitsu (Nephrology Dialysis Transplantation, 2007)
Background. We have demonstrated that pyridoxal 50-phosphate (PLP), an active form of vitamin B6, inhibits formation of advanced glycation end-products (AGEs) by trapping 3-deoxyglucosone. The present study aimed to clarify if PLP could exert beneficial effects on nephropathy in diabetic rats. Methods. Streptozotocin (STZ)-induced diabetic rats were treated by oral administration of PLP or pyridoxamine (PM), another active form of vitamin B6, at a dose of 600 mg/kg/day for 16 weeks. AGEs [imidazolone, Ne-(carboxymethyl)lysine (CML) and N2-carboxyethyl-20-deoxyguanosine (CEdG)], transforming growth factor-b1 (TGF-b1), type 1 collagen and fibronectin were detected in the kidneys using immunohistochemistry. Gene expression of TGF-b1 and receptor for AGEs (RAGEs) in the kidneys was determined using real-time quantitative polymerase chain reaction. Results. Administration of PLP significantly inhibited albuminuria, glomerular hypertrophy, mesangial expansion, and interstitial fibrosis as compared with diabetic rats. PLP markedly inhibited accumulation of AGEs such as imidazolone, CML and CEdG, a DNAlinked AGE, in glomeruli. PLP significantly inhibited expression of TGF-b1, type 1 collagen, fibronectin and RAGE in the kidneys. PLP was superior to PM in inhibiting accumulation of AGEs, expression of TGF-b1, type 1 collagen, and fibronectin, and the development of diabetic nephropathy. Conclusions. PLP prevented progression of nephropathy in STZ-induced diabetic rats by inhibiting formation of AGEs. PLP is considered a promising active form of vitamin B6 for the treatment of AGElinked disorders such as diabetic nephropathy.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.pyrodi
Keywords: advanced glycation end-products (AGEs); diabetic nephropathy; pyridoxal 50-phosphate (PLP); receptor for advanced glycation end-products (RAGE); transforming growth factor-b1 (TGF-b1)

Qualitative and Quantitative Profiling of Fructose Degradation Products Revealed the Formation of Thirteen Reactive Carbonyl Compounds and Higher Reactivity Compared to Glucose - Ohno, Reiichi; Auditore, Andrea; Gensberger-Reigl, Sabrina; Saller, Julia; Stützer, Joachim; Weigel, Ingrid; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2024)
Fructose occurs in foods and as a metabolite in vivo. It can be degraded, leading to the formation of reactive carbonyl compounds, which may influence food properties and have an impact on health. The present study performed an in-depth qualitative and quantitative profiling of fructose degradation products. Thus, the α-dicarbonyl compounds 3-deoxyglucosone, glucosone, methylglyoxal, glyoxal, hydroxypyruvaldehyde, threosone, 3-deoxythreosone, and 1-desoxypentosone and the monocarbonyl compounds formaldehyde, acetaldehyde, glycolaldehyde, glyceraldehyde, and dihydroxyacetone were detected in fructose solutions incubated at 37 °C. Quantitative profiling after 7 days revealed 4.6-271.6-fold higher yields of all degradation products from fructose compared to glucose. Except for 3-deoxyglucosone, the product formation appeared to be metal dependent, indicating oxidative pathways. CaCl2 and MgCl2 partially reduced fructose degradation. Due to its high reactivity compared to glucose, particularly toward metal-catalyzed pathways, fructose may be a strong contributor to sugar degradation and Maillard reaction in foods and in vivo.
CRIS-Team Scopus Importer:2024-09-06
Keywords: high-fructose corn syrup; honey; monocarbonyl compounds; reactive carbonyl compounds; ultrahigh-performance liquid chromatography−tandem mass spectrometry (UHPLC−MS/MS); α-dicarbonyl compounds

Qualitative Determination of Specific Protein Glycation Products by Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Peptide Mapping - Humeny, Andreas; Kislinger, Thomas; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2002)
The nonenzymatic reaction between reducing sugars and proteins, known as the Maillard reaction, has received increased recognition from nutritional science and medical research. The development of new analytical techniques for the detection of protein-bound Maillard products is therefore crucial. In this study, we applied peptide mapping by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to investigate the formation of structurally specific Maillard products on glycated lysozyme (AGE-lysozyme), produced upon incubation with D-glucose. In parallel, we synthesized Nε-(carboxymethyl)lysine-modified lysozyme (CML-lysozyme) and Nε-(carboxyethyl)lysine-modified lysozyme, two well-described glycation products, as model substances. 3-Deoxyglucosone-modified lysozyme and methylglyoxal-modified lysozyme were prepared as examples of glycation products incubated with dicarbonyl compounds. We were able to detect specific modifications on AGE-lysozyme, which were assigned to CML, imidazolone A, and the Amadori product.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.qualit
Keywords: Imidazolone A; Maillard reaction; MALDI-TOF-MS peptide mapping; N; Protein glycation

Qualitative Determination of the Early Maillard-Products by MALDITOF Mass Spectrometry Peptide Mapping - Kislinger, Thomas; Humeny, Andreas; Seeber, Silke; Peich, Carlo; Becker, Cord-Michael; Pischetsrieder, Monika (European Food Research and Technology, 2002)
Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) was used to qualitatively study the formation of early Maillard products of lysozyme, produced upon incubation with seven different sugars (D-ribose, L-rhamnose, D-glucose, D-fructose, D-galactose, D-lactose, D-maltose) in solution, in the presence of oxygen. MALDI-TOF mass spectra of intact lysozyme revealed a heterogeneous distribution of glycation products, detected by significant mass increase and peak broadening. Therefore, to get more detailed information about the nature of the glycation products, we performed MALDI-TOF MS peptide mapping analysis. In each of the peptide mapping spectra we were able to detect the early glycation products (Amadori products/glucosylamines) with high selectivity. We were able to distinguish between the Amadori products of the different sugars, due to the characteristic mass increases of the glycated peptides. Furthermore, variations of the modification pattern were observed, very likely due to the different relativities of the seven reducing sugars. Other, more advanced glycation products of the initially formed Maillard products were also detected. Further studies regarding the nature of these late Maillard products are in progress. Here we report, for the first time, the use of MALDI-TOF MS peptide mapping as a quick and highly selective method for the detection of early stage Maillard products produced upon incubation of lysozyme with seven different reducing sugars.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.qualit_2
Keywords: Maillard reaction; Amadori products; MALDI-TOF MS peptide mapping

Qualitative profiling of polyglucose degradation products in peritoneal dialysis fluids - Gensberger, Sabrina; Knabner, Carina; Waibel, Reiner; Huppert, Jochen; Pischetsrieder, Monika (Analytical Chemistry, 2015)
Heat sterilization of peritoneal dialysis (PD) fluids leads to partial degradation of the osmotic agent to form reactive carbonyl structures, which significantly reduce the biocompatibility of PD fluids and impair long-term PD therapy. Hence, it is important to know the exact composition of the degradation products to improve biocompatibility of PD fluids. Our study conducted targeted screening for degradation products in polyglucose (icodextrin)-containing PD fluids (pGDPs) by applying o-phenylenediamine (OPD) to form stable derivatives, which were analyzed by ultrahigh-performance liquid chromatography with hyphenated diode array tandem mass spectrometry (UHPLC−DAD−MS/MS). For the first time, specific degradation products of polyglucose, namely, 4-deoxyglucosone (4-DG) and 3,4-dideoxypentosone (3,4-DDPS), could be identified in PD fluids. Further, a reaction product of 5-hydroxymethylfurfural (5-HMF) and OPD could be characterized to be (5-(1H-benzo[d]imidazol-2-yl)furan-2-yl)methanol. Additionally, 3-deoxyglucosone (3-DG) and 3-deoxygalactosone (3-DGal), both known to be present in glucose-based PD fluids, were also detected in polyglucose-containing fluids. Trapping a hitherto unknown degradation product with OPD yielded 1,4-bis(1H-benzo[d]imidazol-2-yl)-3,4-dihydroxybutan-1-one, which was present in heat- as well as filter-sterilized PD fluids.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.qualit

Quantification of 24 circulating endocannabinoids, endocannabinoid-related compounds, and their phospholipid precursors in human plasma by UHPLC-MS/MS. - Röhrig, Waldemar; Achenbach, Susanne; Deutsch, Birgit; Pischetsrieder, Monika (Journal of Lipid Research, 2019)
Endocannabinoids and endocannabinoid-related compounds (ERCs) are involved in many physiological processes. They are released on demand from phosphoinositide and N-acylphosphatidyl ethanolamine (NAPE) precursors and comprise 2-monoacylglycerols (2-MGs) and FA ethanolamides (FEAs). Despite the abundance of advanced quantitative methods, however, their determined concentrations in blood plasma are inconsistent because 2-MGs and FEAs undergo artifactual de novo formation, chemical isomerization, and degradation during sample collection and storage. For a comprehensive survey of these compounds in blood and plasma, we have developed and validated an ultra-HPLC-MS/MS method to quantify 24 endocannabinoids, ERCs, and their phospholipid precursors. Immediate acidification of EDTA-blood to pH 5.8 blocked artifactual FEA formation for at least 4 h on ice. The 2-MGs were stabilized after plasma harvest with 0.5 M potassium thiocyanate at pH 4.7. FEA and MG plasma concentrations in six healthy volunteers ranged between 0.04-3.48 and 0.63-6.18 ng/ml, respectively. Interestingly, only 1-5% of circulating FEAs were present in their free form, while the majority was bound to NAPEs. Similarly, 97% of 2-arachidonoylglycerol (2-AG) was bound to a potential phosphoinositide pool. The herein-described stabilization and extraction methods may now be used to reliably and comprehensively quantify endocannabinoids, ERCs, and their phospholipid precursors in clinical studies.
Keywords: fatty acid ethanolamide; 2-arachidonoylglycerol; 2-monoacylglycerol; N-acylphosphatidyl ethanolamine; phosphatidyl ethanolamine; arachidonoyl phosphoinositid; Orlistat; blood; lipases; phospholipases

Quantification of co-, n-, and ad-lupulone in hop-based dietary supplements and phytopharmaceuticals and modulation of their contents by the extraction method - Schulz, Carolin; Chiheb, Chafia; Pischetsrieder, Monika (Journal of Pharmaceutical and Biomedical Analysis, 2019)
Hop β-bitter acids (lupulones) are health-beneficial components of Humulus lupulus L. showing, for example, antidepressant-like effects in vitro. Despite of the widespread use of hops for medicinal purposes, the concentrations of lupulones in hop-based drugs have not been reported yet. The present study developed, validated, and applied a method with external calibration, which allows for the first time separate quantification of co-, n-, and ad-lupulone in hop-based drugs by UHPLC‒DAD. Concentrations between ‘not detectable’ and 2.7 mg/mL co-lupulone, 2.2 mg/mL nlupulone, or 0.7 mg/mL ad-lupulone were measured in nine different commercial dietary supplements and phytopharmaceuticals. Only one hop tincture contained sufficient lupulone to possibly exert potential antidepressant effects. Aiming for products with increased lupulone content, the extraction efficiency of different solvents was investigated. Complete extraction of lupulones from raw hops was achieved by organic solvents including methanol and ethanol, whereas aqueous mixtures resulted in low recovery. These results indicate that adapted extraction conditions may result in more effective hops product
Keywords: β-bitter acids; dietary supplements; hops; lupulones; phytopharmaceuticals; UHPLC-DAD.

Quantification of reactive carbonyl compounds in icodextrin-based peritoneal dialysis fluids by combined UHPLC-DAD and -MS/MS detection - Gensberger-Reigl, Sabrina; Huppert, Jochen; Pischetsrieder, Monika (Journal of Pharmaceutical and Biomedical Analysis, 2016)
During heat sterilization of peritoneal dialysis (PD) fluids, the glucose component is partially degraded. The formed glucose degradation products impair biocompatibility and limit the long-term application of PD fluids. As an alternative to glucose, icodextrin, a polyglucose, is used as osmotic agent in PD fluids. After targeted screening for reactive carbonyl compounds, NMR- and MS-analyses very recently revealed 4-deoxyglucosone (4-DG), 3-deoxyglucosone (3-DG), 3-deoxygalactosone (3-DGal), 3,4-dideoxypentosone (3,4-DDPS), and 5-hydroxymethylfurfural (5-HMF) as main polyglucose degradation products (pGDPs) in icodextrin-based PD fluids. Now, the present study established and validated a UHPLC method with DAD as well as a UHPLC-MS/MS method for the first-time quantification of those five major pGDPs in commercial icodextrin PD fluids after derivatization with o-phenylenediamine. Thus, 4-DG was identified to be the main degradation product (in concentrations up to 20 mu M). In contrast to the values measured in glucose-based products, the concentration of 3-DGal (<= 16 mu M) was higher than the concentration of 3-DG (<= 7 mu M) indicating different reaction pathways starting from polyglucose compared to glucose. The compounds 3,4-DDPS and 5-HMF were present in minor quantities (<= 0.3 mu M each). (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Icodextrin; Polyglucose degradation products; 4-Deoxyglucosone (4-DG); alpha-Dicarbonyl compound; 3; 4-Dideoxypentosone (3; 4-DDPS); Peritoneal dialysis

Quantification of the six major alpha-dicarbonyl contaminants in peritoneal dialysis fluids by UHPLC/DAD/MSMS - Mittelmaier, Stefan; Fünfrocken, Michael; Fenn, Dominik; Berlich, Robert; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2011)
During heat sterilization of peritoneal dialysis solutions, glucose is partially transformed into glucose degradation products (GDPs), which significantly reduce the biocompatibility of these medicinal products. Targeted α-dicarbonyl screening identified glyoxal, methylglyoxal, 3-deoxyglucosone, 3,4-dideooxyglucosone-3-ene, glucosone, and 3-deoxygalactosone as the major six GDPs with α-dicarbonyl structure. In the present study, an ultra-high-performance liquid chromatography method was developed which allows the separation of all relevant α-dicarbonyl GDPs within a run time of 15 min after derivatization with o-phenylenediamine. Hyphenated diode array detection/tandem mass spectrometry detection provides very robust quantification and, at the same time, unequivocal peak confirmation. Systematic evaluation of the derivatization process resulted in an optimal derivatization period that provided maximal derivatization yield, minimal de novo formation (uncertainty range ±5%), and maximal sample throughput. The limit of detection of the method ranged from 0.13 to 0.19 μM and the limit of quantification from 0.40 to 0.57 μM. Relative standard deviations were below 5%, and recovery rates ranged between 91% and 154%, dependent on the type and concentration of the analyte (in 87 out of 90 samples, recovery rates were 100∈±∈ 15%). The method was then applied for the analysis of commercial peritoneal dialysis fluids (nine different product types, samples from three lots of each). [Figure not available: see fulltext.] © 2011 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2011.nat.dchph.llmch.quanti
Keywords: α-Dicarbonyl compounds; 3; 4-DGE; Glucose degradation products; Peritoneal dialysis fluids; Tandem mass spectrometry; UHPLC

Radical arylation of tyrosine residues in peptides - Fehler, Stefanie; Pratsch, Gerald; Östreicher, Christiane; Fürst, Michael; Pischetsrieder, Monika; Heinrich, Markus (Tetrahedron, 2016)
The radical arylation of the phenolic side chain of tyrosine in peptides was investigated. Aryl radicals were generated from aryldiazonium salts using titanium(III) chloride as stoichiometric reductant. Due to the high selectivity with which 3-aryltyrosine derivatives were formed, this reaction type represents a new strategy for the direct functionalization of peptides.
Keywords: Arylation; Diazonium; Peptide; Radical reaction; Tyrosine

Reaction of Ascorbic Acid with Aliphatic Amines - Pischetsrieder, Monika; Larisch, Bernd; Müller, Ursula; Severin, Theodor (Journal of Agricultural and Food Chemistry, 1995)
Ascorbic acid (1) reacts with propylamine or α-N-acetyllysine to afford N-substituted 3-deoxy-3-aminoascorbic acid of general structure 3.
UnivIS-Import:2015-03-05:Pub.1995.nat.dchph.llmch.reacti
Keywords: Aliphatic amines; Aminoreductones; Ascorbic acid

Reaction of folic acid with reducing sugars and sugar degradation products - Schneider, Marc; Klotzsche, Marcus; Werzinger, Christoph; Hegele, Jörg; Waibel, Reiner; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2002)
The reaction of folic acid with reducing sugars (nonenzymatic glycation) under conditions that can occur during food processing and preparation was studied by high-performance liquid chromatography with diode array detection. N-(p-Aminobenzoyl)-L-glutamic acid, a well-established oxidation product, was detected in the reaction mixtures. Furthermore, a new product was isolated and identified as N2-[1-(carboxyethyl)]folic acid (CEF). CEF was the main product that was formed by the nonenzymatic glycation of folic acid. For preparation, N2-[1-(carboxyethyl)]folic acid was obtained in high yields when folic acid and dihydroxyacetone (DHA), a sugar degradation product, were heated at 100°C in phosphate buffer. Mixtures of folic acid and different sugars or DHA were heated under variation of reaction time and temperature, and CEF was quantified. Up to 50% of the vitamin was converted to CEF, with highest yields formed from maltose (49%) and lactose (43%).
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.reacti
Keywords: Folate degradation; Folic acid; HPLC; Maillard reaction; N; Nonenzymatic glycation

Reaction of guanosine with glucose under oxidative conditions - Seidel, Wolfgang; Pischetsrieder, Monika (Bioorganic & Medicinal Chemistry Letters, 1998)
Incubation of glucose with guanosine under oxidative conditions at 37 °C or 70 °C leads to the formation of a main product, which can be detected by HPLC/DAD. The compound was isolated and identified as N2-carboxymethyl- guanosine (CMG). To confirm the structure, CMG was also synthesized from glyoxal and guanosine.
UnivIS-Import:2015-03-05:Pub.1998.nat.dchph.llmch.reacti

Reaction of L-Ascorbic Acid with L-Arginine Derivatives - Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 1996)
When L-ascorbic acid (AA) is heated in the presence of Nα-acetyl-L-arginine, a main product can be detected by HPLC/UV. The compound was isolated and identified by spectroscopic data and synthesis as Nα-acetyl-Aδ >;-(4-(1,2-dihydroxy-3-propyliden)-3-imidazolin-5-on-2-yl)-L- ornithine(DPI) (1a), An analogous derivative (1b) was obtained, starting from methylguanidine, a model compound for arginine. 1a is also formed from L-dehydroascorbic acid (DHA) and xylosone, degradation products of AA. The yield of 1a was investigated at different reaction temperatures, times, and pH-values.
UnivIS-Import:2015-03-05:Pub.1996.nat.dchph.llmch.reacti
Keywords: Ascorbic acid; L-arginine; Maillard reaction

Reactive dicarbonyl compounds cause Calcitonin Gene-Related Peptide release and synergize with inflammatory conditions in mouse skin and peritoneum - Becker, Anna; Auditore, Andrea; Pischetsrieder, Monika; Meßlinger, Karl; Fleming, Thomas; Reeh, Peter; Sauer, Susanne (Journal of Biological Chemistry, 2020)
The plasmas of diabetic or uremic patients and of those receiving peritoneal dialysis treatment have increased levels of the glucose-derived dicarbonyl metabolites like methylglyoxal (MGO), glyoxal (GO), and 3-deoxyglucosone (3-DG). The elevated dicarbonyl levels can contribute to the development of painful neuropathies. Here, we used stimulated immunoreactive Calcitonin Gene–Related Peptide (iCGRP) release as a measure of nociceptor activation, and we found that each dicarbonyl metabolite induces a concentration-, TRPA1-, and Ca2+-dependent iCGRP release. MGO, GO, and 3-DG were about equally potent in the millimolar range. We hypothesized that another dicarbonyl, 3,4-dideoxyglucosone-3-ene (3,4-DGE), which is present in peritoneal dialysis (PD) solutions after heat sterilization, activates nociceptors. We also showed that at body temperatures 3,4-DGE is formed from 3-DG and that concentrations of 3,4-DGE in the micromolar range effectively induced iCGRP release from isolated murine skin. In a novel preparation of the isolated parietal peritoneum PD fluid or 3,4-DGE alone, at concentrations found in PD solutions, stimulated iCGRP release. We also tested whether inflammatory tissue conditions synergize with dicarbonyls to induce iCGRP release from isolated skin. Application of MGO together with bradykinin or prostaglandin E2 resulted in an overadditive effect on iCGRP release, whereas MGO applied at a pH of 5.2 resulted in reduced release, probably due to an MGO-mediated inhibition of transient receptor potential (TRP) V1 receptors. These results indicate that several reactive dicarbonyls activate nociceptors and potentiate inflammatory mediators. Our findings underline the roles of dicarbonyls and TRPA1 receptors in causing pain during diabetes or renal disease.
CRIS-Team Scopus Importer:2020-05-26

Receptor for advanced glycation end products mediates inflammation and enhanced expression of tissue factor in vasculature of diabetic apolipoprotein E null mice - Kislinger, Thomas; Tanji, Nozomu; Wendt, Thoralf; Qu, Wu; Lu, Yan; Ferran, Luis J.; Taguchi, Akihiko; Olson, Kim; Bucciarelli, Loredana; Goova, Mouza; Hofmann, Marion A.; Cataldegirmen, Guellue; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2001)
Advanced glycation end products (AGEs) and their cell surface receptor, RAGE, have been implicated in the pathogenesis of diabetic complications. Here, we studied the role of RAGE and expression of its proinflammatory ligands, EN-RAGEs (S100/calgranulins), in inflammatory events mediating cellular activation in diabetic tissue. Apolipoprotein E-null mice were rendered diabetic with streptozotocin at 6 weeks of age. Compared with nondiabetic aortas and kidneys, diabetic aortas and kidneys displayed increased expression of RAGE, EN-RAGEs, and 2 key markers of vascular inflammation, vascular cell adhesion molecule (VCAM)-1 and tissue factor. Administration of soluble RAGE, the extracellular domain of the receptor, or vehicle to diabetic mice for 6 weeks suppressed levels of VCAM-1 and tissue factor in the aorta, in parallel with decreased expression of RAGE and EN-RAGEs. Diabetic kidney demonstrated increased numbers of EN-RAGE-expressing inflammatory cells infiltrating the glomerulus and enhanced mRNA for transforming growth factor-β, fibronectin, and α1 (IV) collagen. In mice treated with soluble RAGE, the numbers of infiltrating inflammatory cells and mRNA levels for these glomerular cytokines and components of extracellular matrix were decreased. These data suggest that activation of RAGE primes cells targeted for perturbation in diabetic tissues by the induction of proinflammatory mediators.
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.llmch.recept
Keywords: Atherosclerosis; Diabetes; Glycation; Nephropathy; Receptor for advanced glycation end products

Reduced Circulating AGE Levels and Lower Genomic Damage in Patients Undergoing Daily versus Standard Hemodialysis - Fragedaki, Evangelia; Nebel, Michael; Schupp, Nicole; Sebekova, Katarina; Völkel, Wolfgang; Klassen, Andre; Pischetsrieder, Monika; Frischmann, Matthias; Niwa, Toshimitsu; Vienken, Jörg; Heidland, August; Stopper, Helga (Annals of the New York Academy of Sciences, 2005)
UnivIS-Import:2015-04-16:Pub.2005.nat.dchph.llmch.reduce

Regioisomeric distribution of 9-and 13-hydroperoxy linoleic acid in vegetable oils during storage and heating - Pignitter, Marc; Zaunschirm, Mathias; Lach, Judith; Unterberger, Laura; Kopic, Antonio; Kessler, Claudia; Kienesberger, Julia; Pischetsrieder, Monika; Eggersdorfer, Manfred; Riegger, Christoph; Somoza, Veronika (Journal of the Science of Food and Agriculture, 2018)
CONCLUSIONA temperature-dependent distribution of HpODE regioisomers could be shown in vegetable oils, suggesting their application as markers of lipid oxidation in oils used for short-term heating. (c) 2017 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: lipid hydroperoxides; linoleic acid; heating; storage; vegetable oil

Regioselective analysis of heat-induced conformational changes of β-lactoglobulin by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics - Liu, Jiajia; Gensberger-Reigl, Sabrina; Zenker, Hannah; Schichtl, Theresa Maria; Utz, Wolfgang; Pischetsrieder, Monika (Food Chemistry, 2024)
β-Lactoglobulin is a main allergen in cow's milk; its allergenicity is strongly impacted by processing. To understand heat-induced epitope-specific effects, the present study analyzed regiospecific conformational changes of heated native β-lactoglobulin variant A (BLG-A). Complementary fluorescence spectroscopy methods indicated two denaturation phases comprising minor sequential conformational changes (25–75 °C) and complete transitions (80–90 °C). Regioselective conformational changes of BLG-A in the native state (25 °C), sequential (70 °C) and complete transition (90 °C) were determined by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics covering 14 lysine residues and the N-terminus. Conformational changes in two phases were observed for N-terminus, K8 (both N-terminal chain), K60 (β-sheet C), K75 (β-sheet D), K77 (DE loop), K83 (β-sheet E), K100 and K101 (FG loop). The residues K14 (β-sheet A1), K47 (β-sheet B), K69, K70 (both β-sheet D), and K91 (β-sheet F) were not involved in conformational changes.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Allergenic epitopes; Chemical labeling kinetics; Conformational changes; Heat-processing; Quantitative liquid chromatography–mass spectrometry analysis; β-Lactoglobulin

Relative Quantification of N-(Carboxymethyl)lysine, Imidazolone A, and the Amadori Product in Glycated Lysozyme be MALDI-TOF Mass Spectrometry - Kislinger, Thomas; Humeny, Andreas; Peich, Carlo; Zhang, Xiaohong; Niwa, Toshimitsu; Pischetsrieder, Monika; Becker, Cord-Michael (Journal of Agricultural and Food Chemistry, 2003)
The nonenzymatic glycation of proteins by reducing sugars, also known as the Maillard reaction, has received increasing recognition from nutritional science and medical research. In this study, we applied matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) to perform relative and simultaneous quantification of the Amadori product, which is an early glycation product, and of Nε-(carboxymethyl)lysine and imidazolone A, two important advanced glycation end products. Therefore, native lysozyme was incubated with D-glucose for increasing periods of time (1, 4, 8, and 16 weeks) in phosphate-buffered saline pH 7.8 at 50 °C. After enzymatic digestion with endoproteinase Glu-C, the N-terminal peptide fragment (m/z 838; amino acid sequence KVFGRCE) and the C-terminal peptide fragment (m/z 1202; amino acid sequence VQAWIRGCRL) were used for relative quantification of the three Maillard products. Amadori product, Nε-(carboxymethyl)lysine, and imidazolone A were the main glycation products formed under these conditions. Their formation was dependent on glucose concentration and reaction time. The kinetics were similar to those obtained by competitive ELISA, an established method for quantification of Nε-(carboxymethyl)lysine and imidazolone A. Inhibition experiments showed that coincubation with Nα-acetylargine suppressed formation of imidazolone A but not of the Amadori product or Nε-(carboxymethyl)lysine. The presence of Nα-acetyllysine resulted in the inhibition of lysine modifications but in higher concentrations of imidazolone A. o-Phenylenediamine decreased the yield of the Amadori product and completely inhibited the formation of Nε-(carboxymethyl)lysine and imidazolone A. MALDI-TOF-MS proved to be a new analytical tool for the simultaneous, relative quantification of specific products of the Maillard reaction. For the first time, kinetic data of defined products on specific sites of glycated protein could be measured. This characterizes MALDI-TOF-MS as a valuable method for monitoring the Maillard reaction in the course of food processing.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.relati
Keywords: Amadori product; Imidazolone A; Maillard reaction; MALDI-TOF-MS; N; Protein glycation

Role of AGEs and growth factors in peritoneal dysfunction in CAPD patients - Nakamura, Sakurako; Tachikawa, Tetsuya; Tobita, Kazuki; Miyazaki, Shigeru; Sakai, Shinji; Morita, Takashi; Hirasawa, Yoshihei; Weigle, Bernd; Pischetsrieder, Monika; Niwa, Toshimitsu (American Journal of Kidney Diseases, 2003)
High levels of glucose degradation products in peritoneal dialysis fluids are believed to cause excess accumulation of advanced glycation end products (AGEs) in the peritoneum during continuous ambulatory peritoneal dialysis (CAPD) treatment, resulting in functional and structural changes in the peritoneal membrane of CAPD patients. In this study, we investigated whether AGEs, the receptor for AGE (RAGE), and growth factors are involved in deteriorating ultrafiltration (UF) capacity of the peritoneal membrane in patients on CAPD therapy. Immunohistochemical staining showed that ODI-GLC19, a novel monoclonal anti-AGE antibody, was localized exclusively in peritoneal cells, in contrast to imidazolone, localized mostly in peritoneal degenerative collagen. Numbers of ODI-GLC19– and RAGE-positive cells in the peritoneum were increased significantly in CAPD patients, even before a decrease in UF capacity, compared with patients with nonrenal disease. Cells positive for ODI-GLC19 were identified as myofibroblasts and RAGE-positive cells and partly as CD68-positive macrophages in the peritoneum. The peritoneal membrane was thickened significantly in CAPD patients, especially patients with low UF. The number of blood vessels was increased significantly in CAPD patients with low UF. Transforming growth factor-beta1, macrophage colony-stimulating factor, and vascular endothelial growth factor were recognized in the peritoneum of CAPD patients, especially those with low UF, where imidazolone was deposited. Focal hepatocyte growth factor expression was noted in the peritoneum of patients with low UF in moderate intensity, specifically in the area without severe structural changes. In conclusion, progressive accumulation of AGEs in the peritoneum may promote peritoneal expression of various growth factors and subsequently deteriorate UF capacity in CAPD patients.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.llmch.roleof
Keywords: Advanced glycation end products (AGEs); receptor for advanced glycation end product (RAGE); continuous ambulatory peritoneal dialysis (CAPD); peritoneum; growth factors; imidazolone.

S-allyl-L-cysteine and isoliquiritigenin improve mitochondrial function in cellular models of oxidative and nitrosative stress - Denzer, Isabel; Münch, Gerald; Pischetsrieder, Monika; Friedland, Kristina (Food Chemistry, 2016)
Oxidative and nitrosative stress resulting in mitochondria( dysfunction are an early event in the pathogenesis of Alzheimer's disease (AD). Nuclear factor erythroid-2-related factor 2 (Nrf2) is a key transcription factor and regulator of the cellular response to oxidative stress. Thus known Nrf2 activators from food materials were tested for improvement of mitochondrial membrane potential (MMP) and ATP level in neuronal pheochromocytoma cell (PC12) models of oxidative and nitrosative stress. The effects of rotenone and sodium nitroprusside (complex inhibitors of the respiratory chain) on mitochondrial function were also studied. Furthermore, Nrf2 activators were tested in human embryonic kidney cells bearing the Swedish mutation of amyloid precursor protein (APP(sw) HEK cells) as a cellular model of familial AD. Preincubation with S-allyl-L-cysteine and isoliquiritigenin increased MMP in both PC12 cell models in a similar range as the positive control L-sulforaphane. None of the test compounds, however, improved MMP and ATP level in APP(sw) HEK cells. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Mitochondrial dysfunction; Oxidative stress; Nrf2; Alzheimer's disease; Aging

Site-specific formation of Maillard, oxidation, and condensation products from whey proteins during reaction with lactose - Meltretter, Jasmin; Seeber, Silke; Humeny, Andreas; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2007)
Heat treatment of dairy products leads to structural changes of proteins, which can severely decrease the nutritional value [Mauron, J. J. Nutr. Sci. Vitaminol. (Tokyo) 1990, 36(Suppl. 1), S57-69]. In this study, model solutions of the two main whey proteins, α-lactalbumin and β-lactoglobulin, respectively, were incubated with lactose, and modifications were monitored by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Lactulosyl residues were the most abundant modifications of α-lactalbumin and β-lactoglobulin. Up to four of these adducts were identified on the proteins. Enzymatical digest with endoproteinase AspN prior to mass spectrometric analysis allowed the detection of further modifications and their localization in the amino acid sequence. Most prominent modifications were lactulosyllysine, Nε-carboxymethyllysine, oxidation of lysine to aminoadipic semialdehyde, oxidation of methionine to methionine sulfoxide, cyclization of N-terminal glutamic acid to a pyrrolidone, and oxidation of cysteine or tryptophan. The presence of methionine oxidation was deduced from a control protein that had been oxidized by hydrogen peroxide. These studies establish MALDI-TOF-MS as a reliable tool to monitor chemical modifications of nutritional proteins during food processing. © 2007 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.sitesp
Keywords: α-lactalbumin; β-lactoglobulin; Glycation; Maillard reaction; Matrix-assisted laser desorption/ionization mass spectrometry; Milk; Oxidation; Site specific

Small-sized microplastics and pigmented particles in bottled mineral water - Oßmann, Barbara; Sarau, George; Holtmannspötter, Heinrich; Pischetsrieder, Monika; Christiansen, Silke; Dicke, Wilhelm (Water Research, 2018)
Up to now, only a few studies about microparticle contamination of bottled mineral water have been published. The smallest analysed particle size was 5 gm. However, due to toxicological reasons, especially microparticles smaller than 1.5 mu m are critically discussed. Therefore, in the present study, 32 samples of bottled mineral water were investigated for contamination by microplastics, pigment and additive particles. Due to the application of aluminium coated polycarbonate membrane filters and micro-Raman spectroscopy, a lowest analysed particle size of 1 mu m was achieved.Microplastics were found in water from all bottle types: in single use and reusable bottles made of poly(ethylene terephthalate) (PET) as well as in glass bottles. The amount of microplastics in mineral water varied from 2649 +/- 2857 per litre in single use PET bottles up to 6292 +/- 10521 per litre in glass bottles. While in plastic bottles, the predominant polymer type was PET; in glass bottles various polymers such as polyethylene or styrene-butadiene-copolymer were found. Hence, besides the packaging itself, other contamination sources have to be considered.Pigment particles were detected in high amounts in reusable, paper labelled bottles (195047 +/- 330810 pigment particles per litre in glass and 23594 +/- 25518 pigment particles per litre in reusable paper labelled PET bottles). Pigment types found in water samples were the same as used for label printing, indicating the bottle cleaning process as possible contamination route.Furthermore, on average 708 +/- 1024 particles per litre of the additive Tris(2,4-di-tert-butylphenyl) phosphite were found in reusable PET bottles. This additive might be leached out from the bottle material itself.Over 90% of the detected microplastics and pigment particles were smaller than 5 mu m and thus not covered by previous studies. In summary, this is the first study reporting about microplastics, pigment and additive particles found in bottled mineral water samples with a smallest analysed particle size of 1 mu m. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Microplastics; Pigments; Bottled mineral water; Micro-Raman spectroscopy; Food

Snack food as a modulator of human resting-state functional connectivity. - Mendez Torrijos, Andrea; Kreitz, Silke; Ivan, Claudiu-Ionut; Konerth, Laura; Rösch, Julie; Pischetsrieder, Monika; Moll, Gunther; Kratz, Oliver; Dörfler, Arnd; Horndasch, Stefanie; Hess, Andreas (Cns Spectrums, 2018)
OBJECTIVE To elucidate the mechanisms of how snack foods may induce non-homeostatic food intake, we used resting state functional magnetic resonance imaging (fMRI), as resting state networks can individually adapt to experience after short time exposures. In addition, we used graph theoretical analysis together with machine learning techniques (support vector machine) to identifying biomarkers that can categorize between high-caloric (potato chips) vs. low-caloric (zucchini) food stimulation. METHODS Seventeen healthy human subjects with body mass index (BMI) 19 to 27 underwent 2 different fMRI sessions where an initial resting state scan was acquired, followed by visual presentation of different images of potato chips and zucchini. There was then a 5-minute pause to ingest food (day 1=potato chips, day 3=zucchini), followed by a second resting state scan. fMRI data were further analyzed using graph theory analysis and support vector machine techniques. RESULTS Potato chips vs. zucchini stimulation led to significant connectivity changes. The support vector machine was able to accurately categorize the 2 types of food stimuli with 100% accuracy. Visual, auditory, and somatosensory structures, as well as thalamus, insula, and basal ganglia were found to be important for food classification. After potato chips consumption, the BMI was associated with the path length and degree in nucleus accumbens, middle temporal gyrus, and thalamus. CONCLUSION The results suggest that high vs. low caloric food stimulation in healthy individuals can induce significant changes in resting state networks. These changes can be detected using graph theory measures in conjunction with support vector machine. Additionally, we found that the BMI affects the response of the nucleus accumbens when high caloric food is consume
Keywords: Food intake; graph theory; resting state networks; RS-fMRi; snack food; support vector machine

Snack food intake in ad libitum fed rats is triggered by the combination of fat and carbohydrates - Hoch, Tobias; Pischetsrieder, Monika; Heß, Andreas (Frontiers in Psychology, 2014)
Snack food like potato chips substantially contributes to energy intake in humans. In contrast to basic food, snacks are consumed additionally to other meals and may thereby lead to non-homeostatic energy intake. Snack food is also frequently associated with hedonic hyperphagia, a food intake independent from hunger. Analysis of brain activity patterns by manganese-enhanced MRI has previously revealed that the intake of potato chips in ad libitum fed rats strongly activates the reward system of the rat brain, which may lead to hedonic hyperphagia. The purpose of the present study was to develop a two-choice preference test to identify molecular determinants of snack food triggering extra food intake in ad libitum fed rats. Different kinds of test food were presented three times a day for 10 min each time. To minimize the influence of organoleptic properties, each test food was applied in a homogenous mixture with standard chow. Food intake as well as food intake-related locomotor activity were analyzed to evaluate the effects induced by the test foods in the two-choice preference test. In summary, fat (F), carbohydrates (CH), and a mixture of fat and carbohydrates (FCH) led to a higher food intake compared to standard chow. Notably, potato chip test food (PC) was highly significantly preferred over standard chow (STD) and also over their single main macronutrients F and CH. Only FCH induced an intake comparable to PC. Despite its low energy density, fat-free potato chip test food (ffPC) was also significantly preferred over STD and CH, but not over F, FCH, and PC. Thus, it can be concluded that the combination of fat and carbohydrates is a major molecular determinant of potato chips triggering hedonic hyperphagia. The applied two-choice preference test will facilitate future studies on stimulating and suppressive effects of other food components on non-homeostatic food intake. © 2014 Hoch, Pischetsrieder and Hess.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.snackf
Keywords: Eating behavior; Food intake; Macronutrients; Preference test; Rat; Snack food

Stability and activity of the antimicrobial peptide leg1 in solution and on meat and its optimized generation from chickpea storage protein - Heymich, Marie-Louise; Srirangan, Showmika; Pischetsrieder, Monika (Foods, 2021)
The antimicrobial peptide Leg1 (RIKTVTSFDLPALRFLKL) from chickpea legumin is active against spoilage bacteria, yeast, and mold. The present study tested its effectiveness under food storage conditions and examined options to obtain a food-grade agent. The minimum inhibitory concentration (MIC) of Leg1 against E. coli (62.5 µM) proved stable over seven days at 20◦ C or 4◦ C. It was not influenced by reduced pH (5.0 vs. 6.8), which is relevant in food such as meat. An incubation temperature of 20◦ C vs. 37◦ C reduced the MIC to 15.6/7.8 µM against E. coli/B. subtilis. With a minimum bactericidal concentration in meat of 125/15.6 µM against E. coli/B. subtilis, Leg1 is equivalently effective as nisin and 5000–82,000 times more active than sodium benzoate, potassium sorbate, or sodium nitrite. Replacing the counter-ion trifluoroacetate derived from peptide synthesis by the more natural alternatives acetate or chloride did not impair the activity of Leg1. As an alternative to chemical synthesis, an optimized protocol for chymotryptic hydrolysis was developed, increasing the yield from chickpea legumin by a factor of 30 compared to the standard procedure. The present results indicate that food-grade Leg1 could possibly be applicable for food preservation.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antimicrobial peptides; Chickpea; Chymotryptic hydrolysis; Counter-ions; Digestion optimization; Leg1; Meat

Structure- and concentration-specific assessment of the physiological reactivity of alpha-dicarbonyl glucose degradation products in peritoneal dialysis fluids - Distler, Leonie; Georgieva, Angelina; Kenkell, Isabell; Huppert, Jochen; Pischetsrieder, Monika (Chemical Research in Toxicology, 2014)
In peritoneal dialysis (PD), glucose degradation products (GDPs), which are formed during heat sterilization of dialysis fluids, lead to structural and functional changes in the peritoneal membrane, which eventually result in the loss of its ultrafiltration capacity. To determine the molecular mechanisms behind these processes, the present study tested the influence of the six major α-dicarbonyl GDPs in PD fluids, namely, glyoxal, methylglyoxal, 3-deoxyglucosone (3-DG), 3-deoxygalactosone (3-DGal), 3,4-dideoxyglucosone-3-ene (3,4-DGE), and glucosone with respect to their potential to impair the enzymatic activity of RNase A as well as their effects on cell viability. For comprehensive risk assessment, the α-dicarbonyl GDPs were applied separately and in concentrations as present in conventional PD fluids. Thus, it was shown that after 5 days, glucosone impaired RNase A activity most distinctly (58% remaining activity, p < 0.001 compared to that of the control), followed by 3,4-DGE (62%, p < 0.001), 3-DGal (66%, p < 0.001), and 3-DG (76%, p < 0.01). Methylglyoxal and glyoxal caused weaker inactivation with significant effects only after 10 days of incubation (79%, 81%, p < 0.001). Profiling of the advanced glycation end products formed during the incubation of RNase A with methylglyoxal revealed predominant formation of the arginine modifications imidazolinone, CEA/dihydroxyimidazoline, and tetrahydropyrimidine at Arg10, Arg33, Arg39, and Arg85. Particularly, modification at Arg39 may severely affect the active site of the enzyme. Additionally, structure- and concentration-specific assessment of the cytotoxicity of the α-dicarbonyl GDPs was performed. Although present at very low concentration, the cytotoxic effect of PD fluids after 2 days of incubation was exclusively caused by 3,4-DGE (14% cell viability, p < 0.001). After 4 days of incubation, 3-DGal (13% cell viability, p < 0.001), 3-DG (24%, p < 0.001), and, to a lower extent, glyoxal and methylglyoxal (both 57%, p < 0.01) also reduced cell viability significantly. In conclusion, 3,4-DGE, 3-DGal, and glucosone appear to be the most relevant parameters for the biocompatibility of PD fluids. © 2014 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.struct

Targeted label-free quantification of interleukin-8 in PMA-activated U937 cell secretome by nanoLC-ESI-MS/MS-sSRM. - Emirbayer, Pelin Esma; Gerer, Kerstin; Hoyer, Stefanie; Pischetsrieder, Monika (Proteomics, 2017)
Monocytes are a part of the innate immune system. Their differentiation into macrophages changes their cellular proteome and secretome. Particularly secretome components such as cytokines are crucial for immune response and inflammation in many diseases. Differentiation of human lymphoma cell line U937 can be triggered by phorbol 12-myristate 13-acetate (PMA). Screening of the cytokine release in U937 upon PMA stimulation by cytometric bead array almost exclusively showed interleukin-8. Next, a label-free nanoLC-ESI-MS/MS-sSRM method for quantification of interleukin-8 in the cell secretome was established and applied to monitor the time kinetics of PMA treatment in different concentrations. Targeted secretome analysis was achieved by scheduled SRM-MS using one proteotypic peptide as precursor ion and four mass transitions. Label-free quantification was performed by external calibration using interleukin-8 standard. Validation results indicated that the method was suited for the quantification of interleukin-8 in the secretome. The maximal interleukin-8 release of 62.4 ng/mL was observed after incubating cells treated by 50 ng/mL PMA for 48 h. The method can now be used for quantification of interleukin-8 release from different cells under various conditions. Furthermore, it can be easily expanded to other secreted proteins detected by untargeted screening methods. This article is protected by copyright. All rights reserve

Targeted mass spectrometry for the analysis of nutritive modulation of catalase and heme oxygenase-1 expression - Zänglein, Nina; Tucher, Joanna; Pischetsrieder, Monika (Journal of Proteomics, 2015)
Comprehensive physiological food assessment requires recording of activity profiles. To elucidate the nutritive regulation of antioxidant enzymes, a generally applicable targeted MS method was established for the expression analysis of catalase and then adapted to heme oxygenase-1. Before tryptic digestion, target proteins were prefractionated by off-gel IEF of stimulated and control cell lysate. Targeted proteome analysis was achieved by LC coupled with scheduled selected reaction monitoring MS using 2 proteotypic peptides per protein and 3-4 transitions per peptide. Relative quantification was performed by stable isotope labeling by amino acids in cell culture (SILAC). The assay showed good correlation with results by Western blot. Linearity, precision, and sensitivity were even improved (LC/SRM vs. Western blot: 3 vs. 1 orders of magnitude, RSD 3.7-13.7% vs. 18.4%, LOD 0.2 vs. 1.6μg/mL). The developed method indicated that coffee does not modulate catalase expression in macrophages (T7cat 103±22%, T17cat 103±16%, p>0.05 vs. control), but leads to a highly significant increase of heme oxygenase-1 expression (T15Ho-1 420±24%, T22Ho-1 364±37%, p<0.001 vs. control, p>0.05 T15Ho-1 vs. T22Ho-1). In regard to multiplex options of the method, targeted proteome analysis can be a valuable tool for the comprehensive analysis of cellular effects of food components. Biological significance: In the present study, targeted mass spectrometry was applied to determine the influence of food components on the expression of antioxidative enzymes. The results implicate that targeted proteomics may develop into a valuable tool in food science and nutrition to determine the physiological effects of nutrients. In contrast to conventional methods for expression analysis, targeted proteome analysis can be applied to monitor the effects of a food component on a broad range of cellular targets in parallel. Additionally, proteins or protein modifications can be addressed which elude immunochemical methods.
UnivIS-Import:2015-03-09:Pub.2015.nat.dchph.llmch.target
Keywords: Expression analysis; Food proteomics; Nutrition; Selected reaction monitoring; SILAC; Targeted mass spectrometry

Targeted mass spectrometry to monitor nuclear accumulation of endogenous Nrf2 and its application to SH-SY5Y cells stimulated with food components. - Östreicher, Christiane; Gensberger-Reigl, Sabrina; Pischetsrieder, Monika (Analytical and Bioanalytical Chemistry, 2019)
The Nrf2 signaling pathway is highly significant for redox homeostasis. Hence, nutrients and drugs activating Nrf2 can prevent oxidative stress-mediated medical conditions. After activation, Nrf2 accumulates in the cell nucleus; therefore, stimulation of Nrf2 by food components and drugs is usually monitored by measuring nuclear Nrf2 levels. The present study developed a targeted mass spectrometry method for the highly reliable quantification of nuclear Nrf2 levels. Three Nrf2-specific peptides were detected after enzymatic digestion of the nuclear fraction by the developed protocol for micro-liquid chromatography-tandem mass spectrometry in scheduled multiple reaction monitoring mode (microLC-MS/MS-sMRM). The method also identified nuclear Nrf2 unequivocally and specifically in the SDS-PAGE fraction of 100-150 kDa. Moreover, highly precise and linear relative quantification was achieved (mean relative standard deviation 8.3%; coefficient of determination 0.998). Incubation experiments in SH-SY5Y neuroblastoma cells revealed significantly up to 6-fold elevated nuclear Nrf2 levels after stimulation with 10 μM carnosol (rosemary), 10 μM sulforaphane (broccoli), or 20 μM cinnamaldehyde (cinnamon). Our results were in very good accordance with conventional Nrf2 western blotting and were highly correlated with the food components' effect on the expression levels of NAD(P)H dehydrogenase [quinone] 1 and thioredoxin reductase 1, two major Nrf2-regulated cytoprotective enzymes. The newly developed microLC-MS/MS-sMRM method shows broad applicability and can serve as a highly selective and reliable method to analyze Nrf2 activation. Graphical abstract ᅟ.
Keywords: Carnosol; NAD(P)H dehydrogenase [quinone]; Nrf2; Scheduled multiple reaction moniotring; Sulforaphane; Targeted mass spectrometry

Targeted proteome analysis with isotope-coded protein labels for monitoring the influence of dietary phytochemicals on the expression of cytoprotective proteins in primary human colon cells - Östreicher, Christiane; Bartenbacher, Sven; Pischetsrieder, Monika (Journal of Proteomics, 2017)
The present study demonstrated that the major components of cinnamon and rosemary, respectively, i.e. cinnamaldehyde and carnosol, are potent alimentary candidates to increase the expression of cytoprotective enzymes in the human colon. Among the investigated enzymes, NAD(P)H dehydrogenase [quinone] 1 (NQO1) was most susceptible towards modulation by phytochemicals. NQ01 exerts its cytoprotective activity by detoxifying electrophilic and oxidative xenobiotics with quinone structure. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Carnosol; cinnamaldehyde; cytoprotective enzymes; primary human colon cells; scheduled selected reaction monitoring; targeted proteome analysis

The beer component hordenine inhibits alcohol addiction-associated behaviours in mice - Li, Yan; Vogel, Christina; Kalinichenko, Liubov; Hübner, Harald; Weikert, Dorothée; Schaefer, Natascha; Gmeiner, Peter; Villmann, Carmen; Pischetsrieder, Monika; Müller, Christian P. (Addiction Biology, 2023)
Alcohol consumption is a widespread behaviour that may eventually result in the development of alcohol use disorder (AUD). Alcohol, however, is rarely consumed in pure form but in fruit- or corn-derived preparations, like beer. These preparations add other compounds to the consumption, which may critically modify alcohol intake and AUD risk. We investigated the effects of hordenine, a barley-derived beer compound on alcohol use-related behaviours. We found that the dopamine D2 receptor agonist hordenine (50 mg/kg) limited ongoing alcohol consumption and prophylactically diminished relapse drinking after withdrawal in mice. Although not having reinforcing effects on its own, hordenine blocked the establishment of alcohol-induced conditioned place preference (CPP). However, it independently enhanced alcohol CPP retrieval. Hordenine had a dose-dependent inhibitory effect on locomotor activity. Chronic hordenine exposure enhanced monoamine tissue levels in many brain regions. Further characterization revealed monoaminergic binding sites of hordenine and found a strong binding on the serotonin and dopamine transporters, and dopamine D3, and adrenergic α1A and α2A receptor activation but no effects on GABAA receptor or glycinergic signalling. These findings suggest that natural ingredients of beer, like hordenine, may work as an inhibitory and use-regulating factor by their modulation of monoaminergic signalling in the brain.
CRIS-Team Scopus Importer:2023-08-11
Keywords: addiction; alcohol; conditioned preference; drinking; hordenine

The Euro-Balance Trial: The effect of a new biocompatible peritoneal dialysis fluid (balance) on the peritoneal membrane - Williams, John D.; Topley, Nicholas; Craig, Kathrine J.; Mackenzie, Ruth K.; Pischetsrieder, Monika; Lage, Cristina; Passlick-Deetjen, Jutta (Kidney International, 2004)
Background. Although peritoneal dialysis (PD) is a widely accepted form of renal replacement therapy (RRT), concerns remain regarding the bioincompatible nature of standard PD fluid. In order to evaluate whether a newly formulated fluid of neutral pH, and containing low levels of glucose degradation products (GDP), resulted in improved in vivo biocompatibility, it was compared in a clinical study to a standard PD fluid. Methods. In a multicenter, open, randomized, prospective study with a crossover design and parallel arms, a conventional, acidic, lactate-buffered fluid (SPDF) was compared with a pH neutral, lactate-buffered, low GDP fluid (balance). Overnight effluent was collected and assayed for cancer antigen 125 (CA125), hyaluronic acid (HA), procollagen peptide (PICP), vascular endothelial growth factor (VEGF), and tumor necrosis factor alpha (TNFα). Serum samples were assayed for circulating advanced glycosylation end products (AGE), Nε-(carboxymethyl) lysine (CML), and imidazolone. Clinical end points were residual renal function (RRF), adequacy of dialysis, ultrafiltration, and peritoneal membrane function. Eighty-six patients were randomized to either group I starting with SPDF for 12 weeks (Phase I), then switching to "balance" for 12 weeks (Phase II), or group II, which was treated vice versa. Seventy-one patients completed the study with data suitable for entry into the per protocol analysis. Effluent and serum samples, together with peritoneal function tests and adequacy measurements, were undertaken at study centers on three occasions during the study: after the four-week run-in period, after Phase I, and again after Phase II. Results. In patients treated with balance there were significantly higher effluent levels of CA125 and PICP in both arms of the study. Conversely, levels of HA were lower in patients exposed to balance, while there was no change in the levels of either VEGF or TNFα. Serum CML and imidazolone levels fell significantly in balance-treated patients. Renal urea and creatinine clearances were higher in both treatment arms after patients were exposed to balance. Urine volume was higher in patients exposed to balance. In contrast, peritoneal ultrafiltration was higher in patients on SPDF. When anuric patients were analyzed as a subgroup, there was no significant difference in peritoneal transport characteristics or in ultrafiltration on either fluid. There were no changes in peritonitis incidence on either solution. Conclusion. This study indicates that the use of balance, a neutral pH, low GDP fluid, is accompanied by a significant improvement in effluent markers of peritoneal membrane integrity and significantly decreased circulating AGE levels. Clinical parameters suggest an improvement in residual renal function on balance, with an accompanying decrease in peritoneal ultrafiltration. It would appear that balance solution results in an improvement in local peritoneal homeostasis, as well as having a positive impact on systemic parameters, including circulating AGE and residual renal function.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.llmch.theeur
Keywords: Biocompatibility; Cancer antigen 125; Glucose degradation products; pH neutral; Residual renal function; Ultrafiltration

The terpenoids Myrtenol and Verbenol act on δ subunit-containing GABAA receptors and enhance tonic inhibition in dentate gyrus granule cells. - van Brederode, Johannes; Milanos, Sinem; Kessler, Artur; Pischetsrieder, Monika; Villmann, Carmen; Alzheimer, Christian (Neuroscience Letters, 2016)
Sideritis plants and their extracts have been used in traditional medicine as sedatives, anxiolytics and anticonvulsant agents. Pinenes are the most prevalent of the volatile aroma components in Siderites extracts and the pinene metabolites myrtenol and verbenol have been identified as the most potent positive allosteric modulators of synaptic GABAA receptors composed of α1β2 and α1β2γ2 subunits. In view of their therapeutic spectrum, we wondered whether these two terpenoids would also augment tonic GABA currents mediated by extrasynaptic GABAA receptors containing the δ subunit. When we expressed α4β2δ receptors in HEK293 cells, we found that co-application of myrtenol or verbenol enhanced whole-cell current responses to GABA by up to 100%. Consistent with their effects on heterologous α1β2γ2 receptors, we found that myrtenol and verbenol, when co-applied with GABA via local perfusion, increased the amplitude and area of miniature inhibitory postsynaptic potentials (mIPSCs) recorded in whole-cell voltage-clamp recordings from granule cells in the dentate gyrus of mouse hippocampal brain slices. In addition, co-application of terpenoids with GABA was also able to enhance tonic GABA current, measured from the change in baseline current and current noise, compared to GABA perfusion alone. Our results suggest that myrtenol and verbenol act as positive allosteric modulators at synaptic and extrasynaptic GABAA receptors, thereby augmenting phasic and tonic GABAergic inhibition. Thus, our study reveals an important pharmacological and therapeutic target of bicyclic monoterpenoids.

Three-step test system for the identification of novel GABAa receptor modulating food plants - Sahin, Sümeyye; Eulenburg, Volker; Kreis, Wolfgang; Villmann, Carmen; Pischetsrieder, Monika (Plant Foods For Human Nutrition, 2016)
Potentiation of γ-amino butyric acid (GABA)-induced GABAA receptor (GABAAR) activation is a common pathway to achieve sedative, sleep-enhancing, anxiolytic, and antidepressant effects. Presently, a three-component test system was established for the identification of novel GABAAR modulating food plants. In the first step, potentiation of GABA-induced response of the GABAAR was analysed by two-electrode voltage clamp (TEVC) for activity on human α1β2-GABAAR expressed in Xenopus laevis oocytes. Positively tested food plants were then subjected to quantification of GABA content by high-performance liquid chromatography with fluorescence detection (HPLC–FLD) to exclude test foods, which evoke a TEVC-response by endogenous GABA. In the third step, specificity of GABAA-modulating activity was assessed by TEVC analysis of Xenopus laevis oocytes expressing the homologous glycine receptor (GlyR). The three-component test was then applied to screen 10 aqueous extracts of food plants for their GABAAR activity. Thus, hop cones (Humulus lupulus) and Sideritis sipylea were identified as the most potent specific GABAAR modulators eliciting significant potentiation of the current by 182 ± 27 and 172 ± 19 %, respectively, at the lowest concentration of 0.5 μg/mL. The extracts can now be further evaluated by in vivo studies and by structural evaluation of the active components.
EVALuna2:4740
Keywords: GABAA receptor; GABA; Glycine receptor; Sideritis; Lemon balm leaves; Hop cones

Two immunochemical assays to measure advanced glycation end-products in serum from dialysis patients - Zhang, Xiaohong; Frischmann, Matthias; Kientsch-Engel, Rose; Steinmann, Katharina; Stopper, Helga; Niwa, Toshimitsu; Pischetsrieder, Monika (Clinical Chemistry and Laboratory Medicine, 2005)
Advanced glycation end-products are uremic toxins that accumulate in the serum and tissues of patients with chronic renal failure. Here, we established two enzyme-linked immunosorbent assays (ELISAs) for Nε-carboxymethyllysine and imidazolone to analyze advanced glycation end-products in human serum. Both ELISAs detected advanced glycation endproducts bound to human serum albumin in a dosedependent way. Whereas the formation of imidazolone was independent of the presence of oxygen, concentrations of Nε-carboxymethyllysine epitopes increased 20-fold under oxidative conditions. The Nε-carboxymethyllysine ELISA showed a similar response to free, peptide-bound and protein-bound Nε-carboxymethyllysine, whereas the imidazolone antibody showed slightly higher affinity toward peptide-bound compared to protein-bound imidazolone. In human serum, linear dilution ranges from 1:10 to 1:40 (Nε-carboxymethyllysine ELISA) and from 1:2 to 1:8 (imidazolone ELISA) were found. The recovery of Nε-carboxymethyllysine from serum was 101±10% and 94±12%, respectively, and 93±15% and 97±12% for imidazolone. The coefficients of variation for intraassay variability were 0.26-2.7% (Nε-carboxymethyllysine) and 0.1-2.4% (imidazolone), and 8.3-13.4% (Nε-carboxymethyllysine) and 7.8-12.5% (imidazolone) for inter-assay variability. In serum samples from hemodialysis patients (n = 20) and controls (n = 20), an approximately two-fold increase was detected in the patient group (p<0.001). The combination of the Nε-carboxymethyllysine and imidazolone ELISAs is a valuable tool to measure serum concentrations of advanced glycation end-products for clinical studies. © 2005 by Walter de Gruyter.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.twoimm
Keywords: Advanced glycation end-products; Enzyme-linked immunosorbent assay (ELISA); Imidazolone; Nε-carboxymethyllysine(CML); Serum

Unchanged serum levels of advanced glycation endproducts in patients with liver disease - Butscheid, Moritz; Schäfer, Christian; Brenner, Stefanie; Alscher, Dominik; Mürdter, Thomas; Niwa, Toshimitsu; Frischmann, Matthias; Pischetsrieder, Monika; Klotz, Ulrich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)
Advanced glycation end products (AGEs), e.g., carboxymethyllysine (CML) or imidazolone are involved in several age-related disorders. Concerning their accumulation, the importance of hepatic and renal function is controversially discussed. To test whether impairment of hepatic or renal function will affect their accumulation, both AGEs have been measured in various populations, such as 52 patients with liver disease [viral hepatitis C without (n = 19) and with (n = 10) fatty liver; nonalcoholic fatty liver (n = 13), nonalcoholic steatohepatitis (n = 10)]. Serum concentrations of both AGEs have been compared to those in 20 healthy controls and 24 patients with moderate renal impairment (creatinine clearance 23-55 ml/min). Concerning CML (95% C.I. 803-1200 ng/ml), no differences between the various groups could be observed. Likewise, serum levels of imidazolone (95% C.I. 1.3-5.6 units) were similar in all populations. In conclusion, moderate impairment in hepatic or in renal function did not affect serum levels of CML and imidazolone. Apparently, any increase observed in severe cirrhosis or renal failure seems to be rather a consequence than a cause of both disorders. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.unchan
Keywords: Accumulation; Carboxymethyllysine; Elimination; Imidazalone; Liver disease; Renal impairment

Untargeted Proteomics-Based Profiling for the Identification of Novel Processing-Induced Protein Modifications in Milk - Meltretter, Jasmin; Wüst, Johannes; Dittrich, Daniel; Lach, Johannes; Ludwig, Jonas; Eichler, Jutta; Pischetsrieder, Monika (Journal of Proteome Research, 2020)
Nonenzymatic post-translational protein modifications (nePTMs) affect the nutritional, physiological, and technological properties of proteins in food and in vivo. In contrast to the usual targeted analyses, the present study determined nePTMs in processed milk in a truly untargeted proteomic approach. Thus, it was possible to determine to which extent known nePTM structures explain protein modifications in processed milk and to detect and identify novel products. The method combined ultrahigh-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry with bioinformatic data analysis by the software XCMS. The nePTMs detected by untargeted profiling of a β-lactoglobulin-lactose model were incorporated in a sensitive scheduled multiple reaction monitoring method to analyze these modifications in milk samples and to monitor their reaction kinetics during thermal treatment. Additionally, we identified the structures of unknown modifications. Lactosylation, carboxymethylation, formylation of lysine and N-terminus, glycation of arginine, oxidation of methionine, tryptophan, and cysteine, oxidative deamination of N-terminus, and deamidation of asparagine and glutamine were the most important reactions of β-lactoglobulin during milk processing. The isomerization of aspartic acid was observed for the first time in milk products, and N-terminal 4-imidazolidinone was identified as a novel nePTM.
CRIS-Team Scopus Importer:2020-02-18
Keywords: mass spectrometry; processed milk; protein modifications; untargeted profiling; β-lactoglobulin

Utility of 1,3,4,6-tetra-O-acetyl-2-deoxy-2[18F]fluoro-glucopyranoside for no-carrier-added 18F-glycosylation of amino acids - Maschauer, Simone; Pischetsrieder, Monika; Kuwert, Torsten; Prante, Olaf (Journal of Labelled Compounds & Radiopharmaceuticals, 2005)
A radiochemical method for the 18F-glycosylation of amino acid side chains was developed starting from peracetylated 2-deoxy-2-[18F]fluoroglucopyranoside (TA-[18F]FDG). O-(2-deoxy-2-[18F]fluoro-d-glucopyranosyl)-l-serine and the corresponding threonyl compound were obtained in a radiochemical yield of 25% and 12% (related to [18F]fluoride), respectively, after Zemple´n deprotection within a total reaction time of 90 min. The anomeric configuration of the corresponding 19Fsubstituted compounds revealed preferential a-stereoselectivity. The 18F-glycosylation method using TA-[18F]FDG is compatible with the short half-life of fluorine-18 and combines glycosylation and 18F-labelling of a target compound within a single reaction step. TA-[18F]FDG is a promising 18F-labelled prosthetic group and could be adapted to 18F-labelling of bioactive peptides to study their pharmacokinetics using positron emission tomography (PET).
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.llmch.utilit
Keywords: 18F-glycosylation; F-18; glycosidic linkage; positron-emission-tomography; PET

Versatile Features of an Antibody Mimetic Peptide and Its Variants - Dolles, Simon; Leukel, Simon; Gensberger-Reigl, Sabrina; Rohrhofer, Anette; Rauch-Wirth, Lena; Kaygisiz, Kübra; Synatschke, Christopher V; Münch, Jan; Schmidt, Barbara; Pischetsrieder, Monika; Eichler, Jutta (Journal of Peptide Science, 2025)
Antibody mimetic peptides have evolved as versatile tools for biomedical applications, based on their ability to interfere with protein–protein interactions. We had previously designed a functional mimic of the broadly neutralizing HIV-1 antibody b12 that recognizes the CD4 binding site of the HIV-1 envelope glycoprotein gp120. The molecular details of the interaction of a linear variant of this peptide (H1H3s) with gp120 have now been characterized through cross-linking mass spectrometry, confirming the proposed involvement of the CD4 binding site of gp120 in the interaction. In addition, a variant of the b12 mimetic peptide composed mostly of D-amino acids was shown to be stable towards proteolytic degradation, while the binding and HIV-1 neutralizing properties were largely preserved. Furthermore, a peptide variant in which aspartate residues were replaced with lysine was shown to strongly enhance infection of cells with HIV-1 and GALV glycoprotein pseudotyped viral vectors, respectively, introducing this peptide as a tool to facilitate retroviral gene transfer. Collectively, the presented results highlight the versatile potential therapeutic and gene transfer applications of H1H3s and its variants in particular, as well as antibody mimetic peptides in general.
CRIS-Team Scopus Importer:2025-02-28
Keywords: antibody mimetic peptides; D-amino acid peptides; gp120; HIV-1; infection enhancement; mAb b12; peptide nanofibrils

Virtual screening of a milk peptide database for the identification of food-derived antimicrobial peptides - Liu, Yufang; Eichler, Jutta; Pischetsrieder, Monika (Molecular Nutrition & Food Research, 2015)
Scope: Milk provides a wide range of bioactive substances, such as antimicrobial peptides and proteins. Our study aimed to identify novel antimicrobial peptides naturally present in milk. Methods and results: The components of an endogenous bovine milk peptide database were virtually screened for charge, amphipathy, and predicted secondary structure. Thus, 23 of 248 screened peptides were identified as candidates for antimicrobial effects. After commercial synthesis, their antimicrobial activities were determined against Escherichia coli NEB5 alpha, E. coli ATCC25922, and Bacillus subtilis ATCC6051. In the tested concentration range (<2 mM), bacteriostatic activity of 14 peptides was detected including nine peptides inhibiting both Gram-positive and Gram-negative bacteria. The most effective fragment was TKLTEEEKNRLNFLKKISQRYQKFALPQYLK corresponding to alpha(S2)-casein151–181, with minimum inhibitory concentration (MIC) of 4.0 muM against B. subtilis ATCC6051, and minimum inhibitory concentrations of 16.2 M against both E. coli strains. Circular dichroism spectroscopy revealed conformational changes of most active peptides in a membrane-mimic environment, transitioning from an unordered to alpha-helical structure. Conclusion: Screening of food peptide databases by prediction tools is an efficient method to identify novel antimicrobial food-derived peptides. Milk-derived antimicrobial peptides may have potential use as functional food ingredients and help to understand the molecular mechanisms of anti-infective milk effects.
Keywords: antimicrobial peptide; circular dichroism; milk; Peptide database; virtual screening